A 9-year analysis of transoral laser microsurgery (TLM) of head and neck cancer on their potential suitability for transoral robotic surgery (TORS) for estimation of future TORS-specific caseload - Von Scotti, F.; Kapsreiter, M.; Scherl, C.; Iro, Heinrich; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2018)
OBJECTIVE: After that the establishment of transoral robotic surgery (TORS) for head and neck cancer has been adopted in North America, it has also recently been adopted in Europe. In these parts, transoral laser microsurgery (TLM) is widely applied. The aim of the study was to identify the absolute number of operations amenable to TORS at a TORS initiating institution on the basis of all former TLM cases. PATIENTS AND METHODS: All laser surgery procedures from May 2004 to April 2013 (108 months) were initially retrospectively registered; after that, all stage pT1 and pT2 squamous cell carcinomas of the oropharynx, hypopharynx, and larynx were selected. RESULTS: Over a period of nine years out of all TLM cases, there were 45 cases of pT1 and pT2 orohypopharyngeal and supraglottic squamous cell carcinomas, which could have been considered for TORS surgery. With the inclusion of a nowadays-typical TORS indication such as tonsil cancer, 142 cases would have been amendable to TORS. CONCLUSIONS: The indication for TORS would have been made in five of the TLM cases per year. Institutions initiating TORS, which own an intensive TLM experience, are encouraged to TORS indications in more than solely typical TLM indications. By indicating TORS instead of handheld surgery, a higher caseload of more than 15 cases per year can be achieved for TORS indications.
EVALuna2:35389

Abscesstonsillectomy: Uni- or bilateral? - Fauck, Vanessa; Schinz, Katharina; Alexiou, Christoph; Mantsopoulos, Konstantinos; Iro, Heinrich; Müller, Sarina Katrin (Laryngo-Rhino-Otologie, 2022)
Objective In addition to an empirical use of antibiotics for treatment of a peritonsillar abscess (PTA) there is a drainage of pus or the abscess tonsillectomy. Postoperative bleeding after abscesstonsillectomy (ABTE) is this surgery's most feared complication which can rarely lead to patients' deaths. The objective of this study was to compare bleeding complications of ABTE with and without contralateral tonsillectomy (TE) and to analyze the occurrence of a metachronous PTA at the contralateral side. Methods Retrospective study of n= 655 patients undergoing ABTE with and without TE of the contralateral side from January 2004 to February 2019. Bleeding complications needing surgical hemostasis were analyzed regarding demographic and surgical parameters. In addition, occurrence of PTA and need for ABTE of the contralateral side after unilateral ABTE were evaluated. Results Overall, 10/655 (1.5 %) patients presented with postoperative bleeding after ABTE. In 404/655 an ABTE with contralateral TE was performed. Here, 8/404 (1.98 %) patients showed contra- or bilateral bleeding. Only in 2/251 (0.7 %) patients occurred a bleeding complication after unilateral ABTE. Therefore, bleeding after unilateral ABTE was significantly lower than ABTE with contralateral TE (1.98 % vs. 0.7 %, p= 0.001). In 0.8 % of the patients a contralateral ABTE was necessary due to a metachronous PTA. Conclusion Overall, the rate of postoperative bleeding after ABTE (1.5 %) was low. Unilateral ABTE showed significantly lower postoperative bleeding rates compared to ABTE with contralateral TE. Consequently, the indication of a contralateral TE must be very strict.
CRIS-Team WoS Importer:2022-06-03

A comparison between p16-positive head and neck cancer of unknown primary (HPV-HNCUP) and oropharyngeal squamous cell carcinoma (HPV-OPSCC): are they the same disease? - Balk, Matthias; Rupp, Robin; Sievert, Matti; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Introduction: The following study aimed to answer the question if HPV-HNCUP and HPV-OPSCC are the same disease. Propensity score matching (PSM) was used to compare the oncological outcomes of both groups, in particular the 5-year overall survival rate (OS), the 5-year disease specific survival rate (DSS) and the 5-year progression free survival rate (PFS). Materials and methods: Firstly, between January 1st, 2007, and March 31st, 2020 a total of 131 patients were treated with HNCUP at our Department. Out of these, 21 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. Secondly, between January 1st, 2000, and January 31st, 2017, a total of 1596 patients were treated with an OPSSC at our Department. Out of these, 126 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. After PSM, 84 patients with HPV-OPSCC and 21 HPV-HNCUP remained in the study for further comparison. Results: The OS was 63.5% (95% CI 39.4–87.6) for HPV-HNCUP and 88.9% (95% CI 90.4–100.0) for HPV-OPSCC patients and therefore, significantly lower for the first mentioned (p = 0.013). The DSS was also significantly impaired for HPV-HNCUP (71.0%, 95% CI 46.3–95.7), in comparison with HPV-OPSCC patients (95.5%, 95% CI 90.4–100.0; p = 0.002). The PFS for HPV-HNCUP patients was lower (75.6%, 95% CI 54.0–97.2) yet not significantly different to HPV-OPSCC (90.4%, 95% CI 83.5–97.3; p = 0.067). Conclusions: The results presented demonstrate a significant reduced OS and DSS for HPV-HNCUP patients. Accordingly, in our study HPV-HNCUP and HPV-OPSCC are two different entities with a different oncological outcome.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Cancer of unknown primary; Head and neck cancer; HPV-HNCUP; HPV-OPSCC; Neck dissection; Oropharyngeal cancer

A complex fracture of the hyoid bone and the larynx after a bicycle accident – Case report and review of literature - Sievert, Matti; Eisenhut, Felix; Iro, Heinrich; Traxdorf, Maximilian; Müller, Susanna; Taha, Lava (International Journal of Surgery Case Reports, 2021)
Introduction and importance: Reports about laryngeal trauma and fractures of the hyoid bone are rare in the literature. Most cases are forensic cases and the results of postmortem analysis. Traumatic larynx and hyoid bone fractures represent a rare but important differential diagnosis of the common symptom hoarseness. Case presentation: A 60-year-old female patient presented with unclear dysphonia and globus sensation following intubation for a surgical treatment for a lower leg fracture after a bicycle accident two months ago. Endoscopy and the computed tomography (CT) of the neck revealed a fixed and immobile fractured piece of the larynx, a hyoid bone fracture and a pseudarthrosis between the greater horn of the hyoid bone and the upper edge of the thyroid cartilage. The hyoid bone fracture led to a distortion of the supraglottis. After surgical removal of the fractured part of the hyoid bone and the pseudarthrosis separation, the supraglottis appeared symmetrical again. Four weeks after surgery the patient was symptom-free. Clinical discussion: Though combined hyoid bone and larynx fractures after traumatic injuries are rare, they represent an important differential diagnosis in trauma patients with dysphagia or dysphonia. The clinical symptoms can vary and occur immediately or within a latent period taking weeks or months until the proper diagnosis. Depending on the symptoms, surgical management can be effective. Conclusion: An isolated partial resection of the hyoid bone with separation of the pseudarthrosis is a reasonable therapeutic option and can lead to completely resolving symptom. Preoperatively, a CT provides further valuable information.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Case report; Computed tomography; Dysphagia; Dysphonia; Hyoid bone fracture; Laryngeal trauma

Advance directives in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, Magdalena; Rupp, Robin; Allner, Clarissa; Mantsopoulos, Konstantinos; Ostgathe, Christoph; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (BMC Palliative Care, 2022)
Background: Advance Care Planning including living wills and durable powers of attorney for healthcare is a highly relevant topic aiming to increase patient autonomy and reduce medical overtreatment. Data from patients with head and neck cancer (HNC) are not currently available. The main objective of this study was to survey the frequency of advance directives (AD) in patients with head and neck cancer. Methods: In this single center cross-sectional study, we evaluated patients during their regular follow-up consultations at Germany’s largest tertiary referral center for head and neck cancer, regarding the frequency, characteristics, and influencing factors for the creation of advance directives using a questionnaire tailored to our cohort. The advance directives included living wills, durable powers of attorney for healthcare, and combined directives. Results: Four hundred and forty-six patients were surveyed from 07/01/2019 to 12/31/2019 (response rate = 68.9%). The mean age was 62.4 years (SD 11.9), 26.9% were women (n = 120). 46.4% of patients (n = 207) reported having authored at least one advance directive. These documents included 16 durable powers of attorney for healthcare (3.6%), 75 living wills (16.8%), and 116 combined directives (26.0%). In multivariate regression analysis, older age (OR ≤ 0.396, 95% CI 0.181–0.868; p = 0.021), regular medication (OR = 1.896, 95% CI 1.029–3.494; p = 0.040), and the marital status (“married”: OR = 2.574, 95% CI 1.142–5.802; p = 0.023; and “permanent partnership”: OR = 6.900, 95% CI 1.312–36.295; p = 0.023) emerged as significant factors increasing the likelihood of having an advance directive. In contrast, the stage of disease, the therapeutic regimen, the ECOG status, and the time from initial diagnosis did not correlate with the presence of any type of advance directive. Ninety-one patients (44%) with advance directives created their documents before the initial diagnoses of head and neck cancer. Most patients who decide to draw up an advance directive make the decision themselves or are motivated to do so by their immediate environment. Only 7% of patients (n = 16) actively made a conscious decision not create an advance directive. Conclusion: Less than half of head and neck cancer patients had created an advance directive, and very few patients have made a conscious decision not to do so. Older and comorbid patients who were married or in a permanent partnership had a higher likelihood of having an appropriate document. Advance directives are an essential component in enhancing patient autonomy and allow patients to be treated according to their wishes even when they are unable to consent. Therefore, maximum efforts are advocated to increase the prevalence of advance directives, especially in head and neck cancer patients, whose disease often takes a crisis-like course.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Advance care planning; Advance directive; Head and neck Cancer; Living will; Patient autonomy; Power of attorney for healthcare

Age-Related Decline of Speech Perception - Hoppe, Ulrich; Hocke, Thomas; Iro, Heinrich (Frontiers in Aging Neuroscience, 2022)
Hearing loss is one of the most common disorders worldwide. It affects communicative abilities in all age groups. However, it is well known that elderly people suffer more frequently from hearing loss. Two different model approaches were employed: A generalised linear model and a random forest regression model were used to quantify the relationship between pure-tone hearing loss, age, and speech perception. Both models were applied to a large clinical data set of 19,801 ears, covering all degrees of hearing loss. They allow the estimation of age-related decline in speech recognition for different types of audiograms. Our results show that speech scores depend on the specific type of hearing loss and life decade. We found age effects for all degrees of hearing loss. A deterioration in speech recognition of up to 25 percentage points across the whole life span was observed for constant pure-tone thresholds. The largest decrease was 10 percentage points per life decade. This age-related decline in speech recognition cannot be explained by elevated hearing thresholds as measured by pure-tone audiometry.
CRIS-Team Scopus Importer:2022-07-22
Keywords: age-related hearing loss (ARHL); hearing loss; machine learning; maximum word recognition; random forest regression; speech audiometry; speech perception

Agranulozytose nach Metamizol-Einnahme – ein unterschätztes Risiko? - Schinz, Katharina; Wüst, Wolfgang; Iro, Heinrich; Waldfahrer, Frank (Laryngo-Rhino-Otologie, 2020)
OBJECTIVE: Metamizole was the second most common drug prescribed in Germany in 2018 despite the known risk of agranulocytosis and the strict indication. According to Stammschulte et al. up to 25 % of all prescriptions are off-label use. Although mandatory according to the prescribing information of metamizole, regular blood cell counts are not performed in up to 50 % of the patients with long-term use of this drug. MATERIAL AND METHODS: Retrospective analysis of eight cases metamizole-induced agranulocytosis over a period of five years (2016-2020) in the university ENT department in Erlangen. Five patients were men and three women. Mean age of diagnosis was 52,4 years (± 25,6). RESULTS: Agranulocytosis after use of metamizole is a serious adverse drug reaction that may affect patients of all ages. Frequently, only distinct clinical symptoms such as temperature of unknown origin, dysphagia and tonsillitis in combination with abscesses in the head and neck area result in the detection of a metamizole-induced agranulocytosis. An agranulocytosis provokes partially radical surgery and/ or intensive-care measures and could lead to sepsis with organ failure or even to death. CONCLUSIONS: These patient cases show that agranulocytosis is a dangerous or even deadly adverse drug reaction after use of metamizole. Although the risk of agranulocytosis appears to increase with duration of use, we would recommend patient education as well as documentation of even a single administration of metamizole. This may facilitate early diagnosis of metamizole-induced agranulocytosis and thus prevent the onset of severe complications with possible lethal outcome.
CRIS-Team Scopus Importer:2020-07-10

Analysis of Process Costing for the Use of Navigation Systems in Functional Endoscopic Sinus Surgery - Schwan, Franziska Eva; Traxdorf, Maximilian; Seebauer, Caroline Theresa; Sekita, Alexander; Habekost, Cornelia; Iro, Heinrich; Bohr, Christopher (Applied Sciences, 2021)
Featured Application This paper and its findings are important for any clinic that is thinking about setting up a navigation system for its ENT department, concerning the costs, efficiency in the operating room, and applicability for training purposes. (1) Background: The use of navigation systems is rarely necessary for routine sinus surgery. They may prove to be advantageous for difficult operations, for example, in finding structures that are difficult to reach, in the treatment of cancers, or in revisional surgery. Navigation systems are also said to have positive effects on the self-confidence of surgeons in stressful situations and in the training of doctors. (2) Methods: This retrospective study included patients who underwent surgical treatment for chronic sinusitis from 2012 to 2016 at the ENT clinic of the University Hospital, Erlangen. Two groups were formed; one includes patients without navigated sinus surgery, the other includes those with navigation. The incision-suture times of both groups and cost analysis are compared. An appropriate cost estimate for sinus surgery is determined. (3) Results: From the available results, no economically efficient navigation systems in sinus surgery at the ENT clinic can be shown. The main reason is that lengthening the operating time leads to higher costs. (4) Conclusions: Although the use of a navigation system for endonasal sinus surgery cannot be economically justified, it is an important tool, especially in cases with complex anatomical conditions, and the system is essential for training purposes.
CRIS-Team WoS Importer:2021-10-08

Analysis of surgical treatment strategy and outcome factors in persistent tracheoesophageal fistula: a critical analysis of own cases and review of the literature - Koch, Matthias; de Vasconcelos Craveiro, Antonio; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Gostian, Antoniu-Oreste (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: Surgical closure of persistent tracheoesophageal fistulas (TEFs) is complex. Most patients present with multiple risk factors, which may negatively impact the outcome and influence the treatment strategies. PATIENTS AND METHODS: This retrospective study included 22 patients presenting with persistent TEFs. Preoperative RT, comorbidities, tissue conditions of the TEFs and neck skin, and surgical techniques were evaluated regarding a possible impact on success rates and outcome. RESULTS: 21 patients were operated, 95.45% with final success. However, in 52.39% repeated surgery was needed. Final closure of TEFs was achieved in 91.47% only after more invasive surgery was performed. The surgical technique applied had the most significant impact on success rates and outcome compared to all other risk factors analyzed. Our own data and that of the literature point out that the surgical strategy should be adapted to the patients' individual risk factors. CONCLUSIONS: According to the literature, surgical closure of persistent TEFss is demanding. Our data suggest that, considering that the majority of patients with persistent TEFs exhibit multiple risk factors, early performance of more invasive surgery seems associated with a better outcome.
CRIS-Team WoS Importer:2022-02-04

A novel nasopharyngeal stent for the treatment of obstructive sleep apnea: a case series of nasopharyngeal stenting versus continuous positive airway pressure - Traxdorf, Maximilian; Hartl, Michael; Angerer, Florian; Bohr, Christopher; Grundtner, Philipp; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2016)
The objective of the study was to investigate the first-night treatment success of a nasopharyngeal stent compared to standard nCPAP-titration. This is a case series and a single-center study. Eight participants (n = 8) were selected with untreated obstructive sleep apnea with a prestudy AHI >=10. A newly developed nasopharyngeal stent was tested individually versus standard nCPAP-titration. Cardiorespiratory polysomnography was performed on two consecutive nights (random order: stent, nCPAP). The AHI, the number of obstructive apneas and hypopneas, the mean oxygen saturation, and the minimum oxygen saturation were compared before and after using the nasopharyngeal stent or standard nCPAP. The AHI value before treatment (AHIpre) was 31.1 ± 12.0 (mean ± standard deviation). After inserting the AlaxoStent, the mean AHIstent was 19 ± 12.0 compared to mean AHInCPAP 8.2 ± 11.9 with standard nCPAP-titration. Both nasopharyngeal stenting and nCPAP-titration could reduce the mean number of obstructive apneas by >94 %. Compared to responder rates of classic surgical interventions like uvulopalatopharyngoplasty or multi-level surgery, the nasopharyngeal stent seems to give a comparable responder rate of 50 %. There were no complications associated with the use of the stent and it was well tolerated by all subjects. Nasopharyngeal stenting widens the range of non-invasive mechanical treatment and seems to be an effective mechanical therapeutic alternative to surgery in nCPAP non-compliant patients with OSA. Careful selection of the patient population is a prerequisite of treatment and therefore it should be reserved for individual cases only.
EVALuna2:20017

Applicability of shear wave elastography of the major salivary glands: values in healthy patients and effects of gender, smoking and pre-compression - Mantsopoulos, Konstantinos; Klintworth, Nils; Iro, Heinrich; Bozzatoy, Alessandro (Ultrasound in Medicine and Biology, 2015)
Our aim in this study was to determine normal shear wave elastography (SWE) values for the parenchyma of the major salivary glands and to evaluate the influences of gender, smoking, side and type of gland and varying amounts of ultrasound probe pressure on SWE values. Twenty-five consecutive healthy patients were examined with ultrasound. SWE velocities were measured with acoustic radiation force imaging in the hilum and central region of both glands with "normal" and very low pressure. Mean SWE velocities were 1.854 m/s for the parotid gland and 1.932 m/s for the submandibular gland. No statistically significant differences were detected between males and females, smokers and non-smokers, parotid and submandibular gland and left and right sides. Greater pre-compression with the ultrasound probe resulted in a statistically significant increase in the SWE values of both salivary glands (p < 0.000). The degree of pre-compression by the ultrasound transducer should be standardized, so that the reliability and reproducibility of this innovative method can be improved.
EVALuna2:19987

Association between lateral wall electrode array insertion parameters and audiological outcomes in bilateral cochlear implantation - Thimsen, Vivian; Mantsopoulos, Konstantinos; Liebscher, Tim; Taha, Lava; Eisenhut, Felix; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim (European Archives of Oto-Rhino-Laryngology, 2022)
Purpose The aims of this study were to compare speech recognition at different postoperative times for both ears in bilaterally implanted patients and to assess the influence of the time of deafness, frequency-to-place mismatch, angular insertion depth (AID) and angular separation between neighbouring electrode contacts on audiometric outcomes. Methods This study was performed at an academic tertiary referral centre. A total of 19 adult patients (6 men, 13 women), who received sequential bilateral implantation with lateral wall electrode arrays, were analysed in retrospective. Statistical analysis was performed using two-sided t test, Wilcoxon test, median test, and Spearman's correlation. Results Postlingually deafened patients (deafness after the age of 10) had a significantly better speech perception (WRS65[CI]) than the perilingually deafened subjects (deafness at the age of 1-10 years) (p < 0.001). Comparison of cochlear duct length between peri- and postlingually deafened subjects showed a slightly significantly smaller cochleae in perilingual patients (p = 0.045). No association between frequency-to-place mismatch as well as angular separation and speech perception could be detected. There was even no significant difference between the both ears in the intraindividual comparison, even if insertion parameters differed. Conclusion The exact electrode position seems to have less influence on the speech comprehension of CI patients than already established parameters as preoperative speech recognition or duration of deafness.
CRIS-Team WoS Importer:2022-12-16

Auswirkungen der SARS-CoV‑2-Pandemie auf die universitäre Hals-Nasen-Ohren-Heilkunde im Bereich der Forschung, Lehre und Weiterbildung - Stöver, T.; Dazert, S.; Plontke, S. K.; Kramer, S.; Ambrosch, P.; Arens, C.; Betz, C.; Beutner, D.; Bohr, C.; Bruchhage, K. L.; Canis, M.; Dietz, A.; et al. (HNO, 2021)
Background: From spring 2020, SARS-CoV‑2 began to spread worldwide, with what is now known as the first wave of the pandemic, starting in March 2020. This resulted in restructuring and shift of resources at many hospitals. The aim of our work was to detect the effects of the pandemic on the german Oto-Rhino-Laryngology (ORL) university hospitals in terms of research, student teaching and further specialist training. Material and methods: The chairmen of the 39 ORL university hospitals in Germany were asked about the effects of the pandemic on research, student teaching and ORL specialist training (residency) in the period from March to April 2020 using a structured online survey. Results: All 39 chairmen took part in the survey. Of these, 74.4% (29/39) stated that their research activities had deteriorated as a result of the pandemic. In 61.5% (24/39) pandemic-related research issues were addressed. All hospitals reported a restriction for in-house teaching and 97.5% (38/39) introduced new digital teaching methods. During the observation period, 74.4% of the chairmen did not see ORL specialist training (residency)at risk. Conclusion: Our results provide an insight into the heterogeneous effects of the pandemic. The fast processing of pandemic-related research topics and the introduction of innovative digital concepts for student teaching impressively demonstrates the great innovative potential and the ability of the ORL university hospitals to react quickly in order to maintain their tasks in research, student teaching and ORL specialist training in the best possible way even during the pandemic.
CRIS-Team Scopus Importer:2021-02-05
Keywords: COVID-19; ORL; Otorhinolaryngology; Research; Residency; SARS-CoV‑2 pandemic; Specialist training; Teaching; University hospitals

Auswirkungen der SARS-CoV-2-Pandemie auf die universitäre Hals-Nasen-Ohrenheilkunde im Bereich der Krankenversorgung - Stöver, T.; Dazert, S.; Hoffmann, T. K.; Plontke, S. K.; Ambrosch, P.; Arens, C.; Betz, C.; Beutner, D.; Bohr, C.; Bruchhage, K. L.; Canis, M.; Dietz, A.; et al. (Laryngo-Rhino-Otologie, 2020)
Introduction Since December 2019, the SARS-CoV-2 virus has been rapidly spreading worldwide. In Germany, an exponential increase in the number of infections was registered at the beginning of March 2020 and led to a call of the Ministry of Health to create more capacity for intensive medical treatment in hospitals. The aim of the present study was to determine the effects of the SARS-CoV-2 pandemic on Oto-Rhino-Laryngology (ORL) university hospitals regarding patient care. Materials and methods An online survey was sent out to all chairmen of the 39 ORL university hospitals in Germany. The answers to the questions referred to the defined period from March 15 thto April 15 th2020 and were carried out using the online survey tool SurveyMonkey. 87 questions focused on general information, health care, and structural effects in the respective institution. Results All chairmen of the 39 university hospitals in Germany participated in the survey. The collected data prove the considerable impact on organizational, structural and medical aspects of patient care. For example, the surveyed clinics reported a decrease in outpatient cases by 73.8% to 26.2±14.2% and in surgical treatments by 65.9% to 34.1±13.9%. In contrast, emergency treatment remained unchanged or even increased in 80% of the facilities and surgical treatment of emergency patients remained unchanged or even increased in more than 90%. Emergency outpatient and surgical treatment of patients was provided throughout the pandemic in all facilities. In total, about 35000 outpatients and about 12000 surgical cases were postponed. As a result of the acute structural changes, the potential danger of falling below current treatment standards was seen in individual areas of patient care. Discussion The assessment of the impact of the SARS-CoV-2 pandemic is heterogeneous. The majority of the chairmen are critically aware of the risk of falling below current medical treatment standards or guidelines. In the phase of an exponential increase in the number of infections, significant changes in treatment processes had to be accepted for understandable reasons. However, with the currently significantly reduced number of infections, falling below treatment standards and guidelines should not be allowed to remain constant and tolerated. Summary This study shows a differentiated picture with regard to the effects of the SARS-CoV-2 pandemic on outpatient, inpatient and operative patient care at the ORL university hospitals in Germany and illustrates the importance of these institutions for ensuring patient care during this critical phase.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Covid-19; Oto-Rhino-Laryngology (ORL); patient care; restructuring; SARS-CoV-2 pandemic; university hospitals

Behandlungsstrategie beim radiojodrefraktären differenzierten Schilddrüsenkarzinom - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Pavel, Marianne Ellen; Kuwert, Torsten; Meidenbauer, Norbert; Fietkau, Rainer; Sievert, Matti; Iro, Heinrich (TumorDiagnostik & Therapie, 2021)
Traditionally, the multimodal therapy concept for differentiated thyroid carcinomas consists of thyroidectomy with neck dissection (for cN + neck) and adjuvant radioiodine ablation with subsequent risk-adapted TSH suppression. The extent of radioiodine uptake in metastatic thyroid carcinomas plays a significant role is significant in terms of prognosis. Radioiodine refractory lesions are characterized by the lack of radioiodine uptake in combination with the lack of decrease in the tumor marker thyroglobulin as well as signs of progression on imaging. Due to the mostly indolent course over a long period of time, a wait-and-see strategy in combination with local management of distant metastase symptom relief appears to be primarily sufficient. By evidence for change in tumor dynamics, the need for a multi-tyrosine kinase inhibitor (sorafenib, lenvatinib)-based systemic therapy should be thoroughly evaluated. These substances are mostly associated with an unfavorable side-effect profile (diarrhea, rash, arterial hypertension, local wound healing disorders), which leads to a non-negligible rate of treatment-associated morbidity and a high number of treatment interruptions. For this reason, two selective RET inhibitors (selpercatinib, pralsetinib) for differentiated thyroid carcinomas were approved by the FDA in 2020. A new perspective for the future would be the variable re-differentiation strategies, which aim to increase the sensitivity of tumor cells to radioiodine.
CRIS-Team Scopus Importer:2024-12-16
Keywords: differentiated thyroid cancer; metastasized thyroid cancer; radioiodine refractory thyroid cancer; RET inhibitor; tyrosine kinase inhibitor

Calcification in Salivary Gland Cancer Mimicking Sialolithiasis-A Diagnostic Pitfall on Imaging: Report of Two Cases and Brief Review of the Literature - Thimsen, Vivian; Fauck, Vanessa; Wiesmüller, Marco; Agaimy, Abbas; Schapher, Mirco; Iro, Heinrich; Koch, Michael; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Objectives: Sialolithiasis is the most common cause of calcifications detected with ultrasound in patients with chronic inflammatory symptoms and swellings of the salivary glands. Other differential diagnoses of calcifications are extremely rare and mostly benign. Methods: Case report and literature review. Results: Two rare cases of malignant parotid gland tumors with calcifications in a localization typical for sialolithiasis, which were mistaken for salivary calculi based on image findings, are presented. Conclusions: This report intends to highlight the pitfalls in the imaging of parotid gland diseases. Even if malignant tumors of the parotid gland with calcifications are extremely rare, in ambiguous cases, differential diagnoses should be considered carefully. A high suspicion index of the need for further diagnostics in cases with calcifications is practical and could include missing periprandial symptoms, no obstruction signs in the proximal duct, and missing evidence of sialolithiasis in sialendoscopy.
CRIS-Team WoS Importer:2022-07-08

Cartilaginous bending spring for preventing tympanic membrane graft medialisation in anterior or subtotal tympanic membrane perforations—how I do it - Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim (European Archives of Oto-Rhino-Laryngology, 2021)
Background: The reconstruction of anterior or subtotal tympanic membrane perforations is critical due to the risk of anterior graft medialisation and retraction or recurrent perforation. Method: After reconstruction of the tympanic membrane by means of grafting, a rectangular cartilage strut (length 6 mm, breadth 2 mm, thickness 0.1 mm) is prepared using a cartilage knife and scalpel. This strut graft is placed between the cartilage graft and the promontory in the anterior inferior part of the middle ear cavity. Conclusion: Our experience shows that using a U-shaped cartilage strut to sustain the tympanic reconstruction effectively prevents the medialisation of the graft and recurrent perforations.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Cartilage; Graft medialisation; Tympanic membrane; Tympanic perforation

Cartilaginous bending spring tympanoplasty: a temporal bone study and first clinical results - Rupp, Robin; Schelhorn, Tony; Kniesburges, Stefan; Allner, Moritz; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Gostian, Antoniu-Oreste; Balk, Matthias (European Archives of Oto-Rhino-Laryngology, 2022)
Objective: Anchoring grafts for tympanic membrane (TM) reconstruction in anterior and subtotal TM defects is essential to prevent medialisation and can be facilitated by cartilaginous bending spring tympanoplasty (CBST). The purpose of this study was to analyse the impact of spring cartilages on middle ear transfer functions and patient hearing levels. Methods: In six fresh-frozen human temporal bones a cartilage graft (measuring 6 × 2 mm with a thickness of 0.1–0.2 mm) was formed into a ‘U’-shaped bending spring, to be placed between the medial tympanic wall and the tympanic underlay grafts. The stapes velocity for excitation by exponential sweeps from 400 to 10,000 Hz was measured with a laser Doppler vibrometer. The resulting middle ear transfer functions were compared with the reconstructed middle ear. For clinical evaluation, 23 ears in 21 patients with chronic otitis media and an intact ossicular chain were operated using CBST. At each follow-up visit, the patients underwent pure-tone audiometry and the Freiburg monosyllabic speech test at a presentation level of 65 dB SPL for the word recognition score (WRS). Results: The measured stapes velocities at one-third octave midband frequencies averaged 3.56 × 10–2 ± 9.46 × 10–3 (mm/s/Pa) compared to 3.06 × 10–2 ± 6.86 × 10–3 (mm/s/Pa) with the bending and underlay cartilage in place (p = 0.319; r = 0.32). The bending spring tympanoplasty reduced the transfer function by 1.41 ± 0.98 dB on average. In the clinical part of the study, the graft success rate was 96% (22 out of 23 patients) after a mean follow-up of 5.8 ± 2.4 months (min. 3.5 months, max. 12.0 months). The air–bone gap improved significantly by 6.2 dB (± 6.6 dB; p < 0.001; r = 0.69), as well as the WRS from 61.8 ± 33.3% preoperatively to 80.0 ± 20.9% postoperatively (p = 0.031; r = 0.35). Conclusion: Experimental data as well as initial clinical results suggest that CBST is an effective method for reconstructing anterior or subtotal defects of the tympanic membrane with satisfactory audiologic results and graft success rates comparable to previously described methods. It can, therefore, be added to the arsenal of tympanoplasty techniques for anterior and subtotal TM perforations.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Anterior tympanic membrane defect; Chronic otitis media; Laser Doppler vibrometry; Middle ear transfer function; Tympanoplasty

Case-tailored indicated extracapsular dissection versus “one-size-fits-all” nerve dissection: Has the bet been won? - Mantsopoulos, Konstantinos; Gehrking, Mika; Thimsen, Vivian; Sievert, Matti; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2024)
Objective: The aim of the study was to trace the development of surgical therapy in a large cohort, examine its changes at one single institution that has been specializing in salivary gland pathologies over the last 22 years, and to determine the extent to which a possible shift in the surgical therapy of parotid benign tumors towards less radical methods was correlated with a change in the incidence of facial palsy and Frey's syndrome. Study design: Retrospective clinical study. Methods: A retrospective evaluation of the records of all patients treated for benign parotid tumors at a tertiary referral center between 2000 and 2022 was carried out. Surgical methods were classified into four groups: extracapsular dissection, partial superficial parotidectomy, superficial parotidectomy and complete parotidectomy. Results: A total of 4037 patients were included in the study. Our analysis demonstrated an increase in the total number of parotidectomies for benign lesions from 71 (2000) to 298 (2022), mostly due to the increase in extracapsular dissections (from 9 to 212). The increased performance of less radical surgery was associated with a significantly decreased incidence of perioperative complications. Conclusions: Our study showed that the increased performance of less radical surgery was associated with better functional outcomes over the years.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Extracapsular dissection; Facial nerve; Fistula; Frey's syndrome; Paresis; Parotid gland; Parotidectomy

Cellular density and variability in laryngeal and pharyngeal squamous cell carcinoma using confocal laser endomicroscopy - Sievert, Matti; Aubreville, M.; Eckstein, Markus; Mantsopoulos, Konstantinos; Koch, Matthias; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Iro, Heinrich; Goncalves, M. (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: Confocal laser endomicroscopy (CLE) allows the visualization of epithelium in a thousand-fold magnification. This study analyzes the architectural differences at the cellular level of the mucosa and squamous cell carcinoma (SCC). PATIENTS AND METHODS: A total of 60 CLE sequences recorded in 5 patients with SCC undergoing laryngectomy between October 2020 and February 2021 were analyzed. The corresponding histologic sample derived from H&E staining was assigned to each sequence, capturing CLE images of the tumor and healthy mucosa. In addition, the cellular structure analysis was performed to diagnose SCC by measuring the total number of cells and cell size in 60 sequences in a fixed field of view (FOV) with 240 μm in diameter (45,239 μm2). RESULTS: Out of 3,600 images, 1,620 (45%) showed benign mucosa and 1,980 (55%) SCC. The automated analysis yielded a difference in cell size, with healthy epithelial cells being 171.9±82.0 μm2 smaller than SCC cells, which were 246.3±171.9 μm2 and showed greater variability in size (p=0.037). In addition, due to the probe’s fixed FOV, there was a difference in cell count with a total of 188.7±38.3 and 124.8±38.6 cells in images of normal epithelium and SCC (p<0.001), respectively. Regarding cell density as a criterion for the differentiation of benign/malign, using a cut-off value of 145.5 cells/FOV, we obtained sensitivity and specificity of 88.0% and 71.9%, respectively. CONCLUSIONS: SCC reveals marked differences at a cellular level compared to the healthy epithelium. Our results further support the importance of this feature for identifying SCC during CLE imaging.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Classification; Confocal laser endomicroscopy; Head and neck squamous cell carcinoma; Larynx; Optical biopsy; Pharynx

Chronic hearing loss turns out being a calcified chondroid mesenchymal neoplasm with FN1::FGFR2 fusion - Bauerschmitz, Leonard; Agaimy, Abbas; Eckstein, Markus; Balk, Matthias; Iro, Heinrich; Schleder, Stephan; Schlaffer, Sven-Martin; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2024)
A 53 year old female presented with a six-year history of right-sided slow deterioration in hearing and a feeling of pressure in the right ear. The patient had not experienced any pain but reported some paresthesia of the right half of the tongue, whereas no further other cranial nerve deficits were evident. The otoscopy was unremarkable as well as the rest of the clinical ENT examination except for a slight asymptomatic swelling of the right cheek. Imaging findings showed an expansive tumor infiltrating and destroying the right lateral skull base. The tumor was partially composed of cystic/regressive lesions with high contrast media uptake. The tumor had high-signal intensity with water-sensitive sequences (T2w) and was hypointense on T1w images. We performed a tumor resection via a transparotideal-infratemporal approach. Histologically, the tumor was composed of granular variably calcified chondroid matrix with extensive regressive changes and granulation-like tissue reaction associated with calcinosis and crystal deposition. Molecular analysis of the tumor via the TruSight- RNA-Fusion panel detected a fusion involving FN1::FGFR2, consistent with “calcified chondroid mesenchymal neoplasm” (CCMN), a rare tumor entity recently defined by Liu et al 2021. In regular follow-up care no residual tumor has been detected in imaging studies (MRI and CT) within 2 years and 4 months. The biology and consequently the radio sensitivity cannot be defined precisely since long term results are missing due to the first description of this entity in 2021. As a consequence, surgical resection is recommended as the treatment of choice. Thorough clinical and radiological follow-up is mandatory as local recurrences are to be expected due to the infiltrative behavior. In case of a loco regional recurrence the fusion with FGFR2 may represent a therapeutic option for a targeted therapy on molecular level.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Calcified chondroid mesenchymal neoplasm; Calcifying aponeurotic fibroma; CCMN; Chondrobastoma; Chondroma; Chondrosarcoma; Chordoma; FGF23; FGFR1; FGFR2; FN1; Ossifying fibromyxoid tumor; Phosphaturic mesenchymal tumors; PMT; Skull base tumor; TEK; Temporomandibular Joint; Tenosynovial giant cell tumor; TruSight-RNA-Fusion panel

Classification of three prognostically different groups of head and neck cancer patients based on their metabolic response to induction chemotherapy (IC-1) - Semrau, Sabine; Schmidt, Daniela; Hecht, Markus; Haderlein, Marlen; Kitzsteiner, Christian; Müller, Susanna; Traxdorf, Maximilian; Agaimy, Abbas; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Oral Oncology, 2020)
Objectives: There exist no uniform decision criteria for conservative organ preservation treatments in head and neck cancer patients. Even with 18F-FDG-PET/CT after induction chemotherapy patient selection is challenging. This study correlated metabolic tumor response with treatment types and recurrence patterns. Materials and methods: Decrease in SUVmax in 18F-FDG-PET/CT was measured 21–28 days after IC-1 in 102 patients and correlated to cancer-specific endpoints. Results: Residual SUVmax (resSUVmax) values were uniformly distributed across five cut-off levels (0–0.2 vs. >0.2–0.4 vs. >0.4–0.6 vs. >0.6–0.8 vs. >0.8) containing 20%, 25% 25%, 15% and 15% of patients. Patients were stratified into three response categories according to residual SUVmax (Group A: 0–0.4 = high response Group B: >0.4–0.8 = moderate response, Group C > 0.8 = non-response), 5-year local control rates were 90.5% (Group A) vs. 78.9% (Group B; univariate p = 0.07, multivariate: HR: 3.6, p = 0.03) vs. 49.4% (Group C vs. B; univariate p = 0.04, multivariate: HR 5.5, p < 0.01). After IC-1, Group A received chemoradiotherapy (CRT) only. Group B received surgery plus either (chemo)radiotherapy (B_S + RT/CRT) or chemoradiotherapy (B_CRT), yielding local control rates of 100% and 74.2% (p = 0.11). Group C received surgery plus CRT or CRT alone; both achieved equally poor local control (p = 0.71). Group C had significantly worse distant metastasis-free survival and overall survival than Groups A and B (p < 0.05). Conclusion: Metabolic response after IC-1 differentiates HNC patients into three subgroups predicting local tumor control. Non-response was associated with a poor outcome.
CRIS-Team Scopus Importer:2019-12-03
Keywords: 18F-FDG PET/CT; Chemoradiation; Chemoselection; Head and neck cancer; Hypopharynx; Induction chemotherapy; Larynx; Metabolic response; Resection

Clinical characterization of respiratory large droplet production during common airway procedures using high-speed imaging - Müller, Sarina Katrin; Veltrup, Reinhard; Jakubaß, Bernhard; Kniesburges, Stefan; Hübner, Matthias; Kempfle, J. S.; Dittrich, Sven; Dittrich, Sven; Iro, Heinrich; Döllinger, Michael (Scientific Reports, 2021)
During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding large droplet dissemination during airway management procedures in real life settings. 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed. Droplets were detected in 8/12 procedures. The droplet trajectories could be divided into two distinctive patterns (type 1/2). Type 1 represented a ballistic trajectory with higher speed large droplets whereas type 2 represented a random trajectory of slower particles that persisted longer in air. The use of tracheal cannula filters reduced the amount of droplets. Respiratory droplet patterns generated during airway management procedures follow two distinctive trajectories based on the influence of aerodynamic forces. Speaking and coughing produce more droplets than non-invasive ventilation therapy confirming these behaviors as exposure risks. Even large droplets may exhibit patterns resembling the fluid dynamics smaller airborne aerosols that follow the airflow convectively and may place the healthcare provider at risk.
CRIS-Team Scopus Importer:2021-06-04

Cochlear Implantation Following Explorative Tympanotomy in Patients With Sudden Sensorineural Hearing Loss: Surgical Features and Audiological Outcomes - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Sievert, Matti; Müller, Susanna; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Ent-Ear Nose & Throat Journal, 2021)
Objective: To investigate the anatomical status of the round window niche and hearing outcome of cochlear implantation (CI) after explorative tympanotomy (ExT) with sealing of the round window membrane in patients with sudden sensorineural hearing loss at a tertiary referral medical center. Methods: Between January 1, 2007, and July 30, 2020, 1602 patients underwent CI at our department. Out of these, all patients previously treated by ExT with sealing of the round window membrane because of unilateral sudden hearing loss were included in the study. A retrospective chart review was conducted concerning method of round window membrane sealing, intraoperative findings during CI, postoperative imaging, and hearing results. Results: Twenty one patients (9 females; 8 right ears; 54.3 years [± 12.9 years]) underwent ExT with sealing of the round window membrane with subsequent CI after 26.6 months (± 32.9 mo) on average. During CI, in 76% of cases (n = 16), the round window niche was blocked by connective tissue due to the previous intervention but could be removed completely in all cases. The connective tissue itself and its removal had no detrimental effects on the round window membrane. Postoperative computed tomography scan showed no electrode dislocation. Mean postoperative word recognition score after 3 months was 57.4% (± 17.2%) and improved significantly to 73.1% (± 16.4%, P =.005) after 2 years. Conclusion: Performing CI after preceding ExT, connective tissue has to be expected blocking the round window niche. Remaining tissue can be removed safely and does not alter the round window membrane allowing for a proper electrode insertion. Short- and long-term hearing results are satisfactory. Consequently, ExT with sealing of the round window membrane in patients with sudden sensorineural hearing loss does not impede subsequent CI that can still be performed safely.
CRIS-Team Scopus Importer:2021-05-21
Keywords: cochlear implant; explorative tympanotomy; round window membrane sealing; sudden sensorineural hearing loss

Cochlear Implantation in Candidates With Moderate-to-Severe Hearing Loss and Poor Speech Perception - Hoppe, Ulrich; Hocke, Thomas; Hast, Anne; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To determine the improvement in word recognition score (WRS65) after cochlear implant (CI) surgery in hearing aid (HA) users with preoperative hearing threshold ≤80 dB HL and inadequate speech recognition scores with HA. Secondarily, to identify predictive factors for WRS65 with a CI (WRS65[CI]) 6 months after surgery, derived from the standard German CI preoperative assessment. Study Design: Retrospective chart review. Methods: Retrospective review of all adult patients who received a Nucleus cochlear implant in the ear, nose, and throat department of the University Hospital of Erlangen between January 2010 and April 2019. The inclusion criteria were a preoperative hearing threshold ≤80 dB HL in the ear to receive the implantation, German as the native language, and at least 6 months postimplantation care at our center. Results: The inclusion criteria were met by 128 patients. All but two patients (98.4%) showed a significant improvement, WRS65(CI) versus WRS65 with an (HA) (WRS65[HA]), of at least 15 percentage points (pp). The median improvement was 55 pp with a median WRS65(CI) of 70%. Three preoperative audiometric measures, the maximum word recognition score, age at implantation, and WRS65(HA) were identified as predictive factors for WRS65(CI). For three-quarters of the CI recipients, the score was not poorer than 12 pp below the predicted WRS65(CI). Conclusions: For patients with a hearing loss ≤80 dB HL, cochlear implantation should be considered when speech perception with an HA is insufficient. The prediction model can support counseling in this patient group. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-06-09
Keywords: adult; Cochlear implant; hearing aid; hearing threshold; speech audiometry

Cochlear implants in the social courts - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: Since the indication for receiving a cochlear implant (CI) has widened (single-sided deafness [SSD], electric acoustic stimulation [EAS], bilateral CI, CI for long-term deafness), more and more patients come into consideration for such a treatment. Hence, disputes increasingly arise between patients and their insurance companies concerning the question of whether surgery and follow-up treatment have to be paid for by statutory health insurance. OBJECTIVE: This work provides an overview of judgments rendered by the German social courts. We investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIALS AND METHODS: We looked for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear," "Cochlea," "Implant," and "Implantat." Three verdicts were attained by directly contacting the court; another one was mentioned in an article. The reviewed judgements were issued between 2003 and 2017. RESULTS: A total of 12 judgments were found. The patients won in all but one of the main proceedings. The case that was lost concerned exceptional circumstances. One patient didn't get the desired interim measure, but won in the main proceedings. The proceedings took between 1 year and 8 months, and 9 years and 5 months. CONCLUSION: Despite the amount of time the patient has to invest, taking legal action is worthwhile. The proceedings at the social courts are generally exempt from charges. In most cases, the statutory health insurance is ordered to pay for a CI.
EVALuna2:33194

Comparative analysis of titanium clip prostheses for partial ossiculoplasty - Mantsopoulos, Konstantinos; Thimsen, Vivian; Taha, Lava; Eisenhut, Felix; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Objectives: The aim of our study was to perform a comparative analysis in our cases with titanium partial clip ossiculoplasty in terms of audiometric outcome and extrusion rates as well as to review the literature for relevant information on this surgical issue. Materials and methods: The records of all patients who had undergone primary partial ossiculoplasty with the implantation of a CliP® Partial Prosthesis Dresden Type (CPPDT, group A) or a CliP Partial FlexiBAL® (CPF, Group B, both Heinz Kurz GmbH, Dusslingen, Germany) between 2012 and 2020 were studied retrospectively. Results: 274 patients made up our study sample (148 men, 126 women, male to female ratio: 1.17). Their mean age at the time of first surgery was 39.6 years (range: 4–79 years). The mean preoperative air-bone gap (ABG) was 22.7dΒ ± 10.5 dB. Mean follow-up was approximately 4 months (1–12 months). The mean postoperative ABG was 15.7 ± 8.1 dB. In total, the postoperative ABG was significantly improved compared to preoperative values (P < 0.001). Surgical success, defined as an ABG ≤ 20 dB, was achieved in the majority of our study patients (210/274, 76.6%). Extrusion of the prosthesis was detected in 3/216 CPF and 5/58 CPPDT cases (p = 0.012). Comparison of both prosthesis groups revealed a significantly better audiological outcome for the patients with ossicular reconstruction using CPF. A significantly better audiological outcome was detected in the cases with a normal aeration of the middle ear. Discussion: Titanium clip partial ossiculoplasty is a reliable component of modern tympanoplasty, allowing a satisfying audiologic outcome. The higher adaptability of the CPF to the changing postoperative circumstances and the frequently defective aeration of the middle ear is reflected in the better audiologic outcome for this prosthesis.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Air-bone gap; Middle ear; Ossiculoplasty; Outcome; Partial prosthesis; PORP

Comparison of mucus and serum biomarker sampling in chronic rhinosinusitis with nasal polyps - Müller, Sarina Katrin; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Koch, Michael; Mantsopoulos, Konstantinos; Sievert, Matti; Grundtner, Philipp; Iro, Heinrich; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2023)
Objective: The objective of this study was to analyze advantages and disadvantages of mucus and serum for biomarker analysis. Methods: This study includes prospective study of 61 CRS with nasal polyps patients who were followed over 24 months and over nine time points after functional endoscopic sinus surgery. At each time points, the nasal polyp score (NPS) was assessed and mucus as well as serum was collected. Selected were measured in mucus and serum. Mean, standard deviation and variance, undetectable values, and the correlation of the biomarkers to the NPS over time and to early recurrences were calculated, and the effect of surgery on the biomarkers was assessed. Additionally, the diurnal rhythm of all biomarkers was measures in order to assure stable biomarker values during sampling times. Results: All biomarkers showed stable values during sampling times. Serum biomarker levels displayed higher percentages of undetectable values compared to mucus biomarkers. Mucus periostin (p < 0.001, r = 0.89), mucus IgE (p < 0.001, r = 0.51), serum periostin (p < 0.001, r = 0.53), mucus CST1 (p < 0.001, r = 0.27), and serum IgE (p < 0.01, r = −0.18) were the best marker and medium combinations to track the NPS over time and to predict recurrences. Mucus serpinF2 was negatively correlated and predicted early recurrences (p = 0.026, R2 = 0.015). Conclusions: Serum and mucus both represent viable mediums for “liquid biopsies.” The most promising biomarker/medium combinations over time to track disease severity were mucus periostin, mucus IgE, serum periostin, mucus CST1, and serum IgE. Mucus serpinF2 was the best biomarker to predict early recurrences.
CRIS-Team Scopus Importer:2023-12-01
Keywords: biomarker; chronic rhinosinusitis; eosinophilic rhinitis; nasal polyposis

Comparison of vestibular schwannoma visualization between 0.55 T and 1.5 T MRI - Wiesmüller, Marco; Kopp, Markus; Sievert, Matti; May, Matthias; Nagel, Armin Michael; Iro, Heinrich; Uder, Michael; Heiß, Rafael (European Journal of Radiology, 2023)
Objectives: Vestibular schwannoma (VS) is the most common mass of the internal auditory canal (IAC) and is responsible for unilateral sensorineural hearing loss. Magnetic resonance imaging (MRI) at 1.5 T and 3 T is the standard of care for the evaluation of VS, and the feasibility of using modern low-field MRI for imaging of the IAC has not yet been elucidated. Hence, the purpose of this prospective study was to assess image quality and diagnostic performance of a modern 0.55 T MRI. Materials and Methods: Fifty-six patients with known unilateral VS underwent routine MRI of the IAC at 1.5 T, followed immediately by 0.55 T MRI. Two radiologists independently evaluated the image quality, conspicuity of VS, diagnostic confidence, and image artifacts separately for isotropic T2-weighted SPACE images and for transversal and coronal T1-weighted fat-saturated contrast-enhanced images at 1.5 T and 0.55 T using 5-point Likert scales. In a second independent reading, both readers assessed lesion conspicuity and subjective diagnostic confidence in a direct comparison of 1.5 T and 0.55 T images. Results: Image quality of transversal T1-weighted images (p = 0.13 and p = 0.16 for Reader 1 and Reader 2, respectively) and T2-weighted SPACE images (p = 0.39 and p = 0.58) were rated equally at 1.5 T and 0.55 T by both readers, whereas image quality of coronal T1-weighted images was superior at 1.5 T (p = 0.009 and p = 0.001). Analysis of the conspicuity of VS, diagnostic confidence, and image artifacts of all sequences revealed no significant differences between 1.5 T and 0.55 T. In the direct comparison of 1.5 T with 0.55 T images, there were no significant differences in lesion conspicuity or diagnostic confidence for any sequence (p = 0.60–0.73). Conclusions: Modern low-field MRI at 0.55 T provided a sufficient diagnostic image quality and seems feasible for the evaluation of VS of the IAC.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 0.55T MRI; Acoustic neuroma; Image quality; Inner auditory canal; low-field MRI; Vestibular schwannoma

Completion surgery after extracapsular dissection of low-grade parotid gland malignant tumors - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2019)
Background: The aim of the study was to compare the oncological and functional outcome between extracapsular dissection and completion surgery on the one hand and sole extracapsular dissection on the other hand in small low-grade malignant parotid tumors. Methods: The records of all patients treated for T1-T2 low-grade malignant tumors of the parotid gland primarily by means of extracapsular dissection between 2006 and 2015 were studied retrospectively. Results: Forty patients with T1-T2 low-grade parotid malignancies were detected. Our study showed outstanding oncological outcomes in both patient groups, the facial nerve function being significantly better after sole extracapsular dissection in the direct postoperative phase, with no differences between the groups in the long term. Conclusions: Our study showed very encouraging preliminary results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance.
CRIS-Team Scopus Importer:2019-07-16
Keywords: extracapsular dissection; facial nerve; low-grade; malignant tumor; parotid gland

Complex midfacial defects: Is the extended Abbé flap the ideal solution to a tough problem? - Mantsopoulos, Konstantinos; Iro, Heinrich; Constantinidis, Jannis (Oral Oncology, 2020)
Objectives: The aim of this study was to investigate the role of the extended Abbé flap in the reconstruction of complex midfacial defects (upper lip, nasal base and medial cheek). We describe our personal experience with this method and present some interesting aspects from the relevant literature. Materials and methods: Between 2003 and 2017 we retrospectively evaluated the records of all patients with defects of the upper lip and nasal base after the resection of malignant tumors or traumata and reconstruction by means of the extended Abbé flap. We looked for information on the origin of the defect, the functional result, the aesthetic outcome and postoperative complications. The functional result of the reconstruction of the oral commissure was assessed with regard to postoperative subjective speech integrity, preservation of competence of the oral sphincter and lip sensation. The aesthetic outcome was evaluated with regard to limitations in facial expression and scar formation. Results: The study included 8 patients. Follow–up in the oncological cases was 85 months (range: 20–150 months). No tumor recurrences were detected. All patients achieved normal oral competence and mouth opening. No cases of blunting or microstomia were detected. Conclusion: Reconstruction of the upper lip and nasal base with the extended Abbé flap is associated with an outstanding functional outcome that is cosmetically very acceptable.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Extended Abbé flap; Microstomia; Nasal base; Perioral defect; Upper lip

Complications of tracheoesophageal shunts after laryngectomy - Scherl, C.; Kauffels, J.; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Koch, Matthias; Traxdorf, Maximilian; Iro, Heinrich (2018)
EVALuna2:35392

Confocal laser endomicroscopy of head and neck squamous cell carcinoma: a systematic review Konfokale Laser-Endomikroskopie des Kopf-Hals-Plattenepithelkarzinoms: eine systematische Übersicht - Sievert, Matti; Auberville, Marc; Oetter, Nicolai; Stelzle, Florian; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (Laryngo-Rhino-Otologie, 2021)
Objective: Confocal laser endomicroscopy (CLE), with a magnification of up to 1000 ×, offers the possibility to visualize intercellular spaces in vivo. CLE has already established itself in different disciplines. This article gives an overview of the current research on CLE in the diagnosis of the head and neck squamous cell carcinoma. Material and methods: Material and methods: Systematic bibliographic research in the following online databases: PubMed, MEDLINE, Thompson Reuters Web of Science, SPIE using the following keywords: confocal laser endomicroscopy, CLE, endomicroscopy, head and neck, larynx. Evaluation of the scientific relevance according to defined criteria. Results: All studies were analyzed concerning the clinical application, clinical findings, and computer-aided data processing. Conclusions: The recently published data suggest that CLE has a high potential to improve the diagnosis of malignant mucosal lesions in the upper aerodigestive tract.
CRIS-Team Scopus Importer:2021-01-22
Keywords: CLE; confocal laser endomicroscopy; head and neck malignancy; image analysis; laryngeal carcinoma

Considerations for Continuing Semielective and Emergency Otolaryngological Procedures During the COVID-19 Pandemic - Müller, Sarina Katrin; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Sievert, Matti; Koch, Michael; Hübner, Matthias; Iro, Heinrich (Ent-Ear Nose & Throat Journal, 2020)
Introduction: During the COVID-19 pandemic, worldwide over 600,000 human beings died due to the cause of the disease. In order to deescalate the transmission rate and to avoid crush loading the countries medical health systems social distancing, face masks, and lockdowns have been considered essential by the majority of governments. Whereas some countries have highly reduced or completely stopped otorhinolaryngological procedures, other countries have continued selected surgeries. The objective of this study was to analyze procedures and outcomes of continuing semielective and emergency surgeries during the COVID-19 pandemic. Methods: Retrospective analysis of n = 750 patients who received semi-elective or emergency surgery between March 26 and June 16, 2020, in the Otolaryngology Department of the Friedrich-Alexander-University of Erlangen-Nürnberg. All patients were screened for COVID symptoms and swabbed for SARS-CoV-2 prior to surgery. Results: Of the n = 750 patients, n = 699 patients received semielective surgery and n = 51 emergency surgery. For 27 patients, the swab result could not be awaited due to a life-threatening condition. In these cases, surgery was performed in full protective equipment. No patient was tested positive during or after the surgery (follow-up 45 to 127 days). No member of the medical personnel showed symptoms or was tested positive after contact with patients. Due to the continuation of surgeries, patients’ lives were saved and improvement of long-term quality-of-life and outcomes is anticipated. Conclusions: Continuing selected otorhinolaryngological surgeries is crucial for patients’ health, survival, and long-time quality of life, yet, the protection of the medical personnel has to be granted.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; false-negative; otorhinolaryngological procedures; patient’s health; SARS-CoV-2 test

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Defining a baseline identification of artifacts in confocal laser endomicroscopy in head and neck cancer imaging - Pan, Zhaoya; Breininger, Katharina; Aubreville, Marc; Stelzle, Florian; Maier, Andreas; Oetter, Nicolai; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel; Sievert, Matti (American Journal of Otolaryngology, 2023)
Purpose: Probe-based confocal laser endomicroscopy (pCLE) allows imaging of the laryngeal mucosa in a thousand-fold magnification. However, the existence of multiple nondiagnostic frames might hinder the performance of automated systems, especially in post-processing and analysis algorithms. This study aims to investigate the feasibility of building a baseline for the identification of diagnostic frames and to evaluate the influence of sequence information in this task. Materials and methods: We included eight patients with squamous cell carcinoma (SCC) and planned total laryngectomy between October 2020 and February 2021. One hundred frames were randomly selected out of 21,272 pCLE frames of the tumor and healthy mucosa during surgery. Three experts were asked to classify these frames into diagnostic and nondiagnostic ones with different subtypes under two settings, i.e., isolated frames or short video sequences. Inter-rater and intra-rater consistency were analyzed with Cohen's kappa coefficients. Results: Among all raters, regarding the classification of diagnostic frames, an average agreement of κ = 0.79 has been achieved. The overall consistency for the subtypes of nondiagnostic frames is κ = 0.75 and κ = 0.57, respectively. Conclusions: The high level of consistency regarding the identification of diagnostic frames shows the reliability of the classification results and builds the foundation for future automatic algorithms.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Defining intra-tumoral and systemic immune biomarkers for locally advanced head-and-neck cancer – detailed protocol of a prospective, observatory multicenter trial (ImmunBioKHT) and first results of the immunophenotyping of the patients’ peripheral blood - Donaubauer, Anna-Jasmina; Frey, Benjamin; Weber, Manuel; Allner, Moritz; Vogl, Christoph; Almajali, Omar; Kuczera, Lukas; Tamse, Henriette; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Zülch, Lilli; et al. (Frontiers in Oncology, 2024)
The approval and effectiveness of immune checkpoint inhibitors in head-and-neck squamous cell carcinoma (HNSCC) highlights the role of the immune system in this tumor entity. HNSCCs not only interacts with the immune system in the tumor tissue, but also induce systemic effects that may be additionally influenced by further factors such as the microbiome. Nonetheless, reliable immunological biomarkers that predict treatment response and outcome in HNSCC patients are lacking. The currently available biomarkers are mainly limited to analyses from tumor biopsies, while biomarkers from liquid biopsies, such as peripheral blood are not well-established. Thus, the here presented trial aims to identify interactions of intra-tumoral and systemic immune responses and to define prognostic immune signatures. Consequently, not only samples from the tumor tissue, but also from peripheral blood and the microbiome will be studied/are being evaluated and correlated with the clinical outcome. In this prospective, multi-center trial, 1000 HNSCC patients and 100 patients in the control cohort with non-tumor head-and-neck surgery will be enrolled. The local immune status from of the tumor and the microbiome will be sampled before treatment. In addition, the systemic immune status from peripheral blood will be analyzed before and after surgery and after the adjuvant and definitive radio-chemotherapy (RCT). Clinical baseline characteristics and outcome will additionally be collected. Data mining and modelling approaches will finally be applied to identify interactions of local and systemic immune parameters and to define prognostic immune signatures based on the evaluated immune markers. Approval from the institutional review board of the Friedrich-Alexander-Universität Erlangen-Nürnberg was granted in December 2021 (application number 21-440-B). By now, 150 patients have been enrolled in the intervention cohort. The results will be disseminated to the scientific audience and the general public via presentations at conferences and publication in peer-reviewed journal
CRIS-Team Scopus Importer:2024-10-04
Keywords: HNSCC; immune monitoring; immunological biomarker; liquid biopsy; prospective clinical trial

De-intensification of postoperative radiotherapy in head and neck cancer irrespective of human papillomavirus status—results of a prospective multicenter phase II trial (DIREKHT Trial) - Haderlein, Marlen; von der Grün, Jens; Balermpas, Panagiotis; Rödel, Claus; Hautmann, Matthias G.; Steger, Felix; Bohr, Christopher; Hehr, Thomas; Stromberger, Carmen; Budach, Volker; Schymalla, Markus; Engenhart-Cabillic, Rita; et al. (Frontiers in Oncology, 2024)
Background: Current standard treatment concepts in head and neck squamous cell carcinoma (HNSCC) are based on former studies using 2D and 3D treatment plans. However, modern radiation techniques allow for a more precise and individual dose application. Therefore, in a clearly defined patient population, de-intensified risk-adapted radiation is investigated. Methods: Patients with newly diagnosed HNSCC after surgery (with resection margins ≥1 mm and cM0) with the following tumor stages (TNM 7th Edition) were eligible for the study: oral cavity, oropharynx, or larynx: pT1–3, pN0–pN2b; hypopharynx: pT1–2, pN1. The patients should have either a low risk of local recurrence [≤pT2, resection margin ≥5 mm, no peritumoral lymphangiosis (L0), and no perineural invasion] or contralateral lymph node metastasis (≤3 ipsilateral lymph node metastases, in case of well-lateralized oropharyngeal or oral cavity cancer contralateral cN0, otherwise pN0). Patients were assigned to three different treatment regimes with reduction of the treated volume, radiation dose, or both, according to tumor stage and results of surgery performed. The primary objective was to show an LRR of <10% after 2 years. Findings: A total of 150 patients were enrolled. Tumor localizations were as follows: n = 53 (35.3%), oral cavity; n = 94 (62.7%), oropharynx (82% HPV-positive); n = 2 (1.3%), hypopharynx; and n = 1 (0.7%), larynx. A total of 61 patients (41.0%) were stage IVA, 81 (54.0%) were stage III, and 8 (5.3%) were stage II. Median follow-up was 36 months. Cumulative incidence of 2y-LRR was 5.6% (95% CI: 1.7%–9.2%) in the whole study population and 14.1% (95% CI: 3.8%–23.2%) in patients with oral cavity cancer. Cumulative incidence of 2y-LRR in non-irradiated or dose-reduced regions was 3.5% (95% CI: 0.4%–6.5%). After 2 years, disease-free survival was 92% (95% CI: 87%–96%) and overall survival was 94% (95% CI: 90%–98%) for the complete study cohort. Acute III° toxicity was as follows: dysphagia, 30%; xerostomia, 7%; mucositis, 19%; and dermatitis, 4%. Dysphagia and xerostomia decrease over time. After 27 months, late dysphagia III° and xerostomia II° were 1% and 9%, respectively. Interpretation: The study met its primary objective. De-intensification of postoperative radiotherapy irrespective of HPV status in a predefined patient population is associated with a favorable toxicity profile without compromising LRR. In an unplanned subgroup analysis, a significantly increased risk of LRR was observed in patients with oral cavity cancer. In these patients, de-intensified radiotherapy should be applied with caution.
CRIS-Team Scopus Importer:2024-09-13
Keywords: de-intensification; head and neck cancer; HPV; postoperative; radiotherapy

Depression and female gender associated with higher postoperative pain scores after sinonasal surgery - Schinz, Katharina; Steigerwald, Lukas; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Sievert, Matti; Rupp, Robin; Iro, Heinrich; Müller-Hübner, Sarina Katrin Ursel (Acta Oto-Laryngologica, 2021)
Background Although it is extremely necessary to reduce the number of opioids taken postoperatively after sinonasal surgery, this is the subject of controversial discussion. Objectives The objective of this study was to identify factors that predict higher postoperative pain scores (PPS) and the need for opioid analgesics after sinonasal surgery. Material and methods This was a retrospective study of n = 492 patients who underwent functional endoscopic sinus surgery (FESS), septoplasty or a combination of both in the Otolaryngology Department in Erlangen between January and December 2018. Postoperative pain using the numeric rating scale and the postoperative need for non-opioid and opioid analgesics in relation to demographic and surgical parameters were evaluated. Results Significant predictors for a higher pain score were depression (p = .009) and female gender (p < .001). A significant predictor of the need for postoperative opioids was the female gender (p < .001), whereas FESS alone showed a significantly lower need for opioids (p = .035) and a significantly lower PPS compared to septoplasty (p < .001). Conclusions and significance The study identified risk factors for a higher PPS and the need for opioids. The results indicated that reducing postoperative opioids might be possible in patients without these risk factors and might help guide individualized postoperative therapy.
CRIS-Team WoS Importer:2022-01-07

Der Einfluss des Kapseldefektes als Risikofaktor für die Rezidivbildung beim pleomorphen Adenom der Glandula parotidea - Buchta, Peter; Thimsen, Vivian; Iro, Ann-Kristin; Agaimy, Abbas; Iro, Heinrich; Mantsopoulos, Konstantinos (Laryngo-Rhino-Otologie, 2021)
Objective Aim of this study was to enlighten various aspects of the capsular defect of a pleomorphic adenoma and to analyze its influence on recurrence rate with the help of our data and the relevant literature. Material and Methods The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were evaluated retrospectively. The histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. The records of the cases with a capsular defect were examined for information on age, gender, type of surgery and surgical outcome. Results A total of 845 patients were included in the primary group.7 (0.8%) recurrences were detected, all of these were resected without a capsular rupture. Positive margins were found in 37 cases (4.4%). In 13/37 cases the capsular defect was detected intraoperatively, whereas the defect was only identified histopathologically in 24 of the 37 cases. In the group of the intraoperative capsular opening, with a median follow-up of 62 months, the sonographic examination suspected a unilocular recurrence of the pleomorphic adenoma in two cases. Conclusion The intraoperative capsule opening does not inevitably seem to lead to a pre-programmed recurrence.
CRIS-Team Scopus Importer:2021-07-09
Keywords: capsule; capsule opening; parotid gland; pleomorphic adenoma; recurrence; recurrence rate

Der histopathologische „Abdruck“ des Paradigmenwechsels in der Behandlung des parotidealen pleomorphen Adenoms - Mant﻿so﻿pou﻿los, Kons﻿tan﻿ti﻿nos; Iro, Ann Kristin; Agaimy, Abbas; Iro, Heinrich (HNO, 2021)
CRIS-Team Scopus Importer:2021-07-02

Diagnosing complications following cochlear implantation using transcutaneous ultrasound - Rupp, Robin; Thimsen, Vivian; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Mantsopoulos, Konstantinos; Hoppe, Ulrich; Hornung, Joachim; Iro, Heinrich; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: The aim of this study was to investigate the feasibility and reliability of transcutaneous ultrasound for the detection of complications after cochlear implantation. Methods: In a single center retrospective cohort study, 115 consecutive cases of suspected complications after cochlear implantation (intervention group) were examined. The rate of pathologic ultrasound findings for specific leading symptoms and diagnoses was compared to a control group comprising twenty consecutive cochlear implants in symptom-free patients. Results: Diagnostic ultrasound showed distinctly more pathologic findings in the intervention group (n = 67; 58.3%; p < 0.001) compared to the control group (n = 1; 5%). Ultrasound revealed significantly more pathologic findings in haematoma or seroma around the implant (n = 17; 100%; p < 0.001; ϕ = 0.94) and magnet dislocation (n = 44; 97.7%; p < 0.001; ϕ = 0.92) confirmed by a strong effect. Ultrasound examination showed a medium to high effect size in patients presenting with local infections (n = 3; 21.4%; p = 0.283; ϕ = 0.25) and skin flap oedema (n = 2; 50%; p = 0.061; ϕ = 0.51). In contrast, ultrasound examinations displayed a low effect size in undefined cephalgia (0%; p = 0.444; ϕ = 0.17) and device malfunction or failure (0%; p > 0.999; ϕ = 0.13). Conclusion: Transcutaneous ultrasound can be advocated as a feasible and effective method in the diagnostic work-up of magnet dislocation and haematoma or seroma around the implant following cochlear implantation. Contrary, ultrasound findings can be expected to be inconspicuous in patients presenting with undefined cephalgia and device malfunction or failure.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Cochlear implant; Diagnostic sonography; Haematoma; Magnet dislocation; Seroma; Transcutaneous ultrasound

Diagnosis of malignancy in oropharyngeal confocal laser endomicroscopy using GPT 4.0 with vision - Sievert, Matti; Aubreville, Marc; Müller, Sarina Katrin; Eckstein, Markus; Breininger, Katharina; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2024)
Purpose: Confocal Laser Endomicroscopy (CLE) is an imaging tool, that has demonstrated potential for intraoperative, real-time, non-invasive, microscopical assessment of surgical margins of oropharyngeal squamous cell carcinoma (OPSCC). However, interpreting CLE images remains challenging. This study investigates the application of OpenAI’s Generative Pretrained Transformer (GPT) 4.0 with Vision capabilities for automated classification of CLE images in OPSCC. Methods: CLE Images of histological confirmed SCC or healthy mucosa from a database of 12 809 CLE images from 5 patients with OPSCC were retrieved and anonymized. Using a training data set of 16 images, a validation set of 139 images, comprising SCC (83 images, 59.7%) and healthy normal mucosa (56 images, 40.3%) was classified using the application programming interface (API) of GPT4.0. The same set of images was also classified by CLE experts (two surgeons and one pathologist), who were blinded to the histology. Diagnostic metrics, the reliability of GPT and inter-rater reliability were assessed. Results: Overall accuracy of the GPT model was 71.2%, the intra-rater agreement was κ = 0.837, indicating an almost perfect agreement across the three runs of GPT-generated results. Human experts achieved an accuracy of 88.5% with a substantial level of agreement (κ = 0.773). Conclusions: Though limited to a specific clinical framework, patient and image set, this study sheds light on some previously unexplored diagnostic capabilities of large language models using few-shot prompting. It suggests the model`s ability to extrapolate information and classify CLE images with minimal example data. Whether future versions of the model can achieve clinically relevant diagnostic accuracy, especially in uncurated data sets, remains to be investigated.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Confocal laser endomicroscopy; GPT; Head and neck malignancies; Oropharyngeal squamous cell carcinoma

Diagnostic Challenges and Imaging Considerations for Intraparotid Facial Nerve Schwannoma: A Case Report and Literature Review - Luzha, Jeton; Kopp, Markus; Wiesmüller, Marco; Taha, Lava; Rupp, Robin; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Sievert, Matti (American Journal of Case Reports, 2024)
Background: A mass in the parotid gland usually indicates parotid gland neoplasia. Warthin tumors or pleomorphic adenomas are common differential diagnoses. Less frequently, other differential diagnoses and sites of origin are considered. Schwannomas are rare, benign tumors in the head and neck region. Even more rarely, these tumors occur in the intraparotid course of the facial nerve. In the following, we report about 2 patients in whom a mass in the right parotid gland was found incidentally during magnetic resonance imaging (MRI). Case Reports: We reviewed data from the literature on intraparotid facial nerve schwannomas (IPFNS) and compared them with those from our cases. The focus was on data such as clinical history, clinical symptoms, electroneurography, and various imaging modalities, such as ultrasonography and MRI combined with diffusion-weighted imaging. Conclusions: It is challenging to distinguish facial nerve schwannomas from other neoplasms. Patient’s history, clinical symptoms, MRI examination with diffusion-weighted imaging, and high-resolution ultrasound imaging are decisive factors for diagnosis and should be performed when IPFNS is suspected. Diagnosis and therapy for IPFNS remain challenging. A wait-and-scan approach could be an option for patients with small tumors and good facial nerve function. On the other hand, patients with advanced tumors associated with limited facial nerve function can benefit from surgical approaches or stereotactic radiosurgery.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Facial Nerve Diseases; Facial Paralysis; Nerve Sheath Neoplasms; Parotid Gland

Diagnostic value of 3D dynamic contrast-enhanced magnetic resonance imaging in lymph node metastases of head and neck tumors: a correlation study with histology - Treutlein, Christoph; Stollberg, Adrian; Scherl, Claudia; Agaimy, Abbas; Ellmann, Stephan; Iro, Heinrich; Lell, Michael; Uder, Michael; Bäuerle, Tobias (Acta Radiologica Open, 2020)
Background: Accurate staging of cervical lymph nodes (LN) is pivotal for further clinical management of patients with head and neck cancer. Functional magnetic resonance imaging (MRI) such as three-dimensional (3D) dynamic contrast-enhanced (DCE) acquisition might improve the diagnosis of cervical LN metastases.
CRIS-Team WoS Importer:2020-09-25

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Differences in Need for Opioids After Sinonasal Surgery at Day of Surgery and in the Postoperative Period - Steigerwald, Lukas; Schinz, Katharina; Sievert, Matti; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Iro, Heinrich; Müller, Sarina Katrin (Ent-Ear Nose & Throat Journal, 2021)
Introduction: In the last years, the use of opioid analgesics has increased, as well as their morbidity and mortality, especially in the United States. Most patients after sinonasal surgery receive opioid analgesics, although up to 90% have leftover opioid pills. Around 70% of these patients keep the opioid analgesics, which could possibly lead to improper use. The objective of the following study was the investigation of the need for, use of, timing and side effects of opioid and non-opioid analgesics after sinonasal surgery. Methods: This was a retrospective study of (n = 280) patients who underwent sinonasal surgery in the Otolaryngology Department of the University Erlangen-Nürnberg between January and December 2018. The postoperative pain (3-5 days after surgery) using the numeric rating scale and the postoperative need for on-demand opioids and non-opioid analgesics in relation to demographic and surgical parameters were evaluated. Results: Of total, 59.64% of all patients received opioid analgesics postoperatively on the day of surgery. On the first postoperative day (POD1), the mean pain score yielded the highest values; however, only 0.71% of the patients needed opioid analgesics, and pain was sufficiently controlled with non-opioids or no pain medication at all. There was a significant reduction of the pain score from POD2 to 5 (P =.01; P <.01, respectively). Only 1.8% of the patients needed an opioid analgesic from POD1-5. Of total, 2.1% of the patients presented with a postoperative bleeding complication, and only 1 (0.4%) patient needed endoscopic coagulation. Conclusion: Our results indicate that the majority of patients need opioid analgesics almost exclusively on the day of surgery. There were no major complications in patients taking either opioid or non-opioids. Our results indicate that the postoperative pain regimen from POD1 should initially be started using non-opioid analgesics and be further escalated to opioid analgesics in individual cases.
CRIS-Team Scopus Importer:2021-01-22

Does increasing the incidence of extracapsular dissection for benign tumors of the parotid correlate with an increased need for revision surgery? - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Goncalves, Miguel; Schapher, Mirco; Koch, Michael; Iro, Heinrich (Oral Oncology, 2019)
Objectives: The aim of this study was to investigate the hypothesis of whether extracapsular dissection (ED) of the parotid gland increases the need for revision surgery for benign tumours in comparison to traditional surgical modalities. A further aim of this study was to evaluate and compare the functional outcome of revision procedures after primary ED with other modalities involving the parotid gland in our department.
CRIS-Team WoS Importer:2019-06-21

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Drug-Induced Sleep Endoscopy (DISE) with Target Controlled Infusion (TCI) and Bispectral Analysis in Obstructive Sleep Apnea - Traxdorf, Maximilian; Tschaikowsky, Klaus; Scherl, Claudia; Bauer, Judith; Iro, Heinrich; Angerer, Florian (Journal of Visualized Experiments, 2016)
The aim of this study was to establish a standardized protocol for drug-induced sleep endoscopy (DISE) to differentiate obstruction patterns in obstructive sleep apnea (OSA). Target-controlled infusion (TCI) of the sedative propofol was combined with real-time monitoring of the depth of sedation using bispectral analysis. In an observational study 57 patients (mean age 44.8 years, ± SD 10.5; mean apnea hypopnea Index (AHI) 30.8/hr, ± SD 21.6, mean BMI 28.2 kg/m(2), ± SD 5.3) underwent cardiorespiratory polysomnography followed by DISE with TCI and bispectral analysis. Sleep was induced solely by the intravenous infusion of propofol with a TCI-pump, with an initial target plasma level of 2.0 µg/ml. Under continuous monitoring of the patient's respiration, state of consciousness and value of the bispectral analysis, the target plasma propofol level was raised in steps of 0.2 µg/ml/2 min until the desired depth of sedation was reached. The mean value of the bispectral analysis at the target depth of sedation was determined and the obstruction patterns during DISE-TCI-bispectral analysis then classified according to the VOTE-system. Subsequently the results were analyzed according to polysomnographic and anthropometric data. The occurrence of multilevel obstruction sites across all degrees of severity of OSA clarifies the need for sleep endoscopy prior to upper airway surgery. The advantage of this technique is the reproducibility of the protocol even for heterogeneous groups of patients. In addition, the gradual controlled and standardized increase of the plasma level of propofol with real-time control of the bispectral index leads to a precisely controllable depth of sedation. The DISE-TCI-bispectral analysis procedure is a step towards a required reproducible protocol of sleep endoscopy - capable of standardization. However it is not yet known whether these observed obstruction patterns also correspond to findings in natural sleep.
EVALuna2:16743

EAONO/JOS classification for acquired cholesteatoma: evaluating the impact of the number of affected sites on treatment and outcomes - Renner, Beatrix; de Vasconcelos Craveiro, Antonio; Balk, Matthias; Allner, Moritz; Sievert, Matti; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Iro, Heinrich; Rupp, Robin; Hornung, Joachim; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Purpose: The European and Japanese system for cholesteatoma classification proposed an anatomical differentiation in five sites. In stage I disease, one site would be affected and in stage II, two to five. We tested the significance of this differentiation by analyzing the influence of the number of affected sites on residual disease, hearing ability and surgical complexity. Methods: Cases of acquired cholesteatoma treated at a single tertiary referral center between 2010-01-01 and 2019-07-31 were retrospectively analyzed. Residual disease was determined according to the system. The air–bone gap mean of 0.5, 1, 2, 3 kHz (ABG) and its change with surgery served as hearing outcome. The surgical complexity was estimated regarding the Wullstein’s tympanoplasty classification and the procedure approach (transcanal, canal up/down). Results: 513 ears (431 patients) were followed-up during 21.6 ± 21.5 months. 107 (20.9%) ears had one site affected, 130 (25.3%) two, 157 (30.6%) three, 72 (14.0%) four and 47 (9.2%) five. An increasing number of affected sites resulted in higher residual rates (9.4–21.3%, p = 0.008) and surgical complexity, as well poorer ABG (preoperative 14.1 to 25.3 dB, postoperative 11.3–16.8 dB, p < 0.001). These differences existed between the means of cases of stage I and II, but also when only considering ears with stage II classification. Conclusion: The data showed statistically significant differences when comparing the averages of ears with two to five affected sites, questioning the pertinence of the differentiation between stages I and II.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cholesteatoma; EAONO/JOS classification; Tympanoplasty

Early stage oropharyngeal carcinomas: comparing quality of life for different treatment modalities - Ryzek, Don-Felix; Mantsopoulos, Konstantinos; Künzel, Julian; Grundtner, Philipp; Zenk, Johannes; Iro, Heinrich; Psychogios, Georgios (BioMed Research International, 2014)
To compare long-term quality of life outcomes after treating early stage oropharyngeal carcinoma either with surgery, surgery combined with radiotherapy, or surgery combined with chemoradiotherapy.Questionnaire based method: 111 eligible patients agreed to fill out a quality of life questionnaire.Of the 32 scales contained in the EORTC's combined QLQ-C30 and HN35, 11 scales show significantly better results for the surgery-only treatment group when compared to either surgery combined with radiotherapy or surgery combined with any type of adjuvant therapy. These eleven scales are role function (P = 0.019/0.008), social function (P = 0.01/0.034), nausea (P = 0.017/0.025), pain (P = 0.014/0.023), financial problems (P = 0.030/0.012), speech (P = 0.02/0.015), social eating (P = 0.003/<0.001), mouth opening (P = 0.033/0.016), sticky saliva (P = 0.001/<0.001), swallowing (P < 0.001/<0.001), and dry mouth (P < 0.001/0.001).Treatment of early stage oropharyngeal carcinoma with surgery alone has definite advantages over treatments including any form of adjuvant therapy when considering quality of life. Advantages manifest themselves especially in functional aspects of the head and neck realm; however general health aspects as well as psychosocial aspects show improvements as well. This study does not show any indication of QOL-related drawbacks of surgery-only treatment approaches.
EVALuna2:19929

Effect of postoperative systemic prednisolone on short-term and long-term outcomes in chronic rhinosinusitis with nasal polyps: A multi-centered randomized clinical trial - Müller, Sarina Katrin; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Hosemann, Werner; Olze, Heidi; Steinhart, Helmut; Wiegand, Susanne; Teymoortash, Afshin; Kuehnel, Thomas; Hackenberg, Stephan; Hummel, Thomas; et al. (Frontiers in Immunology, 2023)
Introduction: The objective of this study was to determine whether postoperative additive systemic steroid administration in chronic rhinosinusitis with nasal polyps (CRSwNP) impacted selected endoscopic, subjective and objective outcome measures. Methods: This was a prospective, randomized, double-blind, placebo-controlled, noninferiority multicenter trial of n=106 patients with CRSwNP. All patients underwent primary functional endoscopic sinus surgery (FESS) followed by topical nasal steroids. Patients were randomized to a systemic steroid or placebo for 1 month. Patients were followed up for 2 years over 9 time points. The primary outcome measures were the differences between groups with respect to the nasal polyp score (NPS) and sinonasal quality of life (SNQoL). Secondary outcome measures included interactions with respect to the Lund-Kennedy score (LKS), sinonasal symptoms, general quality of life (GQoL), 16-item odor identification test scores, recurrence rates, need for revision surgery and mucus biomarker levels. Results: 106 patients were randomized to either the placebo or the systemic steroid group (n=53 per group). Postoperative systemic steroids were not superior to placebo with respect to all primary (p= 0.077) and secondary outcome measures (p>0.05 for all). Reported adverse events were similar between the two groups. Conclusion: In conclusion, the addition of postoperative systemic steroids after primary FESS did not confer a benefit over topical steroid nasal spray alone with respect to NPS, SNQOL, LKS, GQOL, sinonasal symptoms, smell scores, recurrence rates, the need for revision surgery or biomarkers over a short-term follow-up of up to 9 months and a long-term follow-up of up to 24 months in CRSwNP patients. Functional endoscopic surgery did, however, show a strong effect on all outcome measures, which remained relatively stable up to the endpoint at 2 years.
CRIS-Team Scopus Importer:2023-03-31
Keywords: chronic rhinosinusitis; long-term; nasal polyp (NP); postoperative; prednisolone; randomized controlled trial

Endoscopic laser diverticulotomy in Zenker's diverticulum: Experiences with basal wound sealing using a collagen-fibrin patch - Koch, Michael; Thimsen, Vivian; Traxdorf, Maximilian; Zenk, J.; Iro, Heinrich; Treutlein, Eric; Mantsopoulos, Konstantinos (European Review for Medical and Pharmacological Sciences, 2021)
OBJECTIVE: Very few reports investigated techniques of closure of the basal wound area to reduce severe complications like mediastinitis after endoscopic laser diverticulotomy. In this study, we report our experiences after routine use of a collagen-fibrin sealant patch for basal wound covering after laser diverticulotomy in consideration of postoperative complications and recurrence rates. PATIENTS AND METHODS: This retrospective study was conducted in a tertiary referral center and university hospital. Endoscopic laser diverticulotomies performed in our hospital between January 2006 and July 2018 were included. After complete transection of the laser septum of the diverticulum, we placed a collagen-fibrin patch onto the basal wound area to cover the opening to the mediastinum. Patient records were evaluated to assess the occurrence of perioperative complications, and the data were compared with those reported in the literature. RESULTS: A total of 127 endoscopic laser diverticulotomies were performed in 109 patients (71 men, 38 women) suffering from Zenker's diverticulum. Morality rate was 0%, in particular no mediastinitis was observed. Mediastinal emphysema was observed in two patients (1.6%), and temporary or persistent recurrent nerve palsy in one patient (0.8%) each. The mean follow-up period was 71.6±5.16 months. Recurrent symptomatic diverticulum was observed in 19.3% of the patients. CONCLUSIONS: These findings suggest that use of a collagen-fibrin sealant patch in endoscopic laser diverticulotomy may contribute to the safety of endoscopic controlled laser diverticulotomy without comprising the success rates.
CRIS-Team Scopus Importer:2021-08-06
Keywords: CO; Complications; Endoscopic; Minimally invasive; Treatment; Zenker's diverticulum

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Epidemiology and survival of HPV-related tonsillar carcinoma - Psychogios, Georgios; Alexiou, Christoph; Agaimy, Abbas; Brunner, Kathrin; Koch, Michael; Mantsopoulos, Konstantinos; Tomppert, Andrea; Iro, Heinrich (Cancer Medicine, 2014)
The aim of this study was to determine the proportion of human papilloma virus (HPV)-positive cases in tonsillar carcinomas and investigate its development over the last decade. Further aim was to show the oncologic results in accord to HPV status and various treatment modalities. A retrospective study was conducted between 2000 and 2012 and included 275 patients treated for tonsillar carcinoma. P16 immunohistochemistry was used as a surrogate marker for HPV-associated carcinogenesis. A total of 101 (36.7%) patients proved to be p16 positive and 174 p16 negative. 80.2% of the p16-positive cases presented with T1-2 tumor. Of the early-stage patients, 79% of the p16-positive and 52.3% of the p16-negative presented with lymph node metastases. The percentage of p16-positive patients increased from 23.2% in the period 2005-2007 to 58.6% in the period 2010-2012 in the whole population and from 30.9% to 76.9% in T1-2 carcinomas. Early T-category p16-positive carcinomas had significantly better disease-specific survival (92.4% vs. 75.5%, P = 0.007) and overall survival (OS, 79.6% vs. 54.3%, P < 0.001) compared to p16-negative tumors. This study showed an increase in the percentage of p16-positive patients in tonsillar carcinoma from 23.2% in the years between 2005 and 2007 to 58.6% between 2010 and 2012. The majority (80.2%) of p16-positive patients presented with early T-category tumor but most of these (79.0%) had also lymph node metastases. Nevertheless, p16-positive patients had excellent oncologic results after surgery and adjuvant radiotherapy and could be considered for de-escalation of treatment.
EVALuna2:6679

Erratum: Correction: Confocal laser endomicroscopy of head and neck squamous cell carcinoma: a systematic review (Laryngo- rhino- otologie (2021) 100 11 (875-881)) Erratum: Konfokale Laser-Endomikroskopie des Kopf-Hals-Plattenepithelkarzinoms: eine systematische Übersicht - Sievert, Matti; Aubreville, Marc; Oetter, Nicolai; Stelzle, Florian; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (Laryngo-Rhino-Otologie, 2021)
CRIS-Team Scopus Importer:2024-12-16

Escalation in mucus cystatin 2, pappalysin-A, and periostin levels over time predict need for recurrent surgery in chronic rhinosinusitis with nasal polyps - Müller, Sarina Katrin; Wendler, Olaf; Nocera, Angela; Grundtner, Philipp; Schlegel, Patrick; Agaimy, Abbas; Iro, Heinrich; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2019)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is treated using oral/topical steroids and surgery. Despite maximal medical therapy, some patients remain recalcitrant. Mucus cystatin 2, pappalysin-A, and periostin can predict the presence of CRSwNP and correlate with disease severity. This study was designed to determine whether prospective sampling of these mucus proteins could predict medical failure and the need for revision surgery. Methods: This investigation was an institutional review board‒approved, prospective study of 66 patients with CRSwNP. All patients underwent surgery, administration of topical/oral steroids, and outpatient mucus sampling at 10 time-points over 2 years. Five proteins, including cystatin 2 (CST2), pappalysin-A (PAPP-A), and periostin (PST), were analyzed and correlated with subjective parameters (including scores on the 22-item Sino-Nasal Outcomes Test [SNOT-22]). Variables were then analyzed and compared between those requiring revision surgery within 2 years (n = 5) and those with stable disease (n = 61). Results: All patients demonstrated a significant decline in CST2, PAPP-A, and periostin after their initial surgery. The recalcitrant group demonstrated escalations in all proteins despite steroids, with levels higher than those of the stable group at 1 year (CST2: 258.1 ± 205.2 pg/mL vs 235.3 ± 275.7 pg/mL, p = 0.86; PAPP-A: 170.3 ± 150.4 pg/mL vs 74.6 ± 106.7 pg/mL, p < 0.05; periostin: 188.8 ± 192.4 ng/mL vs 54.5 ± 47.6 ng/mL, p < 0.001). Escalation in all proteins correlated significantly with worsening SNOT-22 score at each time-point (domain 1: 8.2 ± 1.3 vs 5.5 ± 1.1; p < 0.05). Conclusion: Early recurrences and medical recalcitrance in CRSwNP may be predicted noninvasively through the serial, prospective sampling of mucus CST2, PAPP-A, and periostin levels. These biosignatures may help to predict disease course and guide individualized therapy.
CRIS-Team Scopus Importer:2019-08-30
Keywords: biomarker; chronic rhinosinusitis; mucus; noninvasive; recurrence

Evaluation of preoperative Ultrasonography in the Differentiation between Superficial and Deep Parotid Gland Tumors - Mantsopoulos, Konstantinos; Tschaikowsky, Nastasja; Goncalves, Miguel; Müller, Sarina Katrin; Iro, Heinrich (Ultrasound in Medicine and Biology, 2020)
Imaging of the intraparotid course of the facial nerve remains a challenge and is not an established routine procedure. The aim of this study was to evaluate ultrasound in localizing a parotid tumor in relation to the facial nerve. The ultrasound findings and operative reports of all patients treated for parotid gland tumors were studied retrospectively. Eight hundred sixty-eight parotid lesions formed our study sample. The unit of measurement was the minimal distance between the parotideomasseteric fascia and the superficial capsule of the tumor, measured in millimeters by means of ultrasound. The mean value for this parameter was 1.3 mm for superficial and 4.6 mm for deep lobe tumors (p < 0.001). When the cutoff value was set at 2.6 mm, the sensitivity and specificity of ultrasound were 89.6 and 88.4%, respectively. Our study revealed that ultrasound can help in the pre-operative differentiation between tumors of the superficial and deep lobes of the parotid gland.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Deep lobe; Facial nerve; Parotid gland; Superficial lobe; Ultrasonography

Evolution and changing trends in surgery for benign Parotid tumors - Mantsopoulos, Konstantinos; Koch, Michael; Klintworth, Nils; Zenk, Johannes; Iro, Heinrich (Laryngoscope, 2015)
The ideal extent of surgical intervention for benign parotid tumors remains a matter of controversy. The aim of the study was to trace the development of surgical therapy in a large cohort, explore its changes in a single institution specializing in salivary gland pathologies over the last 12 years, and determine the extent to which a possible shift in the surgical therapy of parotid benign tumors toward less radical methods was correlated with a change in the incidence of facial palsy and Frey's syndrome.Retrospective clinical study.A retrospective evaluation of the records for all patients treated for benign parotid tumors between 2000 and 2012 at a tertiary referral center was carried out. Surgical methods were classified into four groups: extracapsular dissection, partial superficial parotidectomy, superficial parotidectomy, and complete parotidectomy.A total of 1,624 patients were included in the study. Our analysis demonstrated an increase in the total number of parotidectomies for benign lesions from 71 (2000) to 184 (2012), mostly due to the increase in extracapsular dissections (from 9 to 123). Increased performance of less radical surgery was associated with a significantly decreased incidence of temporary and permanent facial palsies (from 22.8% to 9% and 9.8% to 5.9%, respectively) and Frey's syndrome (from 11.3% to 1.6%).One of the most controversial issues in the treatment of benign parotid tumors is the best therapeutic approach to be taken in such patients. Our study showed that increased performance of less radical surgery was associated with better functional outcomes.2b. Laryngoscope, 125:122-127, 2015.
EVALuna2:19934

Exosomal serum biomarkers as predictors for laryngeal carcinoma - Müller, Sarina Katrin; Schuster, Johannes; Wendler, Olaf; Iro, Heinrich; Gostian, Antoniu-Oreste (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Experiences in the treatment of patients with multiple head and neck paragangliomas - Künzel, Julian; De Tristan, Julie; Mantsopoulos, Konstantinos; Koch, Michael; Baussmerth, Marcela; Zenk, Johannes; Iro, Heinrich (American Journal of Otolaryngology, 2014)
To analyze treatment results in the multidisciplinary management of patients with multiple head and neck paragangliomas (HNPs).Retrospective analysis including all patients with multiple HNPs (VP, vagal paraganglioma; JTP, jugulotympanic paraganglioma; CBT, carotid body tumor) treated between 2000 and 2013 at a tertiary referral center.Ten patients (three men, seven women) had 25 HNPs (two VPs, eight JTPs, and 15 CBTs). The age range at diagnosis was 31-71 years (mean 40.9 years, median 37 years). Nine tumors (four CBTs, three JTPs, two VPs) were treated only with stereotactic radiotherapy (SRT; 50.4-56Gy, mean 55.3Gy) or in one case intensity-modulated radiotherapy (60 Gy). Nine tumors were treated with surgery alone (eight CBTs, one JTP) and three JTPs with subtotal surgery combined with adjuvant SRT. A "wait and scan" strategy was used in three cases (two CBTs, one JTP). The mean follow-up period was 4.3 years (range 0.1-13 years, median 4 years). The rate of tumor control with surgery and/or SRT was 100% (21/21). One patient with a wait-and-scan strategy for CBT had slow asymptomatic progression during a 13-year follow-up.The treatment results in this series of patients with multiple HNPs show that a very high rate of long-term tumor control with low morbidity can be achieved using tailored and individualized approaches. All of the different treatment strategies available should be discussed with the patient. In particular, the treatment should involve a multidisciplinary team of experts in the fields of nuclear medicine, genetics, pathology, radiology, radio-oncology, and surgery.
EVALuna2:18180

Explainable convolutional neural networks for assessing head and neck cancer histopathology - Dörrich, Marion; Hecht, Markus; Fietkau, Rainer; Hartmann, Arndt; Iro, Heinrich; Gostian, Antoniu-Oreste; Eckstein, Markus; Kist, Andreas (Diagnostic Pathology, 2023)
Purpose: Although neural networks have shown remarkable performance in medical image analysis, their translation into clinical practice remains difficult due to their lack of interpretability. An emerging field that addresses this problem is Explainable AI. Methods: Here, we aimed to investigate the ability of Convolutional Neural Networks (CNNs) to classify head and neck cancer histopathology. To this end, we manually annotated 101 histopathological slides of locally advanced head and neck squamous cell carcinoma. We trained a CNN to classify tumor and non-tumor tissue, and another CNN to semantically segment four classes - tumor, non-tumor, non-specified tissue, and background. We applied Explainable AI techniques, namely Grad-CAM and HR-CAM, to both networks and explored important features that contributed to their decisions. Results: The classification network achieved an accuracy of 89.9% on previously unseen data. Our segmentation network achieved a class-averaged Intersection over Union score of 0.690, and 0.782 for tumor tissue in particular. Explainable AI methods demonstrated that both networks rely on features agreeing with the pathologist’s expert opinion. Conclusion: Our work suggests that CNNs can predict head and neck cancer with high accuracy. Especially if accompanied by visual explanations, CNNs seem promising for assisting pathologists in the assessment of cancer sections.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Classification; Explainable AI; Head and neck cancer; Histopathology; Semantic segmentation

Extended and treatment-oriented classification of parotid duct stenosis - Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To provide an extended and treatment-oriented classification of parotid duct stenosis that might be useful in the management of this condition. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: A total of 550 symptomatic stenoses of the parotid gland excretory duct in 445 patients were analyzed. Sialendoscopy was performed with semirigid endoscopes. The tissue quality, location, grade of luminal narrowing, and length and number of the stenoses were assessed. RESULTS: Inflammation-dominant stenosis (type 1) was found in 8.9% of the patients, web-associated fibrous stenosis (type 2) in 19.5%, and fibrous (type 3) in 71.6%. Multiple stenoses (≥3) were found in 2.8% of patients, and bilateral stenoses in 11.9%. Type 1 stenoses differed significantly from type 3 stenoses, with lower grades. Type 3 stenoses showed significantly higher grades of luminal narrowing than the other two types (P = .0001). Type 2 stenoses were significantly shorter in comparison with the other two types (P = .0001). Multiple stenoses were observed significantly more often in type 2 than in type 3 stenoses (P = .0001). Due to these differences, the type of stenosis appears to be the most important criterion in the treatment-oriented classification. CONCLUSIONS: Significant differences between the different stenoses were observed. Type 1 stenosis may be considered as a precursor of type 3 stenosis, but type 2 stenosis showed significantly different characteristics. The differences prescribed in this classification may be helpful in the management of parotid duct stenoses. LEVEL OF EVIDENCE: 4. Laryngoscope, 2016 127:366-371, 2017.
EVALuna2:33184

Extracapsular dissection as sole therapy for small low-grade malignant tumors of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVE: The aim of the study was to investigate whether extracapsular dissection of a primarily unsuspected lesion in the parotid gland could be oncologically sufficient for carefully selected cases of parotid gland malignomas. STUDY DESIGN: Retrospective clinical study. METHODS: The records of all patients treated for primary malignant tumors of the parotid gland solely by means of extracapsular dissection between 2006 and 2013 were studied retrospectively. Patients with manifestation of malignant tumors in the parotid gland that were not of primary salivary gland origin (squamous cell carcinomas, lymphomas, melanomas) or who had had revision surgery or other malignant tumors in their history, as well as patients with insufficient data, were excluded from our study sample. RESULTS: Nine patients, all with low-grade parotid malignancies, were detected. Our study showed acceptable oncologic and functional outcomes throughout. CONCLUSION: Our study was able to show very encouraging preliminary results following primary extracapsular dissection as sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:1804-1807, 2017.
EVALuna2:33197

Extracapsular dissection for warthin tumors despite the risk of ipsilateral metachronous occurrence - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Laryngoscope, 2018)
OBJECTIVES/HYPOTHESIS: The ideal extent of surgical intervention for cystadenolymphomas of the parotid gland remains a matter of controversy. The aim of our study was to assess the surgical outcome after extracapsular dissection for cystadenolymphomas of the parotid gland. A further purpose of this study was to examine how the number of primary cystadenolymphomas or the size of the primary lesion influences the possibility of an ipsilateral metachronous tumor occurrence. STUDY DESIGN: Retrospective clinical study. METHODS: A retrospective evaluation of the records was carried out for all patients treated for cystadenolymphomas of the parotid gland by means of extracapsular dissection at a tertiary referral center between 2000 and 2012. RESULTS: Three hundred twenty-seven patients were included in the study. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 3.1% (10/327) with a mean follow-up of 108.4 months. A significant difference in the rate of metachronous lesions between unilocular (1.7%) and multilocular (11.6%) tumors could be detected (χ2 (1) = 7.342, P < .001). Our analysis was not able to find any significant influence of the maximal tumor size on the rate of metachronous tumors (χ2 (1) = 0.634, P = .426). CONCLUSIONS: One of the most controversial issues in the treatment of cystadenolymphomas of the parotid gland concerns the question of which is the best therapeutic approach to be taken in such patients. Our analysis was able to demonstrate the benefits of extracapsular dissection in the management of solitary as well as carefully selected multicentric cystadenolymphomas with a consistently acceptable surgical outcome. LEVEL OF EVIDENCE: 4. Laryngoscope, 2521-2524, 2018.
EVALuna2:35386

Extracapsular Dissection in Pleomorphic Adenomas of the Parotid Gland: Results After 13 Years of Follow-up - Schapher, Mirco; Koch, Michael; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To assess long-term results after the treatment of parotid pleomorphic adenomas (PPAs) using different surgical techniques and focusing on recurrence rates and the risk of adverse effects. Study Design: Retrospective analysis. Methods: Retrospective analysis of 182 patients treated exclusively for PPAs at a tertiary referral center between 2000 and 2004. Thorough follow-up examinations over a mean period of 13 years were possible in 53.8% (n = 98/182). Tumors were categorized according to the European Salivary Gland Society (ESGS) system to improve the comparison of outcomes. After different surgical resection strategies, recurrence rates, postoperative facial nerve paresis (FNP), and incidence of Frey's syndrome were assessed. The follow-up period included clinical examinations and imaging of every patient in the treating department. Results: Of 182 patients, extracapsular dissection (ED) was performed in 29.7%, and other surgical modalities (OSMs), including facial nerve dissection, in 70.3%. After the long-term follow-up, 98% of all the patients (n = 96/98) were recurrence free. When recurrence rates were compared, no significant differences were noted (P <.331). ED resulted in significantly lower FNP rates compared to OSMs (P <.001). FNP rates significantly increased with size and location of the tumors according to ESGS categories (temporary and permanent FNP, P =.04). Surgical invasiveness corresponded to a significant increase in the incidence of Frey's syndrome (P <.001). Conclusions: ED was associated with the lowest complication rates, but not with a higher risk of recurrence, when compared with OSM in the long-term course. As ED can be performed in the majority of PPAs, it can be regarded as the treatment of choice whenever possible. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-05-22
Keywords: extracapsular dissection; facial nerve dissection; limited surgery; Parotid pleomorphic adenoma; recurrence

Extracapsular dissection in the parapharyngeal space: benefits and potential pitfalls - Mantsopoulos, K.; Müller, Sandra; Agaimy, Abbas; Goncalves, M.; Koch, Matthias; Wüst, Wolfgang; Bohr, Christopher; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2017)
The aim of this study was to investigate the benefits and potential pitfalls of transcervical extracapsular dissection in the treatment of parotid gland tumours in the parapharyngeal space. We retrospectively evaluated the records of all patients with parapharyngeal parotid gland lesions treated between 2000 and 2015 by transcervical extracapsular dissection. Patients having revision operations and patients whose records were not complete were excluded, leaving 49 patients in the study. We found acceptable oncological and functional outcomes throughout. Special attention should be paid in cases with multilobular growth of the tumour on magnetic resonance imaging, satellite tumours of pleomorphic adenomas, tumours in broad contact with the inner surface of the deep lobe, and lesions suspected of malignancy. Extracapsular dissection in the parapharyngeal region is associated with acceptable oncological and functional outcomes. These outcomes can be expected only after a thorough assessment of patient's history and preoperative imaging.
EVALuna2:6890

Extracapsular dissection versus conventional parotidectomy: comparing ‘apples with oranges’? - Mantsopoulos, Konstantinos; Iro, Heinrich (International Journal of Oral and Maxillofacial Surgery, 2022)
CRIS-Team Scopus Importer:2022-03-25

Extracorporeal Lithotripsy - Koch, Michael; Iro, Heinrich (Surgery of the Salivary Glands, 2021)
CRIS-Team Scopus Importer:2024-12-16
Keywords: Complications; Electromagnetic; ESWL; Extracorporeal; Lithotripsy; Sialolithiasis

Extracranial temporal bone paragangliomas: Re-defining the role of otologic surgery within the scope of function-preserving multimodal concepts - Mantsopoulos, Konstantinos; Thimsen, Vivian; Eisenhut, Felix; Weissmann, Thomas; Putz, Florian; Fietkau, Rainer; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2022)
Introduction: The aim of this study was to present our concept in the management of extracranial temporal bone paragangliomas and demonstrate the outcome after primary surgical management of the middle ear component, with an individualized indication for adjuvant radiotherapy. Materials and methods: The records of all patients treated for extracranial jugulotympanic paragangliomas by means of primary surgical management between 2010 and 2021 were studied retrospectively. Results: Twenty-nine patients made up our study sample (mean age 58.8 years). 15 cases were managed solely by means of surgery. Out of the remaining 14 cases with reduction of the middle ear component, adjuvant irradiation was performed in 11 cases, whereas a wait-and-scan strategy was adopted at the patient's request in three cases. No further growth was detected in our study cases. Conclusion: Our protocol seems to be associated with an acceptable quality of life and a satisfactory oncologic outcome.
CRIS-Team WoS Importer:2021-10-15

Extramedullary plasmacytoma: Tumor occurrence and therapeutic concepts-A follow-up - Holler, Adrian; Cicha, Iwona; Eckstein, Markus; Haderlein, Marlen; Poettler, Marina; Rappl, Anja; Iro, Heinrich; Alexiou, Christoph (Cancer Medicine, 2022)
Background Extramedullary plasmacytoma (EMP) is a solitary tumor consisting of neoplastic plasma cells, with very little to no bone marrow involvement. EMPs are usually located in the head and neck region, but can also occur along the digestive tract, in lungs, or extremities. Methods Following our publication on EMP, which appeared in 1999 (Cancer 85:2305-14), we conducted a literature search for EMP-related reports published between 1999 and 2021. The documented cases, as well as 14 of our own patients from the ENT Clinic Erlangen, were extensively analyzed. Results Between 1998 and 2021, 1134 patients with EMP were reported, for whom information about the tumor localization was available. Among those, 62.4% had EMP in the head and neck area and 37.6% in other body regions. Data on therapy were reported in 897 patients, including 34.3% who received radiation, 28.1% surgery, 22.6% a combination of surgery and radiation, and 15.9% another therapy. In 76.9% patients no recurrence or transformation to multiple myeloma (MM) was reported, 12.8% showed local recurrence and 10.2% developed MM. Radiotherapy alone was associated with a tendency for increased occurrence of MM. In patients with EMP of head and neck area, combination therapy (surgery and radiation) resulted in a 5-year overall survival rate of 98.3%, surgery alone of 92.4%, and radiotherapy of 92.7%. Conclusions Collectively, our analyses indicate that surgical resection alone can achieve long-term tumor control in patients with EMP, if the tumor can be removed within safe limits without causing serious functional impairment. However, if this is not certain, either radiation or a combination of surgery and radiation therapy is suggested as an effective means of local tumor control.
CRIS-Team WoS Importer:2022-05-27
Keywords: extramedullary plasmacytoma; non-Hodgkin lymphoma; survival; therapy; tumor outcomes

F18-FDG PET/CT imaging early predicts pathologic complete response to induction chemoimmunotherapy of locally advanced head and neck cancer: preliminary single-center analysis of the checkrad-cd8 trial - Beck, Michael; Hartwich, J.; Eckstein, Markus; Schmidt, D.; Gostian, Antoniu-Oreste; Müller-Hübner, Sarina Katrin Ursel; Rutzner, Sandra; Gaipl, Udo; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Klautke, G.; et al. (Annals of Nuclear Medicine, 2022)
Aim: In the CheckRad-CD8 trial patients with locally advanced head and neck squamous cell cancer are treated with a single cycle of induction chemo-immunotherapy (ICIT). Patients with pathological complete response (pCR) in the re-biopsy enter radioimmunotherapy. Our goal was to study the value of F-18-FDG PET/CT in the prediction of pCR after induction therapy. Methods: Patients treated within the CheckRad-CD8 trial that additionally received FDG- PET/CT imaging at the following two time points were included: 3–14 days before (pre-ICIT) and 21–28 days after (post-ICIT) receiving ICIT. Tracer uptake in primary tumors (PT) and suspicious cervical lymph nodes (LN +) was measured using different quantitative parameters on EANM Research Ltd (EARL) accredited PET reconstructions. In addition, mean FDG uptake levels in lymphatic and hematopoietic organs were examined. Percent decrease (Δ) in FDG uptake was calculated for all parameters. Biopsy of the PT post-ICIT acquired after FDG-PET/CT served as reference. The cohort was divided in patients with pCR and residual tumor (ReTu). Results: Thirty-one patients were included. In ROC analysis, ΔSUVmax PT performed best (AUC = 0.89) in predicting pCR (n = 17), with a decline of at least 60% (sensitivity, 0.77; specificity, 0.93). Residual SUVmax PT post-ICIT performed best in predicting ReTu (n = 14), at a cutpoint of 6.0 (AUC = 0.91; sensitivity, 0.86; specificity, 0.88). Combining two quantitative parameters (ΔSUVmax ≥ 50% and SUVmax PT post-ICIT ≤ 6.0) conferred a sensitivity of 0.81 and a specificity of 0.93 for determining pCR. Background activity in lymphatic organs or uptake in suspected cervical lymph node metastases lacked significant predictive value. Conclusion: FDG-PET/CT can identify patients with pCR after ICIT via residual FDG uptake levels in primary tumors and the related changes compared to baseline. FDG-uptake in LN + had no predictive value. Trial registry: ClinicalTrials.gov identifier: NCT03426657.
CRIS-Team Scopus Importer:2022-05-20
Keywords: FDG-PET/CT; Head neck cancer; HNSCC; Immunotherapy; Induction therapy

Factors Influencing the Outcome of Head and Neck Cancer of Unknown Primary (HNCUP) - Rupp, Robin; Mantsopoulos, Konstantinos; Sievert, Matti; Gostian, Magdalena; Allner, Moritz; Grundtner, Philipp; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (Journal of Clinical Medicine, 2022)
Background: This study on patients with head and neck cancer of unknown primary (HNCUP) assesses the impact of surgical and non-surgical treatment modalities and the tumour biology on the oncological outcome. Methods: A total of 80 patients with HNCUP (UICC I-IV) were treated with simultaneous neck dissection followed by adjuvant therapy, between 1 January 2007 and 31 March 2020. As the primary objective, the influence of treatment modalities on the overall survival (OS), the disease-specific survival (DSS) and the progression-free survival (PFS) were analysed in terms of cox regression and recursive partitioning. The tumour biology served as secondary objectives. Results: The 5-year OS for the entire cohort was 67.7%, (95% CI: 54.2-81.2%), the 5-year DSS was 82.3% (72.1-92.5%) and the 5-year PFS was 72.8% (61.8-83.8%). Cox regression revealed that patients undergoing adjuvant radiotherapy only had a four times higher risk to die compared to patients receiving chemoradiation therapy (HR = 4.45 (1.40; 14.17), p = 0.012). The development of distant metastases had a significantly negative impact on OS (HR = 8.24 (3.21-21.15), p < 0.001) and DSS (HR = 23.79 (6.32-89.56), p < 0.001). Recursive portioning underlined the negative influence of distant metastases on OS (3.2-fold increase in death probability) and DSS (4.3-fold increase in death probability), while an UICC stage of IVb increased the risk for further progression of the disease by a factor of 2. Conclusions: The presence of distant metastases as well as adjuvant treatment with radiation without concomitant chemotherapy, were among others, significant predictors for the overall survival of HNCUP patients, with distant metastases being the most significant predictor.
CRIS-Team WoS Importer:2022-06-10

Failure of pedicled flap reconstruction in the head and neck area: A case report of a bilateral subclavian artery stenosis - Sievert, Matti; Koch, Michael; Mantsopoulos, Konstantinos; Traxdorf, Maximilian; Müller, Sarina Katrin; Iro, Heinrich; Scherl, Claudia (International Journal of Surgery Case Reports, 2020)
Introduction: Pedicled flap reconstruction still plays an essential role in head and neck surgery as an alternative to free grafts. Two standard methods are the pectoralis major and the deltopectoral flap, which are generally characterized by their reliable perfusion. This case describes bilateral arteriosclerosis of the subclavian artery as a possible cause of flap failure. Presentation of case: We report on a 65-year-old patient with a multilevel carcinoma of the right pharynx. Due to the unique patient history, a free flap reconstruction was not possible. After resection of the primary, we performed reconstruction with a pedicled pectoralis major flap. Discussion: Postoperatively, we observed necrosis of the pectoralis major flap. Secondary defect reconstructions were performed with a deltopectoral flap first from the right and then, in the case of necrosis, from the left side. Stenosing arteriosclerotic plaques of the subclavian artery on both sides were the cause of flap failure. Conclusion: Preoperative angiography of the subclavian artery is not a standard diagnostic procedure in the surgical planning of pedicled flap reconstruction in the head and neck region. In exceptional cases, we recommend angiographic imaging of the supplying vessels to make a more precise flap selection and avoid complications.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Case report; Deltopectoral flap; Flap failure; Head and neck surgery; Pectoralis major flap; Pedicled flap reconstruction

Feasibility of intraoperative assessment of safe surgical margins during laryngectomy with confocal laser endomicroscopy: A pilot study - Sievert, Matti; Oetter, Nicolai; Aubreville, Marc; Stelzle, Florian; Maier, Andreas; Eckstein, Markus; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Koch, Michael; Agaimy, Abbas; Iro, Heinrich; et al. (Auris Nasus Larynx, 2021)
Objective: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with Confocal Laser Endomicroscopy (CLE) during planned partial or total laryngectomy. Methods: Eight patients with confirmed larynx squamous cell carcinoma (SCC) and planned partial or total laryngectomy were included in this study in March 2020. Two head and neck surgeons and one pathologist were asked to classify carcinoma or healthy epithelium in a sample of 94 representative sequences (5.640 images), blinded to the histological results (H&E staining). Results: Healthy mucosa areas showed epithelium with cells of uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of SCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 80.1%, 72.3%, 87.9%, 85.7%, and 76.1%, respectively. A distinct transition between healthy appearing tissue and suspicious lesions could also be detected. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the larynx for evaluation and demarcation of cancer. If validated in further studies, CLE could eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Confocal laser endomicroscopy; Laryngeal cancer; Safe surgical margins

Feasibility of sentinel lymph node detection by near-infrared endoscopy in squamous cell carcinoma of the oral cavity: A pilot study - Sievert, Matti; Goncalves, Miguel; Eckstein, Markus; Iro, Heinrich; Koch, M. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: Near-Infrared (NIR) fluorescence imaging is a novel technique for intraoperative sentinel lymph node (SLN) identification. It has demonstrated promising results in several surgical specialties. The study aims to evaluate the feasibility of identifying the SLN by indocyanine green (ICG) enhanced NIR endoscopy in squamous cell carcinoma of the oral cavity (OCSCC). PATIENTS AND METHODS: Seven patients with (cT1-3 N0) OCSCC were included. We injected 1-1.25 ml of ICG (5 mg/ml) at four to five points around the primary. After the elevation of a platysma flap and posterior retraction of the sternocleidomastoid muscle, fluorescence images were taken via IMAGE1 STM NIR/ICG system to define the SLN(s). We sampled fluorescence marked SLN(s) stratified to lymph node levels, followed by level-specified elective neck dissection. RESULTS: The detection of at least one unilateral or bilateral SLN (range 1-5) was possible in every case. The fluorescence signal occurred, on average, 5.0 ± 2.2 minutes after injection. A total of 22 SLN could be identified. Among 331 histo-logically examined lymph nodes we could detect one micrometastasis, which was correctly defined as SLN (1/22). There were no false-negative findings. No adverse reactions to ICG occurred. CONCLUSIONS: Our first results are indicating the concept of SLN concerning OCSCC after the application of real-time NIR fluorescence endoscopy. However, this has to be verified by more extended studies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Indocyanine green; Near-infrared-imaging; Neck dissection; Oral cavity squamous cell carcinoma; Sentinel node biopsy

Free Latissimus Dorsi Myocutaneous Flap in a 6-Month-Old Child for Reconstruction of a Temporal Fossa Defect After Teratoma Resection - Fried, Frederik W.; Beier, Justus; Bohr, Christopher; Iro, Heinrich; Horch, Raymund E.; Arkudas, Andreas (Annals of Plastic Surgery, 2019)
Although free flap reconstruction has already gained widespread acceptance in pediatric patients, little is known about the outcome of free tissue transfer in head and neck reconstruction in pediatric patients. We present a case of a 6-month-old boy with a large volume deficit in the right temporal fossa after resection of a teratoma. This led to a large volume deficit with widely undermined skin margins. Therefore, we provided volume augmentation by microsurgical free latissimus dorsi myocutaneous flap transplantation. Intraoperative use of laser-assisted indocyanine green angiography indicated excellent flap perfusion. Postoperative magnetic resonance imaging showed adequate flap perfusion with no signs of flap necrosis. To our best knowledge, this case presents the youngest patient who underwent free flap transplantation in the head and neck region. Our case demonstrates that microvascular surgery can play an important role in particular cases in pediatric oncology, even in very young patients.
EVALuna2:35384

Frozen Section of Parotid Gland Tumours: The Head and Neck Pathologist as a Key Member of the Surgical Team - Mantsopoulos, Konstantinos; Bessas, Zacharias; Sievert, Matti; Müller-Hübner, Sarina Katrin Ursel; Koch, Michael; Agaimy, Abbas; Iro, Heinrich (Journal of Clinical Medicine, 2022)
Introduction: The aim of this study was to evaluate the impact of subspecialised head and neck versus general surgical pathologists on the reliability of the histopathologic evaluation during intraoperative consultation. Materials and Methods: The medical records of all patients who underwent a parotidectomy with frozen section between 2006 and 2021 were retrospectively evaluated. The frozen section was evaluated for sensitivity, specificity, accuracy, and predictive value. Assessment by two groups of pathologists (subspecialised head and neck versus general surgical pathologists) was compared, and the nature or types of misdiagnoses compared with final diagnoses on paraffin sections were analysed for the two groups. Results: Our study sample was made up of 669 cases. The mean age of patients was 57.7 years (range: 10–94 years). Of these, 490 patients had a benign lesion (73.2%), whereas 179 patients had a malignant lesion (26.8%). Frozen section had an overall accuracy of 97.6%, sensitivity for malignancy was 91.1%, specificity was 100%, PPV was 100%, and the NPV was 96.8%. The exact histologic subtype in the group of malignant tumours was correctly identified in FS in 89.4% of cases. A comparison of head and neck pathologists versus general surgical pathologists revealed a highly statistically significant difference concerning both overall detection of malignancy (p < 0.001) as well as correct identification of the histologic subtype (p < 0.001). Conclusion: Involvement of subspecialised head and neck pathologists in the intraoperative consultation for salivary gland tumours results in a gain of 19.8% more sensitivity, underlining the importance of specialisation in salivary gland pathology for the optimisation of frozen section quality.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Accuracy; Benign tumour; Frozen section; Head and neck cancer; Malignant tumour; Parotid gland; Predictive value; Sensitivity; Specificity

Full-Thickness Skin Grafts and Quilting Sutures for the Reconstruction of Internal Nasal Lining - Gostian, Antoniu Oreste; Balk, Matthias; Stegmann, Achim; Iro, Heinrich; Wurm, Jochen (Facial Plastic Surgery, 2020)
Restoration of the inner nasal lining is an essential factor in successful nasal reconstruction. Among various methods, free full-thickness skin grafting represents a readily available and feasible technique. A prerequisite for success is a secure and immobile fixation to the undersurface of the nourishing forehead flap. This retrospective study aims to evaluate the results of multiple quilting sutures to secure free full-thickness skin grafts for the reconstruction of the inner nasal lining in partial and extended nasal reconstruction. Between February 1, 2015, and December 31 2018, 16 patients underwent three-stage nasal reconstruction of all three layers using a forehead flap. All full-thickness free flaps were harvested from either the neck or inguinal area and fixated to the undersurface of the distal part of the forehead flap by multiple quilting sutures. All but one free skin grafts healed well (seven ♀; mean: 63 years; range: 52-81). Four patients developed minor complications that resolved completely through conservative treatment. One patient with a history of stroke, extensive nicotine abuse, and arterial hypertension developed flap necrosis that required two surgical revisions and ended up with a stenosis of the left nostril. The follow-up time averaged 18.4 months (range: 3-55 months). Multiple quilting sutures are an effective and feasible option to fixate full-thickness free skin grafts on the undersurface of the forehead flap for the reconstruction of the inner nasal lining. They are not associated with increased risks for necrosis and can be applied even to extended full-thickness nasal defects in selected cases.
CRIS-Team Scopus Importer:2020-06-30

Fusion of Preoperative MRI and Postoperative FD-CT for Direct Evaluation of Cochlear Implants: An Analysis at 1.5 T and 3 T - Eisenhut, Felix; Kleibe, Isabella; Hornung, Joachim; Iro, Heinrich; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Clinical Neuroradiology, 2019)
Aim: This study was carried out to evaluate the diagnostic value of merging preoperative magnetic resonance imaging (MRI) with postoperative flat-panel computed tomography (FD-CT) and compare it to standard postoperative FD-CT for assessment of cochlear implant (CI) insertion. Methods: The T2-weighted (T2w) constructive interference in steady state (CISS) data sets of preoperative 1.5 T and 3 T MRI scans of CI patients with both regular and adverse implant spiralization were co-registered with the corresponding postoperative FD-CT data sets using defined anatomic landmarks. These merged FD-CT/MRI volumes (CMV) were compared to the corresponding postoperative FD-CT MPRs in consensus reading with respect to qualitative, i.e. scala tympani spiralization, scala vestibuli spiralization, scalar translocation and quantitative, i.e. distance of the last electrode to the lateral cochlea wall (D1) distance of the 2nd/5th electrode to the basal cochlear wall (D2) and the transition point (TP) of the scalar translocation, parameters. Results: In total 30 patients (n 1.5T MRI = 18 patients; n 3T MRI = 12 patients) were included in the analysis. In all cases both CMVs and FD-CT MPRs were generated. Qualitative analysis of intracochlear CI position with CMVs (both 1.5 T and 3 T) and FD-CT was equivalent: In 20 patients the CI showed a regular implant spiralization, in 10 cases a scalar translocation was identified with both CMVs and FD-CT. Quantitative analysis showed a high level of congruency between CMVs (both 1.5 T and 3T) and FD-CT for fusion accuracy (D1: mean FD-CT D1 = 1.30 ± 0.7 mm; mean CMV D1 = 1.27 ± 0.77 mm, correlation r = 0.94, p < 0.0001; D2: mean FD-CT D2 = 1.17 ± 0.34 mm; mean CMV D2 = 1.10 ± 0.31 mm, correlation r = 0.89, p < 0.0001) and TP of the scalar translocation (mean FD-CT = 126.0 ± 59.25°, mean CMV = 117.0 ± 52.82°, correlation r = 0.95, p < 0.0001). Conclusion: The co-registration of preoperative 1.5 and 3 T MRI with postoperative FD-CT enables a direct evaluation of the position of a CI equivalent to the current standard FD-CT. Despite the fact that CMV provided no additional diagnostic value in this series, regardless whether preoperative 1.5 or 3 T MRI was used for co-registration, it might help to simplify postoperative CI diagnostics.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Cochlear implant; Flat panel computed tomography; Magnetic resonance imaging; Merging; Scalar translocation

Genomic aberrations of MDM2, MDM4, FGFR1 and FGFR3 are associated with poor outcome in patients with salivary gland cancer - Ach, Tobias; Schwarz-Furlan, Stephan; Ach, Stephanie; Agaimy, Abbas; Gerken, Michael; Rohrmeier, Christian; Zenk, Johannes; Iro, Heinrich; Brockhoff, Gero; Ettl, Tobias (Journal of Oral Pathology & Medicine, 2016)
Fibroblast growth factor receptor 1 and 3 (FGFR1, FGFR3) impact on tissue homoeostasis, embryonic development and carcinogenesis. Murine double minute protein 4 (MDM4) and mouse double minute 2 homologue (MDM2) are regulators of p53-protein and may be the origin of an apoptosis overpowering cascade. A collective of 266 carcinomas of salivary glands were investigated for MDM2, MDM4, FGFR1 and FGFR3 aberrations by fluorescence in situ hybridization (FISH). The results were matched with clinicopathological parameters and with expression of PTEN and p53. MDM2 gene amplification (n = 9) and chromosomal aberrations (trisomy, n = 47; high polysomy, n = 7) are linked to high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.001), advanced tumour size (P = 0.013) and stage (P < 0.001), gender (P = 0.002) and age (P = 0.001). MDM4 gene amplification (n = 19) and chromosomal aberrations (trisomy, n = 34; high polysomy, n = 31) are correlated to high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.008), advanced tumour size (P = 0.039), stage (P = 0.004) and loss of PTEN (P < 0.001). Only, high-grade malignancy (P < 0.001), lymph node metastasis (P = 0.036) and advanced tumour stage (P = 0.025) are associated with FGFR3 amplification (n = 1) or chromosomal aberrations (low polysomy, n = 61; high polysomy, n = 55) but not with MDM4 alterations. FGFR1 amplifications (n = 5) and chromosomal aberrations (trisomy, n = 38; high polysomy, n = 30) are associated with high-grade malignancy (P < 0.001), advanced tumour size (P = 0.026) and stage (P = 0.004), gender (P = 0.016) and age (P = 0.023). Aberrations of MDM2, MDM4, FGFR1 and FGFR3 correlate with aggressive tumour growth and nodal metastasis. MDM2 (P < 0.001), MDM4 (P = 0.005) and FGFR3 (P = 0.006) alterations are associated with worse overall survival of patients with salivary gland cancer.
EVALuna2:6776

Gibt es eine neue Kopfspeicheldrüse? – Eher nicht! - Guntinas-Lichius, Orlando; Ihrler, Stephan; Freesmeyer, Martin; Guehne, Falk; Kluge, Regine; Bräuer, Lars; Iro, Heinrich; Paulsen, Friedrich; Dietz, Andreas; Bechmann, Ingo (Laryngo-Rhino-Otologie, 2020)
In October 2020, the lay press, but also some medical journals and websites reported the putative discovery of a new salivary gland in the nasopharynx based on prostate-specific membrane antigen positron emission tomography computed tomography (PSMA-PET/CT) examinations. As an interdisciplinary group from the fields of anatomy, pathology, nuclear medicine and otorhinolaryngology, we come to the view that an accumulation of minor salivary glands has been described here. Minor salivary glands in the nasopharynx and in the peritubar region have been described at least since 1866. The current description in PSMA-PET/CT does not justify the definition of a new, independent salivary gland. The PSMA-PET/CT could, however, be suitable to better protect salivary glands in the nasopharynx when planning radiation therapy. This should be evaluated in clinical trials.
CRIS-Team Scopus Importer:2020-12-04

Going beyond extracapsular dissection in cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Traxdorf, Maximilian; Schapher, Mirco; Iro, Heinrich (Oral Oncology, 2019)
BACKGROUND: The aim of this study was to evaluate the potential for reducing surgical invasiveness in parotid cystadenolymphomas by means of capsular dissection based on the experience made in our department and on various aspects of these lesions gained from the relevant literature. METHODS: All patients treated for cystadenolymphomas with extracapsular or capsular dissection at a tertiary referral center between 2000 and 2017 were examined retrospectively. A literature review of various aspects and of different treatment strategies for this lesion was also performed. RESULTS: 629 patients were included in the study. 499 had solitary tumors (79.3%) and 130 had unilateral multicentric lesions (20.7%). 595 patients were managed by means of ED, while 34 patients underwent a CD. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 2.06% (13/629), all after extracapsular dissection, with a mean follow-up of 104.1 months. No statistical difference could be found between ED and CD in the overall occurrence rate of ipsilateral metachronous tumors or in the complication rate. No cases of a malignancy arising from a preexisting Warthin tumor could be detected in our study sample. CONCLUSION: A clear potential for reducing surgical invasiveness could be shown. A reliable imaging diagnosis, appropriate patient counseling and high compliance with close follow-up are the basic prerequisites for an acceptable outcome.
EVALuna2:35382

Hearing aid provision - can the limited obligation of statutory health insurance to provide indemnification only up to the reference price be successfully challenged in the social courts in cases of medical indication? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
EVALuna2:209866

Hearing restoration with cochlear implants after translabyrinthine vestibular schwannoma resection - Bohr, Christopher; Müller, Susanna; Hornung, Joachim; Hoppe, Ulrich; Iro, Heinrich (HNO, 2017)
BACKGROUND: Hearing restoration after translabyrinthine vestibular schwannoma resection is a challenge. Because the cochlea can begin to ossify a few months after cochlear or labyrinthine injury, the time interval for cochlear implant surgery is limited. To avoid complete ossification and to prolong the time interval until cochlear implantation, it is possible to insert a placeholder (depth gauge) into the cochlea and perform the cochlear implant surgery at a later time point (two-stage approach). OBJECTIVE: The aim of this retrospective case series was to present the outcomes after restoration of hearing with cochlea implants in six patients and to evaluate the use of the depth gauge in practice. METHODS: The hearing outcome of all patients with (n = 3) and without (n = 3) insertion of a depth gauge was measured with the Freiburg monosyllabic test without background noise at 65 dB. The first measurement was performed prior to the translabyrinthine vestibular schwannoma resection, the last measurement was performed up to 48 months after cochlear implantation. RESULTS: All 6 patients reached 22.5 ± 36.57% prior to vestibular schwannoma resection and 41.3 ± 26% 12 months after cochlear implantation. The understanding values of the patients with a depth gauge were 25.8 ± 16% after 12 months which is below the values of the other patients with 56.6 ± 25.0%. No severe intraoperative or postoperative complications occurred in any patient. CONCLUSION: The two-stage approach for cochlear implantation with depth gauge insertion following labrynthine incision and intact nerve appears to represent a very promising and safe variation for hearing restoration. Intensified research on this approach seems to be justified and necessary.
EVALuna2:33160

High-grade histology as predictor of early distant metastases and decreased disease-free survival in salivary gland cancer irrespective of tumor subtype - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Uter, Wolfgang; Neukam, Friedrich Wilhelm; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
The purpose of this study was to evaluate risk factors that influence overall survival (OS)/disease-free survival (DFS)/locoregional recurrence-free survival (LRFS), and distant metastases-free survival (DMFS) in patients with high-risk primary salivary gland carcinoma who underwent surgery and postoperative (chemo)radiotherapy with curative intention.We reviewed data of 63 patients with high-risk primary salivary gland carcinoma in a retrospective single-center audit.At a median follow-up of 31 months (range, 5-145 months), cumulative OS and DFS were 91.7%, 77.6%, and 62.9%, and 82.1%, 65.6%, and 57.7%, respectively, after 1, 2, and 5 years. LRFS and DMFS were 92%, 86%, and 86%, and 83.4%, 70.4%, and 62.3% after 1, 2, and 5 years, respectively. Of all patient-related, tumor-related, and treatment-related factors, high-grade histology (G3) was the only factor in univariate and multivariate analysis that was predictive for a shorter DMFS (low/intermediate vs high-grade: 100%, 100%, and 89.4% vs 72.9%, 54.3%, and 42.8% after 1, 2, and 5 years, respectively) and a shorter DFS (low/intermediate vs high-grade: 100%, 90%, and 84.4% vs 71.2%, 50.1%, and 39.4% after 1, 2, and 5 years, respectively) and OS (low/intermediate vs high-grade: 100%, 100%, and 86.5% vs 86.5%, 63.2%, and 46.5% after 1, 2, and 5 years, respectively).High-grade tumor histology is a highly significant predictor of a shorter DMFS, OS, and DFS in salivary gland carcinoma, irrespective of histological subtype. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2041-E2048, 2016.
EVALuna2:5539

High-grade salivary gland cancer: is surgery followed by radiotherapy an adequate treatment to reach tumor control? Results from a tertiary referral centre focussing on incidence and management of distant metastases - Freitag, Viola; Lettmaier, Sebastian; Semrau, Sabine; Hecht, Markus; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Traxdorf, Maximilian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer; Haderlein, Marlen (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: Salivary Gland cancer (SGC) is a rare and heterogenous group of tumors. Standard therapeutic options achieve high local but poor distant control rates, especially in high-grade SGC. The aim of this monocentric study was to evaluate patterns of recurrence and its treatment options (local ablative vs. systemic) in a homogenously treated patient population with high-grade SGC after surgery and radio(chemo)therapy. Methods: Monocentric, retrospective study of patients with newly diagnosed high-grade salivary gland cancer. We retrospectively reviewed clinical reports from 69 patients with high-grade salivary gland cancer in a single-center audit. Survival rates were calculated using the Kaplan–Meier method and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox regression analysis). Results: The median time of follow-up was 31 months. After 5 years, the cumulative overall survival was 65.2%, cumulative incidence of local recurrence was 7.2%, whereas the cumulative incidence of distant metastases was 43.5% after 5 years. 30 of 69 patients developed distant metastases during the time of follow-up, especially patients with adenoid cystic carcinoma, salivary duct carcinoma, adenocarcinoma NOS and acinic cell carcinoma with high-grade transformation. The most common type of therapy therefore was chemotherapy (50%). 85.7% of patients with local ablative therapy of distant metastases show disease progression during follow-up afterwards. Conclusion: With surgery and radio-chemotherapy, a high rate of loco-regional control is reached, but over 40% of patients develop distant metastases in the further follow-up which usually present a diffuse pattern involving in a diffuse metastases. Therefore, in the future, intensified interdisciplinary combination therapies even in the first-line treatment in certain subtypes of high-grade SGC should be investigated.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Chemotherapy; Distant metastases; High-grade; Radiotherapy; Salivary gland cancer

Highlights from the 2021 ASCO and ESMO annual meetings on radiotherapy of head and neck cancer Highlights der ASCO- und ESMO-Jahrestagungen 2021 zur Strahlentherapie von Kopf-Hals-Tumoren - Hecht, Markus; von der Grün, Jens; Semrau, Sabine; Müller, Susanna; Weissmann, Thomas; Gaipl, Udo; Iro, Heinrich; Fietkau, Rainer; Gostian, Antoniu-Oreste (HNO, 2022)
At this year’s annual meetings of the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO), several studies on radiotherapy of locally advanced head and neck cancer were presented. For the indication of definitive radiochemotherapy, particularly the administration of immune checkpoint inhibitors concomitant to radiotherapy was investigated. In the phase III GORTEC-REACH trial, combined inhibition of epidermal growth factor receptor (EGFR) and programmed death-ligand (PD-L1) concomitant to radiotherapy of locally advanced head and neck cancer was inferior to platinum-based chemoradiotherapy. However, this therapeutic approach may be more efficient than radiotherapy with simultaneous EGFR inhibition alone. The concept of the phase II CheckRad-CD8 trial with induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy after appropriate patient selection also proved to be highly efficient. In initial phase II trials, dose de-escalation of radiotherapy seems feasible for HPV-positive oropharyngeal cancer after appropriate patient selection both postoperatively (ECOG-ACRIN E3311 trial) and after induction therapy (Optima II trial). However, dose de-escalation should currently not be performed outside of clinical trials. In addition, first studies indicate a benefit of functional imaging (diffusion-weighted magnetic resonance imaging [MRI] or F‑fluoromisonidazole positron-emission tomography [FMISO-PET]) to establish personalized dose concepts in radiotherapy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Chemoradiotherapy; Head and neck squamous cell carcinoma; Human papillomavirus; Immunotherapy; Oropharyngeal cancer

High locoregional Control Rates after Radio (chemo) Therapy in anaplastic Thyroid Carcinoma - a monocentric Analysis - Schmied, M.; Semrau, Sabine; Hecht, Markus; Lettmaier, Sebastian; Mantsopoulos, K.; Traxdorf, Maximilian; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

High-speed flat-detector computed tomography for temporal bone imaging and postoperative control of cochlear implants - Eisenhut, Felix; Manhart, Michael; Thimsen, Vivian; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Neuroradiology, 2022)
Purpose: Flat-detector computed tomography (FD-CT) is the standard for cochlear implant (CI) imaging. FD-CT systems differ in technical characteristics. Our aim was an evaluation of two different FD-CT generations with different protocols and hardware regarding image quality, radiation dose, and scan time. Methods: Two temporal bone specimens (− / + CI = TB0/TB1) were scanned using three different scanners: two FD-CT systems with different scanning protocols (standard FD-CT: 20 s 70 kV, 20 s 109 kV; high-speed FD-CT [HS-FD-CT]: 7 s 109 kV, 9 s 109 kV, 14 s 72 kV) and MS-CT (5 s 120 kV). Acquired datasets were evaluated in consensus reading regarding qualitative and quantitative parameters: addressing CI- and cochlea-specific parameters, cochlea delineation, lamina spiralis ossea visibility, distinction of single CI electrodes, determination of intracochlear implant position, stapes delineation, and mastoidal septation were assessed. Addressing protocol-specific parameters, radiation dose (dose-length-product/DLP), and scan time were assessed. Results: Two HS-FD-CT protocols (14 s/9 s) provide higher or equivalent diagnostic information regarding CI- and cochlea-specific parameters compared to both standard FD-CT protocols. The fastest HS-FD-CT protocol (7 s)—providing inferior diagnostic information compared to all other FD-CT protocols—still exceeds MS-CT. The highest DLP was recorded for the 14 s HS-FD-CT protocol (TB1 = 956 mGycm); the lowest DLPs were recorded for the 7 s HS-FD-CT protocol (TB0 = 188 mGycm) and for MS-CT (TB0 = 138 mGycm), respectively. HS-FD-CT allows a significant reduction of scan time compared to standard FD-CT. Conclusion: High-speed FD-CT improves visualization of temporal bone anatomy and postoperative assessment of CIs by combining excellent image quality, fast scan time, and reasonable radiation exposure.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Anatomy; Cochlear implant; Flat-detector computed tomography; Postoperative control; Temporal bone

Histopathological comparison of pleomorphic adenomas of the parotid and submandibular gland - Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Ann Kristin; Müller, Susanna; Koch, Michael; Schapher, Mirco; Agaimy, Abbas; Iro, Heinrich (Oral Diseases, 2021)
Objective: The aim of this study was to investigate and compare the histopathological findings in pleomorphic adenomas (PA) of the parotid and submandibular gland with emphasis on the histological subtype and capsular characteristics. Materials and Methods: The histopathological specimens of all patients with PAs of the parotid and submandibular gland between 2000 and 2020 were re-examined by an experienced head and neck pathologist. Patients without representative slides allowing evaluation of the whole periphery of the PA were excluded from our study sample. Results: Nine hundred and thirty-four patients formed our study sample (327 men, 607 women, male-to-female ratio: 0.53:1). Eight hundred and forty-four cases had a PA in the parotid gland and the remaining 90 in the submandibular gland. Our comparative analysis showed that submandibular PAs are characterized by the consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia and satellite nodules, and a low proportion of the high-risk myxoid subtype. Conclusion: Our study highlights significant differences between PAs of the parotid and submandibular glands in their histopathological characteristics. Their differences likely underlie the favorable surgical outcome observed in PAs of the submandibular glands and may explain the propensity of PAs of the parotid glands for local recurrences.
CRIS-Team Scopus Importer:2021-04-16
Keywords: capsule; parotid gland; pleomorphic adenoma; satellite nodules; submandibular gland

Histopathology of Parotid Pleomorphic Adenomas: A "Pleomorphic Approach" to a Demanding Lesion - Mantsopoulos, Konstantinos; Thimsen, Vivian; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Sievert, Matti; Iro, Ann-Kristin; Agaimy, Abbas; Iro, Heinrich (Laryngoscope, 2021)
Objectives/Hypothesis The aim of this study was to identify potential associations between epidemiologic, morphologic, and histopathologic features in pleomorphic adenomas (PAs) of the parotid gland in order to extract information about the natural course and biologic behavior of these lesions on the basis of a single-center series of 845 cases within a period of 15 years. Study Design Retrospective study in a tertiary academic center. Methods For this study, an experienced head and neck pathologist critically re-evaluated the histological slides of the pathological specimens of all patients who underwent a parotidectomy for PA of the parotid gland between 2006 and 2020. Results A total of 845 cases made up our study sample. Our analysis showed a statistically significant association of the histologic subtype with younger age (P = .001) and maximal diameter (P = .044), with the hypocellular type being encountered more often in younger patients and in smaller lesions. The same subtype was significantly associated with an incomplete capsule (P = .001), pseudopodia (P = .006), and satellite nodules (P = .001). An incomplete capsule was associated with the presence of pseudopodia (P = .001) and satellite nodules (P = .001). Conclusion It seems that various histologic subtypes have different capsule-producing properties. Apparently, over the course of time, tumor material builds a finger-like projection still inside the capsule, separates itself from the parenchyma with fibrous tissue still remaining enclosed within the capsule (pseudopodium), slowly penetrates the capsule (incomplete capsule), and leaves the main lesion taking a part of the capsule with it (satellite nodules). Laryngoscope, 2021
CRIS-Team WoS Importer:2021-07-16

HMGA2-WIF1 Rearrangements Characterize a Distinctive Subset of Salivary Pleomorphic Adenomas With Prominent Trabecular (Canalicular Adenoma-like) Morphology - Agaimy, Abbas; Ihrler, Stephan; Baneckova, Martina; Martineau, Valerie Costes; Mantsopoulos, Konstantinos; Hartmann, Arndt; Iro, Heinrich; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2022)
Most of salivary gland neoplasms (benign and malignant) are characterized by recurrent gene fusions. Pleomorphic adenoma (PA), the most frequent salivary gland tumor, is driven by chromosomal rearrangements involving PLAG1 mapped to 8q12 and HMGA2 mapped to 12q13-15 in most cases. Multiple fusion partners have been identified including CTNNB1, FGFR1, LIFR, CHCHD7 and TCEA for PLAG1 fusions and NFIB, WIF1 and FHIT for HMGA2 fusions. To date, no data exist on the morphology of the few reported HMGA2-WIF1-rearranged PAs. We present 28 major salivary gland adenomas displaying distinctive trabecular and canalicular morphology associated with recurrent genotype. Patients were 15 females and 13 males aged 43 to 87 (median: 65). All tumors originated from the parotid. Their size range was 1 to 4 cm (mean: 2.3). Histologically, all tumors showed elongated or columnar cells arranged into bilayered to multilayered communicating and branching strands and trabeculae in a manner similar to canalicular adenoma of minor salivary glands or trabecular myoepithelioma with variable solid confluent intercalated duct-like areas. Fifteen tumors were exclusively canalicular/trabecular while 13 had intermingled or well-demarcated conventional (chondromyxoid) PA component comprising 5 to >50% of the tumor. The monomorphic areas expressed uniformly CK7 (28/28), vimentin (21/21), S100 (24/24), SOX10 (16/17) and variably p63 (8/21) and mammaglobin (6/16) but were negative with p40 (0/24), smooth muscle actin (0/24) and MUC4 (0/16). Targeted RNA sequencing revealed HMGA2 fusions in 14/16 (87%) assessable cases. Fusion partner was WIF1 (12), RPSAP52 (1) and HELB (1). Separate testing of the 2 components in 1 hybrid tumor showed same HMGA2/WIF1 fusion. HMGA2 immunohistochemistry was homogeneously positive in all cases including the 2 fusion-negative cases. A control cohort of 12 genuine canalicular adenomas revealed no HMGA2 fusions (0/4) and lacked HMGA2 immunoreactivity (0/12). This study highlights a distinctive variant in the spectrum of PA characterized by prominent trabecular and canalicular adenoma-like morphology. Our data confirm that canalicular adenomas in major salivary glands (either monomorphic or part of hybrid tumors) are distinct from canalicular adenoma of minor salivary glands. Their uniform genotype irrespective of presence or absence of a conventional PA component argues for classifying those tumors lacking a conventional PA component as "monomorphic variants of PA" rather than canalicular/basal cell adenomas, intercalated duct adenoma, trabecular myoepithelioma or true hybrid tumors.
CRIS-Team WoS Importer:2022-01-21

Hörgeräteversorgung – Kann die Begrenzung der Leistungspflicht der Krankenkassen durch Festbeträge bei medizinischer Indikation erfolgreich vor den Sozialgerichten angefochten werden? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
CRIS-Team Scopus Importer:2019-10-22

Hydroxyapatite bone cement in the reconstruction of defects of the long process of the incus: Personal experience and literature review - Mantsopoulos, Konstantinos; Thimsen, Vivian; Wohlleben, Felix; Sievert, Matti; Müller, Sarina Katrin; Goncalves, Miguel; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2021)
Objective: Erosion of the long process of the incus is the most common ossicular chain pathology occurring in the course of chronic middle ear disease. The aim of this study was to evaluate our experience in the reconstruction of short-length defects of the long process of the incus using hydroxyapatite bone cement over a period of 15 years. Methods: The medical records of all patients treated with hydroxyapatite bone cement for an isolated short-length erosion of the long process of the incus or the lenticular process at an academic tertiary referral center between 2005 and 2019 were studied retrospectively. Results: 48 patients made up our study sample (19 men, 29 women). The mean age at the time of surgery was 38.1 years. The mean preoperative air-bone gap (ABG) was 21.36 dB. The mean postoperative ABG was 15.89 dB within 8 weeks of surgery and 11.81 dB at least 6 months after surgery. The postoperative ABG had significantly improved compared to preoperative ABG values at both the short- and middle-term follow-up (p < 0.001 for both). An ABG ≤ 20 dB was achieved in 68% in the short term and 83% in the middle term. The mean ABG in the long term (< 12 months) was 11.1 dB. Conclusion: Restoration of the anatomic and functional continuity of the ossicular chain using hydroxyapatite cement in defects of the long process of the incus seems to warrant a satisfactory audiologic outcome in the majority of cases.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Bone cement; Hydroxyapatite; Incus; Long process; Ossicular chain

Identification of anatomic risk factors for scalar translocation in cochlear implant patients - Eisenhut, Felix; Lang, Stefan; Hölter, Philip; Wiesmüller, Marco; Uder, Michael; Iro, Heinrich; Dörfler, Arnd; Hornung, Joachim; Taha, Lava (Zeitschrift für Medizinische Physik, 2021)
Aim: Microanatomical evaluation of cochlear implant (CI) patients to identify anatomical risk factors for a scalar translocation. Methods: CI patients with both a regular scala tympani spiralization (group A) and a scalar translocation (group B) were identified via postoperative flat-detector computed tomography (FD-CT). Then, the corresponding preoperative multislice computed tomography (MS-CT) and postoperative FD-CT datasets were assessed: First, the cochleae were separated in 6 segments of 45° each. Next, quantitative (cochlea height, length, depth, cochlear duct diameter [CD] per segment; percentual tapering of the CD per segment named cochlear geometry index [CGI]) and qualitative (identifiability of the CI model; CI-integrity; intracochlear array position) parameters were evaluated and compared for both groups. Receiver-operating-characteristics (ROC) analysis was performed for the CGI. Results: In total, 40 preoperative MS-CT and postoperative FD-CT datasets (nA = 20; nB = 20) were analysed. Model “CI 512” was successfully identified and CI-integrity has been confirmed in all cases. Quantitative analysis showed a significant difference of both the CD at 0° (CDA 0°= 2.06 ± 0.23 mm; CDB 0°= 2.19 ± 0.18 mm; p0°= 0.04) and the CGI of the first segment (CGIA 0° -45°= 18.87 ± 6.04%; CGIB 0°-45°= 28.89 ± 8.58%; p0°-45°= 0.0001). For all other 5 cochlear segments there was no significant difference of CD and CGI; there was no significant difference of external cochlea diameters. The area under the curve (AUC) of the CGI0-45° was 0.864 with 24.50° as the optimal cut-off value to discriminate patients with a scala tympani spiralization and a scalar translocation. CGI0-45° of > 24.50° allowed the correct identification of 85% of patients with a scalar translocation. Conclusion: CI insertion trauma is associated with a significantly higher narrowing of the proximal basal cochlea turn (BCT). The CGI as percentual tapering of the BCT turned out as reliable, clinically applicable parameter for identification of patients with an increased risk for a scalar translocation.
CRIS-Team Scopus Importer:2021-03-12
Keywords: anatomical parameters; Cochlear implant; flat-detector computed tomography; insertion trauma; scalar translocation

IMP3 and p16 expression in squamous cell carcinoma of the head and neck: A comparative immunohistochemical analysis - Riener, Marc-Oliver; Hoegel, Josef; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Oncology Letters, 2017)
Expression of p16 has been established as a good surrogate marker for high-risk human papillomavirus (HPV) infection in oropharyngeal squamous cell carcinoma (OPSCC) patients, and it has been associated with an improved prognosis, irrespective of the actual HPV status. Conversely, the human insulin-like growth factor II mRNA binding protein 3 (IMP3) has been related to aggressiveness in several types of tumors. The aim of the present study was to investigate and compare p16 and IMP3 as markers of favorable and unfavorable behavior, respectively, in head and neck SCC (HNSCC), with particular reference to the HPV status. Both markers were analyzed by immunohistochemical analysis of 156 HNSCC samples originating from the oropharynx (n=81), oral cavity (n=44), larynx (n=15), hypopharynx (n=10) and nasopharynx (n=6). The HPV status was examined in a randomly selected representative subcohort (n=38) using polymerase chain reaction. Of the 156 HNSCC samples, 81 (51.9%) and 54 (34.6%) were positive for IMP3 and p16, respectively. IMP3 expression (P=0.022), p16 expression (P<0.001) and the combination of these markers (P<0.001) were significantly associated with tumor site. In particular, 69/81 (85%) OPSCC samples were positive for either one or both markers compared with 36/75 (48%) SCC samples from other sites. p16 expression was significantly associated with HPV infection (P=0.017) and a trend towards a negative association between IMP3 expression and HPV infection was observed (P=0.053). The results of the present study suggested that IMP3 and p16 are more frequently expressed in OPSCC compared with other HNSCCs. The prognostic impact of IMP3 on OPSCC remains to be investigated in a larger series with an extended follow-up period.
EVALuna2:6894

Impact of Cancer Localization on Symptom Burden and Quality of Life in Head and Neck Cancers: A Comparative Study - Balk, Matthias; Rak, Atina; Rupp, Robin; Sievert, Matti; Müller-Hübner, Sarina Katrin Ursel; Koch, Michael; Iro, Heinrich; Gostian, Magdalena; Putz, Florian; Weissmann, Thomas; Allner, Moritz; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Background: Head and neck cancer (HNC) is a critical concern in oncology, with notable disparities in survival rates. While the long-term symptom burden in HNC survivors and its impact on quality of life (QoL) has been explored, there is limited understanding of the influence of cancer localizations on these aspects. This study aims to elucidate the role of cancer localizations in shaping long-term outcomes in HNC patients. Methods: A cross-sectional study was conducted at the University Hospital Erlangen’s Department of Otolaryngology, exploring the impact of cancer localization on symptom burden and QoL in 138 HNC patients using the University of Washington Quality of Life Questionnaire Version 4. Results: In our study of HNC patients, we investigated symptom burden across different cancer localizations, including oral cavity, oropharyngeal, hypopharyngeal, laryngeal, and cancer of unknown primary (CUP). While we found no significant variations in parameters such as pain, appearance, and activity, notable differences emerged in swallowing, speech, and salivation. Patients with oral cavity and laryngeal carcinomas had significantly higher swallowing and salivation scores compared to those with oropharyngeal carcinoma and CUP, while speech-related symptoms were lower for oral cavity and laryngeal carcinoma patients. Importantly, these symptom differences did not significantly impact health-related and overall QoL. These findings emphasize the nuanced interplay between symptomatology and QoL in different HNC cancer localizations. Conclusion: The research highlights significant disparities in post-treatment symptoms across different HNC localizations and underscores the need for personalized treatment and management strategies to address unique challenges associated with each HNC type, ultimately aiming to enhance post-treatment QoL.
CRIS-Team Scopus Importer:2024-11-08
Keywords: advanced-stage cancer; cancer; disease stage; early-stage cancer; follow-up; head and neck cancer; individualized care; patient-reported outcome; physical symptoms; psychological symptoms; quality of life; survivorship; symptom burden

Impact of delayed adjuvant therapy after surgery in p16 positive oropharyngeal cancer: a retrospective analysis - Sievert, Matti; Goncalves, Miguel; Müller, Sarina Katrin; Hecht, M.; Pflaum, A.; Grundtner, P.; Iro, H.; Gostian, A. O.; Iro, Heinrich (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: This study aimed to clarify the impact of delayed adjuvant therapy on the outcome of HPV associated oropharyngeal squamous cell carcinoma (HPV-OPSCC). PATIENTS AND METHODS: A total of 157 patients with HPV-OPSCC treated by surgery and adjuvant radiotherapy or chemoradiation therapy were analyzed retrospectively. We divided participants into two groups implementing adjuvant therapy within or after 50 days. Primary endpoints were the rates of locoregional recurrence and distant metastases, overall survival, and disease-specific survival. RESULTS: Adjuvant treatment began within 50 days (average: 38.8 days) in 79 cases compared to 78 cases after 50 days (average: 71.5 days). Five-year overall survival was 85.7% and 87.4% (p=0.588), the rates of local and regional recurrence were 3.8% and 6.4% (p=0.455) and of distant metastases 5.1% and 9% (p=0.369) implementing adjuvant treatment within or later than 50 days, respectively. CONCLUSIONS: These results suggest that adjuvant therapy initiated later than seven weeks after primary ablative surgery may still be effective HPV-OPSCC.
CRIS-Team Scopus Importer:2020-03-06

Impact of intraepithelial capillary loops and atypical vessels in confocal laser endomicroscopy for the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma - Sievert, Matti; Eckstein, Markus; Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Stelzle, Florian; Aubreville, Marc; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose Confocal laser endomicroscopy (CLE) allows surface imaging of the laryngeal and pharyngeal mucosa in vivo at a thousand-fold magnification. This study aims to compare irregular blood vessels and intraepithelial capillary loops in healthy mucosa and squamous cell carcinoma (SCC) via CLE.
CRIS-Team WoS Importer:2021-07-23

Impact of postoperative radiotherapy and HER2/new overexpression in salivary duct carcinoma : A monocentric clinicopathologic analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Erber, Ramona; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
Retrospective Investigation of the prognostic relevance of clinicopathologic parameters in patients with salivary duct carcinoma (SDC).An experienced pathologist reviewed 67 patients with de novo SDC or SDC ex pleomorphic adenoma. Paraffin-embedded tumor samples were examined by immunohistochemistry for expression of HER2/neu, androgen (AR), progesterone (PR), estrogen (ER), epidermal growth factor (EGFR) and programmed death ligand 1 (PD-L1-R) receptor. In 45 patients who had cM0 and follow-up data available, survival rates were calculated (Kaplan-Meier method) and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox-regression analysis).Overexpression of HER2/neu, AR, ER, PR, EGFR, PD-L1-R was found in 25.4%, 84%, 0%, 0%, 17.9%, 16.4% of patients. Overall (OS), disease-free (DFS), distant-metastases-free survival (DMFS) and locoregional control (LRC) were 92.3/72.4/56.9%, 78.2/58.1/58.1%, 85.4/65.2/65.2% and 89.7/81.9/81.9% after 1/3/5 years (medial follow-up 26 months). In univariate analysis a positive resection margin (p = 0.008) and no postoperative radiotherapy (p = 0.001) predict an increased locoregional recurrence rate. In multivariate analysis only postoperative radiotherapy is statistically significant (p = 0.004). Presence of lymph node metastases, a lymph node density >4 and HER2/neu overexpression predict decreased DFS and DMFS. In multivariate HER2/neu overexpression was the only significant predictor for reduced DFS (p = 0.04) and DMFS (p = 0.02).Postoperative radiotherapy is the only significant predictor for LRC. HER2/neu receptor expression is an independent prognostic factor for decreased DFS and DMFS in patients with SDC. In addition to radio(chemo)therapy, intensified first-line treatment regimens should also be evaluated in the future.
EVALuna2:6895

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Improved Postoperative Facial Nerve and Hearing Function in Retrosigmoid Vestibular Schwannoma Surgery Significantly Associated with Semisitting Position - Roessler, Karl; Krawagna, Maximilian; Bischoff, Barbara; Rampp, Stefan; Ganslandt, Oliver Thomas; Iro, Heinrich; Schmitt, Hubert; Buchfelder, Michael (World Neurosurgery, 2016)
The pros and cons of semisitting positioning (SSP) versus lateral, horizontal positioning (LP) during retrosigmoid vestibular schwannoma (VS) surgery, especially concerning postoperative cranial nerve and brain stem preservation, are under continuous discussion.In a single-center retrospective cohort study, 30 VSs operated on in SSP compared with 30 operated on in LP with comparable demography were analyzed. During SSP surgery, transesophageal echocardiographic monitoring for venous air embolism was used continuously. Electrophysiologic cranial nerve monitoring was used in both groups.Length of surgery was significantly different between both groups: 183 minutes mean in SSP surgery versus 365 minutes mean in LP surgery (P = 0.0001). Postoperative rates of facial palsy and hearing loss were also significantly different. Six months postoperatively, 63% had normal facial nerve function after SSP surgery, whereas in LP surgery, 40% had no facial palsy (P = 0.02). Hearing preservation rate was also significantly different: 44% in SSP surgery compared with 14% in LP surgery who had preserved hearing (P = 0.006). Because of cerebrospinal fluid leaks, there were 3 operative revisions in the LP group (10%) and 1 (3.3%) in the SSP group. A clinically insignificant venous air embolism rate was found in 3.3% of patients (1/30) during SSP surgery. The neurologic outcome after 6 months was 1.2 on the Rankin Scale in the LP group and 1.0 in the SSP group, with zero mortality.SSP compared with LP surgery was associated with significantly shorter operation time and better facial and cochlear nerve function in VS surgery postoperatively, without differences in complication rate
EVALuna2:16715

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias Günther; Brunner, Thomas B.; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Inflamed benign tumors of the parotid gland: Diagnostic pitfalls from a potentially misleading entity - Mantsopoulos, Konstantinos; Psychogios, Georgios; Agaimy, Abbas; Künzel, Julian; Zenk, Johannes; Iro, Heinrich; Bohr, Christopher (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2015)
The purpose of this study was to evaluate our experience in the diagnostic approach to inflamed benign tumors of the parotid gland at a single tertiary center.A retrospective evaluation was carried out for all patients with signs of inflammation in the parotid gland on the ground of a benign parotid tumor, as confirmed by permanent histology.Sixteen patients were detected for our study. Histopathologic examination confirmed cystadenolymphoma in 11 cases (with metaplastic changes in 2 cases), 2 pleomorphic adenomas, 2 monomorphic adenomas, and 1 oncocytic cystadenoma. Diverse clinical signs (inflammation signs, facial palsy), ultrasound and MRI findings (poorly defined lesion margins), and the presence of squamous metaplastic changes on cytology often raised the suspicion of parotid malignancy or abscess.In most cases, a high suspicion index combined with close monitoring of the patient may allow prompt and successful diagnosis and therapy. © 2014 Wiley Periodicals, Inc. Head Neck 37: 23-29, 2015.
EVALuna2:6639

Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer - Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al. (Acta Oto-Laryngologica, 2020)
Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients (n = 108 p16–, n = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi2(two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi2(two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.
CRIS-Team Scopus Importer:2020-11-06
Keywords: de-escalation; HPV; Oropharyngeal cancer; p16; radiochemotherapy

Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Zenk, Johannes; Bozzato, Alessandro; Kuenzel, Julian; Zengel, Pamela; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
Purpose The aim of this study was to assess the interrater reliability of ultrasound for diagnosing sialolithiasis. Materials and Methods A total of 100 consecutive patients with signs of obstructive sialadenopathy were evaluated. The patients all underwent ultrasound examinations in a standardized manner conducted by one specialist with extensive experience in the management of salivary gland disorders and proficiency in head and neck ultrasonography. The video recordings were sent to six colleagues with comparable experience without providing any further information about the patients' medical history and physical examination. Results The overall agreement between the seven observers was substantial, with a κ of 0.765 for the 100 cases and a percentage agreement level of 88.29 ± 3.01 % (range: 83-94 %). The range of agreement on this video set for observer pairs varied from substantial to almost perfect agreement (0.663 to 0.878). Among the few false-negative findings (5.4 %), 71.8 % were due to distal sialolithiasis. Two-thirds of the false-positive findings (3.7 %) were due to fibrotic stenosis. Conclusion The study confirmed the diagnostic value of ultrasound in sialolithiasis and demonstrated a very high level of interrater agreement, even in the absence of additional clinical patient information, thus further underscoring the importance of ultrasound as the examination of first choice in sialolithiasis.
CRIS-Team Scopus Importer:2019-08-16
Keywords: interrater; parotid; sialolithiasis; submandibular; ultrasound

Intraductal Fragmentation in Sialolithiasis Using Pneumatic Lithotripsy: Initial Experience and Results - Koch, Michael; Schapher, Mirco; Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2021)
Objective: To report initial experience in using a pneumatic lithotripter to treat salivary stones. Study Design: Level IV retrospective study. Setting: University hospital and tertiary referral center. Methods: A pneumatic lithotripter was used to treat salivary stones after these were diagnosed. Probes with diameters of 0.7 mm were used. Total fragmentation was intended in all stones. Stone fragments were removed using several instruments in serial sialendoscopies to achieve complete stone clearance. Results: A total of 62 patients with 77 stones were treated. Forty-three submandibular stones were treated in 34 patients, and 34 parotid stones were treated in 28 patients. An operating pressure of 2.5 bar and a single frequency mode were used. Complete fragmentation was achieved in all but one of the treated stones in both glands (98.7%). Among the patients, 90.32% became stone free and 100% symptom free. Multiple stones were treated in 24.19% of the patients, and multimodal therapy was also carried out in 24.19%. All of the glands were preserved. Conclusions: The pneumatic lithotripter proved to be effective in the treatment of sialolithiasis. Stone size, location, and the gland involved were important clinical factors. The device was sufficient to achieve success without any increased risk for complications in the patients or damage to the sialendoscopes.
CRIS-Team Scopus Importer:2021-10-22
Keywords: intraductal lithotripsy; pneumatic lithotripsy; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal Lithotripsy in Sialolithiasis Using the Calculase III™ Ho:YAG Laser: First Experiences - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Iro, Heinrich (Lasers in Surgery and Medicine, 2020)
Background and Objectives: To report the first experiences with a newly available Ho:YAG laser system for the treatment of salivary stones. Study Design/Materials and Methods: A retrospective study in a tertiary referral center was conducted. Patients diagnosed with sialolithiasis were treated in Erlangen using the Calculase III™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany). Preset parameters had a frequency of 4 Hz and energy of 0.8–1.2 J, resulting in 3.2–4.8 W. Following total fragmentation, one to two serial sialendoscopies were performed to achieve complete fragment clearance. Results: A total of 55 stones in 49 patients were treated; 17 stones in 15 submandibular glands and 38 in 34 parotids. In total, 61 laser lithotripsies (range 1–3 per stone) were performed using various modes (long, short, and burst) and with preset parameters of 4 Hz and energy of 0.8–1.2 J, resulting in effective power of 3.2–4.8 W. Complete fragmentation was achieved in all the accessible stones. Sialendoscopes, fibers, or the mode used had no significant influence on success rates. A multimodal therapy concept was employed to treat stones in 12.24% of the cases; 95.92% of the patients were ultimately stone-free, and all became symptom-free. All glands were preserved. Conclusions: The new Calculase III™ Ho:YAG laser was effective in the treatment of sialolithiasis with no increased risk of complications in the patients or damage to the sialendoscopes. Clinical factors such as the type of gland involved, or the location and size of stones had a greater impact on success rates than the technical or preset parameters. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.
CRIS-Team Scopus Importer:2020-10-09
Keywords: intraductal lithotripsy; laser; salivary gland; sialendoscopy; sialolithiasis; treatment

Intraductal lithotripsy in sialolithiasis with two different Ho:YAG lasers: presetting parameters, effectiveness, success rates. - Koch, Matthias; Hung, S. H.; Su, C. H.; Lee, K. S.; Iro, Heinrich; Mantsopoulos, Konstantinos (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: To compare two different Ho:YAG laser systems in relation to the preset parameters and their effectiveness for intraductal fragmentation of the salivary stones. PATIENTS AND METHODS: We made a retrospective study in two tertiary referral centers (Department of ENT, Head and Neck Surgery, University of Erlangen-Nuremberg, Germany and the MacKay Memorial Hospital, Taipei, Taiwan). Patients with a diagnosis of sialolithiasis were treated in Erlangen and Taipei. The Erlangen patients were treated using the Calculase II™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany) at 4 Hz, 1.2 J (4.8 W) and the MacKay patients were treated using the VersaPulse® PowerSuite™ Ho:YAG laser (Lumenis Ltd., Yokneam, Israel) at 6 Hz, 0.5 J (3 W). RESULTS: A total of 12 patients with 12 stones were treated in Erlangen and 54 with 75 stones in Taipei. The submandibular stones were present in 50% and 86.7% of cases, respectively. The complete fragmentation was achieved in all of the treated stones in both groups; 100% and 92.6% of the patients were stone-free, 100% and 94.4% of the patients became symptom-free, respectively. 33% of the Erlangen patients had multimodal treatments. The glands were preserved in all cases in both centers. CONCLUSIONS: The Ho:YAG laser proved to be effective in the treatment of sialolithiasis. Stone size, location, and involved gland were important additional parameters. Our experience and the literature results show that the laser presetting with a frequency of 3-6 Hz, an energy level of 0.5-1.2 J, and effective power of between 3 and 4.8 W is sufficient to achieve maximum success without any increased risk for complications.
EVALuna2:209872

Intraductal lithotripsy in sialolithiasis with two different Ho:YAG lasers: Presetting parameters, effectiveness, success rates - Koch, M.; Hung, S. H.; Su, C. H.; Lee, K. S.; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: To compare two different Ho:YAG laser systems in relation to the preset parameters and their effectiveness for intraductal fragmentation of the salivary stones. PATIENTS AND METHODS: We made a retrospective study in two tertiary referral centers (Department of ENT, Head and Neck Surgery, University of Erlangen-Nuremberg, Germany and the MacKay Memorial Hospital, Taipei, Taiwan). Patients with a diagnosis of sialolithiasis were treated in Erlangen and Taipei. The Erlangen patients were treated using the Calculase II™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany) at 4 Hz, 1.2 J (4.8 W) and the MacKay patients were treated using the VersaPulse® PowerSuite™ Ho:YAG laser (Lumenis Ltd., Yokneam, Israel) at 6 Hz, 0.5 J (3 W). RESULTS: A total of 12 patients with 12 stones were treated in Erlangen and 54 with 75 stones in Taipei. The submandibular stones were present in 50% and 86.7% of cases, respectively. The complete fragmentation was achieved in all of the treated stones in both groups; 100% and 92.6% of the patients were stone-free, 100% and 94.4% of the patients became symptom-free, respectively. 33% of the Erlangen patients had multimodal treatments. The glands were preserved in all cases in both centers. CONCLUSIONS: The Ho:YAG laser proved to be effective in the treatment of sialolithiasis. Stone size, location, and involved gland were important additional parameters. Our experience and the literature results show that the laser presetting with a frequency of 3-6 Hz, an energy level of 0.5-1.2 J, and effective power of between 3 and 4.8 W is sufficient to achieve maximum success without any increased risk for complications.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Intraductal lithotripsy; Laser; Salivary gland; Sialendoscopy; Sialolithiasis; Treatment

Intraductal Papillary Mucinous Neoplasms of Minor Salivary Glands With AKT1 p.Glu17Lys Mutation - Agaimy, Abbas; Müller, Susanna; Bumm, Klaus; Iro, Heinrich; Moskalev, Evgeny; Hartmann, Arndt; Stoehr, Robert; Haller, Florian (American Journal of Surgical Pathology, 2018)
The spectrum of low-grade intraductal papillary proliferations of the salivary glands is heterogenous, and reproducible morphologic diagnostic criteria have not yet been established. Recognized types are sialadenoma papilliferum, inverted ductal papilloma, and intraductal papilloma, but some lesions have been possibly included in the morphologic spectrum of cystadenoma or low-grade intraductal carcinomas. We herein present detailed morphologic, immunophenotypic, and genotypic features of 3 minor salivary gland neoplasms affecting 2 men (aged 65 and 71 y) and 1 woman (aged 78 y). They ranged in size from 1 to 2.5 cm. All tumors showed atypical papillary intraductal growth that presented either as uninodular/unicystic lesions (intraductal papilloma-like; n=2) or as a discontinuous growth along the ductal system in a manner similar to pancreatic intraductal papillary mucinous neoplasm (n=1). Variable cytologic and architectural atypia was observed, ranging from bland intraductal papilloma-like features, to areas mimicking atypical ductal hyperplasia and low-grade ductal carcinoma in situ of the breast. Amplicon-based massive parallel sequencing revealed an identical AKT1 p.Glu17Lys mutation in all 3 cases, but absence of concurring mutations in other genes of the RAS or PI3K pathway. This small series represents the first genetic study on salivary intraductal papillary neoplasms. Our cases showed significant variation in the degree of cytologic and architectural atypia, which overlaps with intraductal papillomas at the one end and with low-grade intraductal carcinoma at the other end of the spectrum, suggesting a disease continuum. As the full biological and morphologic characteristics of these ductal papillary lesions remain to be defined, the noncommitted term "intraductal papillary neoplasms" might be more appropriate. Our novel genetic findings mirror similar activating mutations of AKT1 and other PI3K pathway members in intraductal papillary lesions of the breast and anogenital glands.
EVALuna2:34605

Intraductal Pneumatic Lithotripsy after Extended Transoral Duct Surgery in Submandibular Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2018)
Objective Persistent, residual, or recurrent stones after transoral duct surgery are always associated with hilar to intraparenchymal and/or multiple sialolithiasis, causing difficulties in the treatment. This study was performed to assess the value of intraductal lithotripsy in the treatment of persistent, residual, or recurrent sialolithiasis after extended duct surgery in the submandibular gland. Study Design Retrospective study covering February 2015 to June 2018. Study Setting Tertiary referral center for salivary gland diseases. Subjects and Methods After extended ductal surgery, 39 patients presenting with persistent, residual, or recurrent stones were treated. Four patients had persistent stones; 16 had residual stones; and 19 presented with recurrent stones. Among these patients, 50 stones were treated with intraductal pneumatic lithotripsy. Fragmentation rate, stone-free rate, and symptom-free rate after treatment with intraductal lithotripsy were outcome measures. Results Of the 39 patients, 97.4% became stone-free, and all were symptom-free. Ninety-eight percent of the stones were completely fragmented. For 23.1% of the patients, >1 stone was treated with intraductal lithotripsy. All patients with persistent stones, 93.7% of those with residual stones, and all with recurrent stones became stone-free and symptom-free. No severe complications developed. Conclusions This study shows that patients presenting with difficult and/or multiple sialolithiasis after extended transoral submandibular duct surgery can be treated with success rates >97%. For multiple sialolithiasis in particular, a multimodal treatment approach with interventional sialendoscopy and intraductal lithotripsy as a central element is a prerequisite for success, as this enables the most difficult part to be performed with high success rates.
EVALuna2:35383

Intraductal pneumatic lithotripsy for salivary stones with the StoneBreaker: Preliminary experience - Koch, Michael; Mantsopoulos, Konstantinos; Schapher, Mirco; Von Scotti, Felix; Iro, Heinrich (Laryngoscope, 2016)
OBJECTIVES/HYPOTHESIS: To test the effectiveness of a newly approved pneumatic lithotripter for fragmentation of salivary stones. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: In 44 patients, 49 stones were primarily treated with direct endoscopic guidance using the StoneBreaker. Twenty-three stones were located in the parotid gland and 26 in the submandibular gland. RESULTS: Complete fragmentation was achieved combined extracorporeal in 97.7% of the stones. All of the patients became symptom free, and 97.7% were stone free. Three patients underwent lithotripsy procedures. Altogether additional treatment was necessary in five cases to achieve stone clearance. The reason for residual sialolithiasis was intraparenchymal repulsion of a residual fragment (n = 1). The glands were preserved in all cases. CONCLUSIONS: Endoscopically guided intraductal pneumatic lithotripsy using the StoneBreaker is an effective and promising procedure for the treatment of sialolithiasis. LEVEL OF EVIDENCE: 4 Laryngoscope, 126:1545-1550, 2016.
EVALuna2:33186

Intraoperative free margins assessment of oropharyngeal squamous cell carcinoma with confocal laser endomicroscopy: a pilot study - Sievert, Matti; Stelzle, Florian; Aubreville, Marc; Müller, Sarina Katrin; Eckstein, Markus; Oetter, Nicolai; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with confocal laser endomicroscopy (CLE) during oropharyngeal squamous cell carcinoma (OPSCC) surgery. Methods: We included five consecutive patients confirmed OPSCC and planned tumor resection in September and October 2020. Healthy appearing mucosa in the marginal zone, and the tumor margin, were examined with CLE and biopsy during tumor resection. A total of 12,809 CLE frames were correlated with the gold standard of hematoxylin and eosin staining. Three head and neck surgeons and one pathologist were asked to identify carcinoma in a sample of 169 representative images, blinded to the histological results. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of OPSCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 86%, 90%, 79%, 88%, and 82%, respectively, with inter-rater reliability and κ-value of 0.60. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the oropharynx for evaluation and demarcation of cancer. It can eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Confocal laser endomicroscopy; Head and neck malignancies; Oropharyngeal squamous cell carcinoma; Safe surgical margins

Investigation of arguments against properly indicated extracapsular dissection in the parotid gland - Mantsopoulos, Konstantinos; Scherl, Claudia; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2017)
BACKGROUND: The ideal extent of surgical intervention for benign parotid tumors remains a matter of controversy. The purpose of this study was to examine the existing arguments against extracapsular dissection and present our experience over the last 16 years. METHODS: A retrospective evaluation was carried out on the records of all patients who underwent extracapsular dissection for benign parotid tumors at a tertiary referral center between 2000 and 2015. RESULTS: A total of 1359 cases were included in the study. Temporary postoperative facial palsy was detected in 68 cases (5%), permanent facial palsy in 5 cases (0.37%), and postoperative Frey's syndrome in 31 cases (2.3%). Recurrences of pleomorphic adenomas were shown in 4 cases (0.87%). CONCLUSION: Our analysis could not justify the arguments against correctly indicated implementation of extracapsular dissection and showed that increased performance of this modality was associated with excellent oncologic and functional outcomes. © 2016 Wiley Periodicals, Inc. Head Neck 39: 498-502, 2017.
EVALuna2:33198

Investigation of locoregional metastatic behavior in low-grade malignant tumors of the parotid gland - Kapsalas, Andreas; Thimsen, Vivian; Varga, Regina; Agaimy, Abbas; Sievert, Matti; Balk, Matthias; Rupp, Robin; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of low-grade malignant tumors of the parotid gland following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for low-grade malignant tumors of the parotid gland by complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 94 patients formed our study sample (50 females, 44 males, female to male ratio: 1.14). The mean age was 59 years (range 15–95 years). The mean number of lymph nodes in the specimen from complete parotidectomy was 3.33 (range: 0–12). The mean number of involved lymph nodes in the parotid gland was 0.05 (range: 0–1). The mean number of lymph nodes in the specimen from the ipsilateral neck dissection was 16.2 (range 4–42). The mean number of involved lymph nodes in the neck dissection specimen was 0.09 (range: 0–2). Comparison of T1-T2 vs. T3-T4 cases revealed no statistically significant difference concerning the tumorous involvement of the lymphatic network (x2 = 0.719, p = 0.396). Conclusion: Low-grade primary malignant tumors of the parotid gland are characterized by an initially low metastatic potential, which justifies conservative forms of surgical treatment.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Investigation of Sonographic Criteria for Reliable Identification of T1–T2 Low-Grade Malignant Tumors of the Parotid Gland - Berner, Ferdinand; Koch, Michael; Müller, Sarina Katrin; Schapher, Mirco; Grundtner, Philipp; Iro, Heinrich; Mantsopoulos, Konstantinos (Ultrasound in Medicine and Biology, 2020)
The aim of this study was to investigate sonographic findings of low-grade malignant tumors of the parotid gland. The sonographic findings of all patients treated for T1–T2 low-grade carcinomas of the parotid gland between 2003 and 2018 were retrospectively examined and compared with those of patients with pleomorphic adenomas for the following parameters: definition of tumor margins, echotexture, echogenicity, shape and vascularization. Statistical analysis was performed using the χ2 test. A p value of <0.05 was considered statistically significant. A total of 310 patients (62 with T1–T2 low-grade malignant tumors, 248 with pleomorphic adenomas) were evaluated. Our analysis detected a statistically significant difference in the definition of margins, echotexture, echogenicity and shape. Furthermore, we could detect a specific pattern (anechoic islets in a small hypoechoic lesion with distal enhancement) appearing far more frequently in low-grade malignant lesions. It seems that there is still potential to reduce the incidence of the false working hypothesis “benign lesion” on imaging of low-grade malignant tumors.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acinic cell carcinoma; Mucoepidermoid carcinoma; Parotid gland; Pleomorphic adenoma; Ultrasound

Investigation of the surgical strategies for unilateral multifocal cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Goncalves, Miguel; Iro, Heinrich (Oral Oncology, 2018)
OBJECTIVES: The aim of the study was to compare multifocal extracapsular dissection with complete parotidectomy in the treatment of unilateral multifocal cystadenolymphomas of the parotid gland. MATERIALS AND METHODS: The records from all patients treated for unilateral multifocal cystadenolymphomas of the parotid gland at a tertiary referral center between 2000 and 2016 were retrospectively analyzed. RESULTS: 203 patients were included in the study. 96 patients were managed by multifocal extracapsular dissection, 107 patients underwent complete parotidectomy. Metachronous tumors were detected in 7 cases (3.4%) with a significant difference in the occurrence rate between multifocal extracapsular dissection (7/96, 7.3%) and complete parotidectomy (0/107, 0%) (p = 0.004). Permanent facial palsy was significantly more common after complete parotidectomy (21/107, 19.6%) than multifocal extracapsular dissection (2/96, 2.1%) (p = 0.000). CONCLUSIONS: The functional benefit of multifocal extracapsular dissection was counterbalanced by the advantage of complete parotidectomy, in terms of recurrences. Extracapsular dissection is at its limit in cases of multifocal cystadenolymphomas and the indication for it should be thoroughly verified in each and every case.
EVALuna2:35388

Is Dissection of the Facial Verve avoidable during Surgery for benign Parotid Tumors? Parotid Surgery without Facial Nerve Dissection - Mantsopoulos, K.; Baer, B.; Iro, Heinrich (HNO, 2020)
CRIS-Team WoS Importer:2020-03-13

Is extracapsular dissection for pleomorphic adenoma rather a euphemism for enucleation that jeopardises the intactness of the capsule? - Mantsopoulos, Konstantinos; Iro, A. K.; Sievert, Matti; Müller, Sarina Katrin; Agaimy, Abbas; Schapher, Mirco; Koch, Matthias; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2021)
The aim of this study was to compare several surgical modalities with respect to the incidence of positive margins and focal capsular exposure of pleomorphic adenoma of the parotid gland. The clinical records and histopathological findings of all patients who underwent parotidectomy for pleomorphic adenoma between 2006 and 2020 were retrospectively evaluated (n = 845). The lesion was removed by extracapsular dissection in 577 cases (68%) and facial nerve dissection in 268 (32%). Our analysis did not reveal a statistically significant difference between the examined modalities regarding positive margins (p=0.648) or capsular exposure (p=0.112). Recurrences were detected in 7/845 cases (0.82%) with a mean (range) follow-up time of 82.3 (6-183) months. The choice of surgical method does not seem to have a significant effect on the incidence of positive margins, or on the capsular exposure of a pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: capsule; complete parotidectomy; extracapsular dissection; partial superficial parotidectomy; pleomorphic adenoma; superficial parotidectomy

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
Purpose: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1–3, pN0–pN2b), hypopharynx (pT1–2, pN0–pN1), and the indication for postoperative radio(chemo)therapy. Patients and methods: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan–Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. Results: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). Conclusion: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
CRIS-Team Scopus Importer:2019-06-04
Keywords: Disease-free survival; Late side effect; Overall survival; Radio(chemo)therapy; Second cancer

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
PURPOSE: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1-3, pN0-pN2b), hypopharynx (pT1-2, pN0-pN1), and the indication for postoperative radio(chemo)therapy. PATIENTS AND METHODS: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan-Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. RESULTS: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). CONCLUSION: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
EVALuna2:184476

Juvenile Larynxpapillomatose: Therapieoptionen und Literaturübersicht - Hübner, Matthias; Schützenberger, Anne; Traxdorf, Maximilian; Dittrich, Sven; Iro, Heinrich; Müller, Sarina Katrin (Monatsschrift Kinderheilkunde, 2022)
Background: Despite various therapeutic options, there is currently no cure for juvenile onset recurrent respiratory laryngeal papillomatosis (JORRP). Additionally, for the majority of these therapeutic options mild to severe side effects have been described. Objective: Analysis of the effects and side effects of previous and current therapeutic options. Discussion of active ingredients, dosage and administrative form of the available drugs. Material and methods: Review of literature and analysis of the therapeutic options concerning effects and side effects, active ingredients, dosage and administrative form. Results: Surgery remains the gold standard of all treatment options. There are multiple therapeutic options in the literature; however, no treatment options currently lead to a complete remission. Maintaining the function, increasing the time interval between interventions and diminishing the papilloma load in cases of recurrence remain the utmost priority. Conclusion: There are several promising therapeutic options for the treatment of JORRP; however, the current data situation is not sufficient for a general recommendation or guidelines. In the future, further prospective studies with a larger patient population/juvenile population are necessary.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Bevacizumab; Human papillomavirus; Laryngeal papillomatosis; Programmed cell death 1 receptor; Vaccine

Juvenile recurrent parotitis: a retrospective comparison of sialendoscopy versus conservative therapy - Schneider, Helgard; Koch, Michael; Künzel, Julian; Gillespie, M. Boyd; Grundtner, Philipp; Iro, Heinrich; Zenk, Johannes (Laryngoscope, 2014)
There are several therapeutic approaches to treat juvenile recurrent parotitis. The aim of this study was to compare sialendoscopy, including prophylactic cortisone irrigation, with observation and a conservative approach of antibiotic therapy alone.Retrospective study, tertiary clinical center.The charts of patients treated for juvenile recurrent parotitis between November 2004 and June 2011 were reviewed. Initial acute flares were always treated with a course of antibiotics. Subsequent treatment consisted of either salivary gland endoscopy including cortisone irrigation or additional pure antibiotic therapy. Patients treated with salivary endoscopy were compared to patients treated with antibiotics alone with regard to the number of inflammatory episodes and pain intensity pre- and posttreatment.Thirty-six patients were treated during the period of study, 15 with salivary endoscopy with cortisone irrigation and 21 with antibiotic therapy alone. A significant reduction in recurrent episodes and pain intensity following therapy was found in both groups. With respect to these two outcomes, the comparison showed two therapeutic options of equal merit.Salivary gland endoscopy is an option in the management of juvenile recurrent parotitis that helps in confirming the diagnosis and that also provides therapeutic intervention. However, although there are further advantages, the definitive value of salivary gland endoscopy requires ongoing evaluation in further prospective studies.4.
EVALuna2:19939

Kommentar zu „Sialendoskopie bei Sjögren-Syndrom und nach Radiojodtherapie - Iro, Heinrich (Laryngo-Rhino-Otologie, 2023)
CRIS-Team Scopus Importer:2023-08-25

KRAS codon 12 mutations characterize a subset of de novo proliferating “metaplastic” Warthin tumors - Agaimy, Abbas; Mantsopoulos, Konstantinos; Iro, Heinrich; Stöhr, Robert (Virchows Archiv, 2023)
Warthin tumor (WT; synonym: cystadenolymphoma) represents one of the most frequent salivary gland tumors with a frequency equaling or even outnumbering that of pleomorphic adenomas in some series. Histologically, the tumor displays tall columnar oncocytic cells, arranged into two cell-thick layers lining variably cystic glands within an organoid lymphoid stroma. Tumors with exuberant squamous metaplasia in response to FNA-induced or other types of tissue injury/infarction have been referred to as “metaplastic WTs.” However, the same terminology was used for tumors with variable mucinous cell and solid or stratified epidermoid proliferations (occasionally mimicking mucoepidermoid carcinoma), although the “metaplasia concept” has never been proven for the latter. We herein investigated 22 WTs showing prominent mucoepidermoid-like or solid oncocytoma-like proliferations without prior FNA or histological evidence of infarction/ trauma using the TruSight Tumor 15 gene panel and KRAS pyrosequencing. As a control, we tested 11 conventional WTs. No statistically significant differences were observed between the two subcohorts regarding patient’s age and tumor size. Six of 22 (27%) proliferating/ metaplastic WTs revealed oncogenic KRAS mutations clustering at codon 12 (exon 2), while all conventional tumors lacked these mutations. Our findings are in line with a neoplastic nature of the epidermoid/ mucoepidermoid proliferations in non-injured “metaplastic” Warthin tumors. We propose the descriptive term “de novo proliferating Warthin tumor” for this variant to distinguish it from infarcted/inflamed genuine metaplastic Warthin tumor.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cystadenolymphoma; KRAS mutations; Metaplastic Warthin tumor; Mucoepidermoid carcinoma; Salivary glands; Warthin tumor

Letter to the Editor-1 regarding "Extracapsular dissection versus superficial parotidectomy in benign parotid gland tumors: The Vienna Medical School experience" - Mantsopoulos, Konstantinos; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2018)
EVALuna2:33196

Letter to the editor regarding the "Functional outcomes after extracapsular dissection with partial facial nerve dissection for small and large parotid neoplasms" - Mantsopoulos, Konstantinos; Iro, Heinrich (American Journal of Otolaryngology, 2021)
CRIS-Team WoS Importer:2021-06-25

Limited parotid surgery as sole form of treatment for carefully selected malignant tumours of the parotid gland: Still sufficient on the long-term? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Sievert, Matti; Balk, Matthias; Grundtner, Philipp; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate the oncological and functional outcome following extracapsular dissection as the sole form of treatment in locally limited low-grade malignant parotid tumours in the long term. Methods: The records of all patients treated for T1-T2 low-grade malignant tumours of the parotid gland solely by means of extracapsular dissection between 2005 and 2017 were studied retrospectively. Results: A total of 16 cases formed our study sample (7 men, 9 women). Their mean age was 50.2 years (21–84 years). Mean follow-up was 107 months (60–201 months). In 6 cases the tumour was an acinic cell carcinoma, in 9 cases a mucoepidermoid carcinoma and in one case a basal cell adenocarcinoma. Regarding the T category, the tumour was Tis in one case, T1 in 12 cases and T2 in three cases. The five-year disease-specific survival rate was 100 %, as was local disease control. Facial nerve function was House-Brackmann grade I without exception. Conclusions: Our study showed very encouraging long-term results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. Lay summary: The “one-size-fits-all” strategy of complete parotidectomy with neck dissection might be tantamount to overtreatment by less aggressive cases of parotid cancer. Extracapsular dissection seems to be oncologically sufficient for carefully selected T1-T2 low-grade cases in the long-term in patients with ensured follow-up.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Extracapsular dissection; Facial nerve; Low-grade; Malignant tumour; Parotid gland

Lipotransfer führt zu Verbesserung von Schluck- und Artikulationsstörungen nach mikrochirurgischer Zungenrekonstruktion – ein Fallbericht - Cai, Aijia; Iro, Heinrich; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2021)
Atrophy of tongue after free-flap reconstruction often leads to functional problems like dysphagia and articulation disorders. Lipotransfer might resolve this issue. We describe a case of repeated lipotransfer into an atrophied reconstructed tongue. A 66-year-old patient with a squamous cell carcinoma of the tongue underwent hemiglossectomy and reconstruction of the tongue by a free radial forearm flap. After atrophy of the reconstructed tissue, repeated sessions of lipotransfer were undertaken to augment the atrophic tissue. Three sessions of lipotransfer resulted in satisfactory augmentation of the atrophied reconstructed tongue, leading to improvement of dysphagia and articulation. To our knowledge, this is the first report of lipotransfer used to augment a flap inside the oral cavity. We propose this tool as a potential aid to improve typical tongue reconstruction sequelae.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Lipotransfer; Neozunge; Schluckstörung; Sprechstörung; Zungenrekonstruktion

Locoregional metastatic behavior in a complex mosaic of primary malignant tumors of the parotid gland - Varga, Regina; Iro, Ann Kristin; Thimsen, Vivian; Sievert, Matti; Agaimy, Abbas; Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of various malignant tumors of the parotid gland with varying grades following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for primary malignant tumors of the parotid gland by means of complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 196 patients formed our study sample (98 females, 98 males). The mean age was 65.7 years (22–101 years). 92 cases presented with low-grade subtypes, 19 with intermediate-grade, and 85 with high-grade carcinomas. The locoregional lymphatic network had been invaded in a total of 66/196 cases (33.6 %). The intraparotid lymph nodes were positive in 54/196 cases (27.5 %) and the cervical lymph nodes in 41/196 cases (20.9 %). In 12 out of the 66 cases with a pN+ status, the neck had been invaded without involvement of the intraparotideal lymph nodes (18.2 %). Male patients tended to suffer from more aggressive carcinomas, and high-grade subtypes presented significantly more frequently as locally advanced tumors. Higher grading was significantly associated with the involvement of the parotid (p < 0.001) and cervical (p < 0.001) lymph nodes. Intermediate and low-grade cases presented similar behavior concerning tumorous invasion of the lymphatic network of the parotid gland (p = 0.522) and the neck (p = 0.467). Conclusion: The locoregional metastatic potential of parotid malignant tumors depends upon a variety of histopathologic factors, which have to be considered in the decision-making process concerning the management of locoregional lymph nodes.
CRIS-Team Scopus Importer:2023-07-21
Keywords: High-grade; Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Long-term follow-up as an indispensable parameter for reliable assessment of the audiologic outcome after middle ear surgery - Mantsopoulos, Konstantinos; Thimsen, Vivian; Goncalves, Miguel; Sievert, Matti; Müller, Sarina Katrin; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
CRIS-Team WoS Importer:2021-10-22

Long-term oncologic and functional outcome in pleomorphic adenomas of the submandibular gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich (Laryngoscope, 2017)
Objectives: The aim of the study was to evaluate the oncologic and functional long-term outcome after surgical therapy of pleomorphic adenomas of the submandibular gland. Methods: The medical charts of all patients treated for pleomorphic adenomas of the submandibular gland by means of submandibulectomy between 2000 and 2016 were studied retrospectively. Patients who had had revision after external primary surgery, as well as patients with insufficient data were excluded from our study sample. Results: A total of 75 patients formed our study sample (28 men, 47 women, male:female ratio 0.59:1). Their mean age was 48 years (14-78 years). Mean follow-up was 82 months (12-170 months). No recurrences of a pleomorphic adenoma could be detected in our study cases. Normal facial nerve function (House-Brackmann grade I) in the direct postoperative phase was shown in 54/75 cases (72%). In the remaining 21/75 cases (28%), mild paresis of the marginal mandibular branch of the facial nerve (House-Brackmann II) could be detected in the direct postoperative phase. All cases with facial palsy had recovered with normal facial nerve function (House-Brackmann I) in 3-6 months. Conclusion: Our study was able to show oncologic and consistently acceptable oncologic and functional outcomes after submandibulectomy for pleomorphic adenomas of the submandibular gland. Level of Evidence: 4.
EVALuna2:33360

Long-term results and subjective outcome after gland-preserving treatment in parotid duct stenosis - Koch, Michael; Künzel, Julian; Iro, Heinrich; Psychogios, Georgios; Zenk, Johannes (Laryngoscope, 2014)
To assess the objective long-term results and subjective outcome after treatment of Stensen's duct stenosis.Retrospective study at a tertiary center.The long-term results after treatment with a minimally invasive regimen focusing on sialendoscopy were assessed in 82 patients with 98 parotid duct stenoses after primary gland-preserving treatment. A questionnaire was used to assess the patients' perception of success, including clinical parameters and a visual analogue scale (VAS) assessing pain, symptoms, and salivary gland-related quality of life (QOL). Patients were invited to present for clinical and ultrasound examinations and sialendoscopy.The average follow-up period was 98.48 months. Fifty percent of the patients reported having recurrent gland swelling; but only 19.5% reported recurrent pain and the VAS scores for current symptoms and pain were low. Independent of the type of stenosis, the VAS scores showed a significant reduction in symptoms and improvement in the perceived QOL after the treatment (P = 0.0001 each). Follow-up examinations were carried out in 20.73% of the patients, and sialendoscopy was performed in 12.1% of the patients. After diagnosis, recurrent stenoses (n = 8, 9.75%) were successfully reopened in all cases. The glands were preserved in all of the patients.Long-term evaluation after minimally invasive treatment of stenoses of the parotid duct indicates that high success rates, high rates of gland preservation, and an acceptable subjective patient outcome can be achieved.
EVALuna2:19940

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-06-18

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma. German version - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-05-07

Lymph node ratio as a predictor of outcome in patients with oropharyngeal cancer - Künzel, Julian; Psychogios, Georgios; Mantsopoulos, Konstantinos; Grundtner, Philipp; Waldfahrer, Frank; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2014)
To evaluate the utility of lymph node ratio (LNR) as a potential prognostic predictor and to test whether LNR may be useful as a potential selection criterion for adjuvant treatment in patients with oropharyngeal squamous cell carcinoma (OPSSC). This retrospective study included 384 patients with regionally metastasized OPSCC who underwent primary surgery with or without adjuvant therapy from 1980 to 2010. LNR was calculated as the ratio of positive lymph nodes to the total number of lymph nodes removed during neck dissection. Statistical analysis using a Cox regression model was carried out. The 5-year disease-specific survival (DSS) was 73%. An individual LNR peak at 0.1 was closest to the median of 0.0909, and both were set as cut-off values. Patients in the group greater than median had a hazard ratio (HR) of 2.472 for a DSS event; this was close to an HR of 2.513 for LNR >0.1. In multivariate analysis, LNR showed a markedly stronger HR with regard to survival in comparison with the grouped pN classification. The covariate treatment modality did not meet the assumption of the Cox regression, and it was therefore not possible to comment reasonably on the issue of whether LNR could be a potential selection criterion for adjuvant treatment. Lymph node ratio is in itself a valuable additional prognostic factor for risk stratification. According to the current results, the most valuable LNR for OPSSC is expected to be located in the range from 0.09 to 0.1. Further investigations in large prospective trials will be required to allow evidence-based recommendations for treatment decisions based on the LNR.
EVALuna2:19931

Lymph node ratio is of limited value for the decision-making process in the treatment of patients with laryngeal cancer - Kuenzel, Julian; Mantsopoulos, Konstantinos; Psychogios, Georgios; Agaimy, Abbas; Grundtner, Philipp; Koch, Michael; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2015)
The lymph node ratio (LNR) combines two types of information–about the extent of neck dissection and about the extent of the pathological examination of the specimen–and thus represents an interesting variable for risk assessment in patients with head and neck cancer. This retrospective study with data from January 1, 1980, to December 31, 2010, evaluates the utility of the LNR as a potential prognostic predictor in patients with laryngeal squamous cell carcinoma (LSCC). A total of 202 consecutive patients with regionally metastasized LSCC who underwent primary surgery with or without adjuvant treatment were included. The mean follow-up period was 4.4 years. The LNR was calculated as the ratio of positive nodes to the total number of nodes removed during neck dissection. Multivariate analysis was carried out. Peak values as averaged clusters of individual LNRs were registered at three points (LNR 0.05, 0.07, and 0.09). LNR 0.09 was a significant prognostic parameter in the Cox regression model (P = 0.007). Patients with an LNR > 0.09 had a hazard ratio of 2.065 for a disease-specific survival event in comparison with LNR < 0.09. The most accurate LNR for LSCC is expected to be located in the range of 0.08-0.1. The LNR seems to be of limited value for the decision-making process in the treatment of patients with LSCC, in comparison with other locations. Prospective trials will be required in order to allow evidence-based recommendations for treatment decisions based on the LNR.
EVALuna2:6680

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Management of advanced hypopharyngeal and laryngeal cancer with and without cartilage invasion - Scherl, Claudia; Mantsopoulos, Konstantinos; Semrau, Sabine; Fietkau, Rainer; Kapsreiter, Markus; Koch, Michael; Traxdorf, Maximilian; Grundtner, Philipp; Iro, Heinrich (Auris Nasus Larynx, 2016)
To compare efficacy, in terms of disease control/survival in advanced hypopharyngeal and laryngeal lesions, according to treatment strategy (primary surgery, PS or primary chemoradiotherapy, CRT) and invasion pattern (cartilage, CAI or soft tissue involvement, STI).Records from 463 patients with T3 and T4a carcinoma with CAI (n=221) or STI (n=242) treated at a university clinic over 18 years were retrospectively reviewed.Disease-specific survival (DSS) for the CAI group was 70.1% (PS) and 38.4% (CRT), and 76.6% and 46% for the STI group, respectively. Overall survival (OS) for STI was 56.4% (PS) and 30.6% (CRT), and for CAI 51.1% (PS) and 28.5% (CRT) respectively. Positive resection margins and regional neck metastases reduced survival. T3 lesions treated non-operatively still had significantly improved survival versus T4a by >20%.Surgery remains an indispensable part of treatment in local advanced hypopharyngeal and laryngeal cancer with high survival results. It should be part of a concept that includes adjuvant (C)RT. For T3 lesions, primary CRT is also acceptable and CAI is not a contraindication for primary CRT. Regional disease is a strong prognostic factor. In spite of adjuvant treatment, DSS deteriorates by about 20% in cases with positive resection margins.
EVALuna2:18360

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Management von Patienten mit Tracheostoma während der COVID-19-Pandemie: Literaturüberblick und Demonstration - Kempfle, J. S.; Löwenheim, H.; Hübner, Matthias; Iro, Heinrich; Müller, Sarina Katrin (HNO, 2020)
Background: Since emergence of the new coronavirus in China in December 2019, many countries have been struggling to control skyrocketing numbers of infections, including among healthcare personnel. It has now been clearly demonstrated that SARS-CoV‑2 resides in the upper airways and transmits easily via aerosols and droplets, which significantly increases the risk of infection when performing upper airway procedures. Ventilated COVID-19 patients in a critical condition in the intensive care unit may require tracheotomy for long-term ventilation and to improve weaning. However, the risk of secondary infection of medical personnel performing subsequent tracheostomy care remains unclear. Objective: This study aimed to evaluate the risk of droplet dispersion during tracheostomy tube change and overview tracheostomy tube change in COVID-19 patients. Materials and methods: The current literature was reviewed, quantitative and qualitative analyses of droplet formation during tracheostomy tube change in n = 8 patients were performed, and an overview of and checklist for tracheostomy tube change were compiled. Results: This study demonstrates that tracheostomy tube change, in particular insertion of the new tube, may cause significant droplet formation. The aerosolization of particles smaller than 5 µm was not analyzed. Conclusion: Our data, together with the current literature, clearly emphasize that tracheostomy care is associated with a high infection risk and should only be performed by a small group of well-trained, maximally protected healthcare personnel.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Aerosols; COVID-19; Droplets; PPE; Tracheostomy tube change

Maximum monosyllabic score as a predictor for cochlear implant outcome - Hoppe, Ulrich; Hocke, T.; Hast, A.; Iro, Heinrich (HNO, 2019)
ObjectiveThis study investigated the speech perception of cochlear implant (CI) recipients with measurable preoperative ipsilateral speech perception. These data should support improved individual counselling of CI candidates.Materials and methodsPre- and postoperative speech audiometric parameters were analyzed, including maximum score for phonemically balanced words (PBmax) and monosyllabic score at anormal conversational level of 65dB(SPL), with hearing aids one hand and CI on the other. Data of 284 experienced adult CI wearers were grouped and evaluated in terms of preoperative PBmax.ResultsThe preoperative PBmax was exceeded by the postoperative monosyllabic score in 96% of cases. The overall median postoperative score was 72.5%. The groups with preoperative PBmax>0% showed significantly better speech perception scores with CI than the group with PBmax=0%. Median improvement compared to the preoperative monosyllabic score with hearing aids was 65percentage points, independent of preoperative PBmax.ConclusionThe preoperatively measured PBmax may be used as apredictor for the minimum speech perception obtained with CI. This is of high clinical relevance for CI candidates with a PBmax above zero.
CRIS-Team WoS Importer:2019-03-26

Maximum preimplantation monosyllabic score as predictor of cochlear implant outcome - Hoppe, Ulrich; Hocke, Thomas; Hast, Anne; Iro, Heinrich (HNO, 2019)
ObjectiveThis study investigated the speech perception of cochlear implant (CI) recipients with measurable preoperative ipsilateral speech perception. These data should support improved individual counselling of CI candidates.Materials and methodsPre- and postoperative speech audiometric parameters were analyzed, including maximum score for phonemically balanced words (PBmax) and monosyllabic score at anormal conversational level of 65dB(SPL), with hearing aids one hand and CI on the other. Data of 284 experienced adult CI wearers were grouped and evaluated in terms of preoperative PBmax.ResultsThe preoperative PBmax was exceeded by the postoperative monosyllabic score in 96% of cases. The overall median postoperative score was 72.5%. The groups with preoperative PBmax>0% showed significantly better speech perception scores with CI than the group with PBmax=0%. Median improvement compared to the preoperative monosyllabic score with hearing aids was 65percentage points, independent of preoperative PBmax.ConclusionThe preoperatively measured PBmax may be used as apredictor for the minimum speech perception obtained with CI. This is of high clinical relevance for CI candidates with a PBmax above zero.
CRIS-Team WoS Importer:2019-06-28

Merged Volume Rendered Flat-panel Computed Tomography for Postoperative Cochlear Implant Assessment - Eisenhut, Felix; Lang, Stefan; Dörfler, Arnd; Iro, Heinrich; Hornung, Joachim; Taha, Lava (Clinical Neuroradiology, 2019)
Purpose: Evaluation of a new postprocessing method for postoperative control of cochlear implants (CI) based on a single flat detector computed tomography (FD-CT) run and volume rendering of 3D models of the inner ear. Methods: The FD-CT datasets of CIs were selected and postprocessed to generate both standard multiplanar reconstructions (MPR) and merged volume-rendered 3D datasets (MRD) of the CIs. The MRDs consisted of two different reconstructions (bone/implant) that are automatically layered to avoid manual coregistration inaccuracy. Corresponding datasets were evaluated in consensus reading in terms of qualitative (integrity, position, configuration) and quantitative (insertion depth angle) CI parameters. Results: In total 20 FD-CTs with 20 CIs were successfully postprocessed. Qualitative evaluation of MPR and MRD demonstrated complete congruency (integrity: narray integrity = 20; position: nscala tympani = 13, nscalar translocation = 7; configuration: nharmonic spiralization = 16, ntip fold over = 3, nlooped implant = 1). Adverse intracochlear implant spiralization was identified in all 10 cases with MRD and MPR. Measurement of the insertion depth angle in MRD was equivalent to that in MPR (r = 0.99; P = <0.0001). Conclusion: The use of MRD is a helpful method for precise postoperative CI assessment and provides easy detection of incorrect intracochlear spiralization.
CRIS-Team Scopus Importer:2019-09-20
Keywords: CI; FD-CT; Postprocessing; Temporal bone; Three-dimensional

Metabolic Response of Short-term Induction Chemotherapy (IC) for Therapy Selection as well as Prediction of long-term local and systemic Therapy Success for Head and Neck cancer. The Results of 100 Patients - Semrau, S.; Haderlein, Marlen; Schmidt, Daniela; Waldfahrer, F.; Scherl, C.; Lettmaier, S.; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer (2017)
EVALuna2:32895

Microcystic adnexal carcinoma (MAC)-like squamous cell carcinoma as a differential diagnosis to Bell´s palsy: review of guidelines for refractory facial nerve palsy - Müller, Sandra; Iro, Heinrich; Lell, M.; Seifert, F.; Bohr, Christopher; Scherl, C.; Agaimy, Abbas; Traxdorf, Maximilian (Journal of Otolaryngology-Head & Neck Surgery, 2017)
Bell´s palsy is the most common cause of facial paralysis worldwide and the most common disorder of the cranial nerves. It is a diagnosis of exclusion, accounting for 60-75% of all acquired peripheral facial nerve palsies. Our case shows the first case of a microcystic adnexal carcinoma-like squamous cell carcinoma as a cause of facial nerve palsy.The patient, a 70-year-old Caucasian male, experienced subsequent functional impairment of the trigeminal and the glossopharyngeal nerve about 1½ years after refractory facial nerve palsy. An extensive clinical work-up and tissue biopsy of the surrounding parotid gland tissue was not able to determine the cause of the paralysis. Primary infiltration of the facial nerve with subsequent spreading to the trigeminal and glossopharyngeal nerve via neuroanastomoses was suspected. After discussing options with the patient, the main stem of the facial nerve was resected to ascertain the diagnosis of MAC-like squamous cell carcinoma, and radiochemotherapy was subsequently started.This case report shows that even rare neoplastic etiologies should be considered as a cause of refractory facial nerve palsy and that it is necessary to perform an extended diagnostic work-up to ascertain the diagnosis. This includes high-resolution MRI imaging and, as perilesional parotid biopsies might be inadequate for rare cases like ours, consideration of a direct nerve biopsy to establish the right diagnosis.
EVALuna2:6836

Multimodal treatment in difficult sialolithiasis: Role of extracorporeal shock-wave lithotripsy and intraductal pneumatic lithotripsy - Schapher, Mirco; Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; von Scotti, Felix; Goncalves, Miguel; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES: To assess results after treatment of difficult/complex sialolithiasis with extracorporeal shock-wave lithotripsy (ESWL) and intraductal pneumatic lithotripsy (IPL). STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: Altogether, 63 stones were diagnosed in 38 patients with difficult/complex sialolithiasis. Forty-nine stones were treated with fragmentation using both ESWL and IPL. Stones accessible with the sialendoscope were treated primarily with IPL in multiple sialolithiasis. RESULTS: Seventy-one ESWL procedures and 57 IPL were performed in our patients. Forty-nine stones were treated by 67 ESWL procedures and 52 IPL. ESWL converted sialoliths from sialendoscopically untreatable into sialendoscopically treatable cases in 94.7%; the treatment then was completed by a total of 52 IPL procedures. ESWL was performed before IPL (81.6%), in combination with IPL (7.9%) and after (10.5%). Complete fragmentation was achieved in 97.9%. Four stones each were treated with ESWL and IPL alone in multiple sialolithiasis. Altogether, 53 stones were treated by 57 IPL procedures. Complete fragmentation was achieved in 98.1% of the 53 stones. ESWL and IPL were the dominant treatment modalities in 84.1% of all 63 stones treated. Of all 38 patients, 92.1% became stone-free and all became symptom-free. All the glands were preserved. Multiple stones were treated in 34.2% of the patients; of these, 92.3% became stone-free. CONCLUSION: These results show that patients with difficult and complex sialolithiasis can be treated with high success rates of > 90% using a multimodal, minimally invasive, and gland-preserving treatment approach. ESWL and IPL played a key role in this multimodal treatment regime in > 80% of stones. LEVEL OF EVIDENCE: 4. Laryngoscope, 2017.
EVALuna2:33362

Myringoplasty for pediatric chronic otitis media: An uncritical closure of a natural middle ear drainage? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Richter, Daniel; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Background: Performing tympanoplasty for tympanic perforations in children and adolescents is often considered to be less successful than in adults. Objectives: The aim of our study was to evaluate the surgical outcome of tympanoplasty type I in patients under 15 years of age with chronic otitis media and to identify potential factors that influence the success rate. Materials und methods: The present study was based on a retrospective analysis of the medical records of all patients under the age of 15 who were treated for chronic otitis media by means of type I tympanoplasty between 2005 and 2020. The minimum follow-up period was 6 months. The data were analyzed with regard to epidemiological parameters, tube-related pathologies in the contralateral ear, the local condition and the extent of the eardrum perforation as well as the extent of the surgical intervention (tympanoplasty type I with or without adenotomy). Results: 83 cases were included in our study. The mean age at the time of the surgery was 8.9 years. The mean follow-up time was 46 months (6–182 months). The anatomical closure rate was 88.0%. Children with “dry” tympanic perforations tended to perform better (p = 0.052). The average improvement in the air bone gap was 2.0 dB. Conclusion: Detailed preoperative counseling about the advantages and disadvantages as well as the expected success rate of an early myringoplasty in this age group is just as important as an individualized approach for a high level of patient satisfaction.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cartilage; Chronic otitis media; Myringoplasty; Tympanic perforation; Tympanoplasty

Near-infrared sentinel diagnostics in head and neck squamous cell carcinoma: a systematic review - Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-25

Nearly 3,000 salivary stones: some clinical and epidemiologic aspects - Sigismund, Paolo E.; Zenk, Johannes; Koch, Michael; Schapher, Mirco; Rudes, Mihael; Iro, Heinrich (Laryngoscope, 2015)
To investigate epidemiological features and symptoms of sialolithiasis and their implications for diagnosis and management.Retrospective cohort study.Retrospective analysis on 2,322 patients with sialolithiasis, between 1987 and 2009. The statistical significance between two sample distributions was computed using analysis of variance Student t test for two-tailed distribution.A total of 2,959 calculi were identified by means of ultrasound. Of those, 80.4% were located in the submandibular duct system (53% hilar/proximal, 37% distal, 10% intraparenchymal) and 19.6% were parotid stones (83% in Stensen's duct, 17% intraparenchymal). Sialoliths had been discovered beforehand in the submandibular gland (P = 0.00024; t test). Symptoms, measured from first visit, lasted on average 26 months (range: 1 day-30 years). The main group suffered from swelling (50.3%), followed by painful swelling (41.6%) and pain (3.1%). Multiple stones were found in 16.9% of patients (18.1% in the submandibular gland; 14.3% in the parotid). Average stone diameter in the submandibular gland was 8.3 mm (range 1-35 mm), and the stones were in Lustmann group II (46%). In the parotid gland, the average diameter was 6.4 mm (range 1-31 mm), and 51% were in Lustmann group I.Nowadays, epidemiologic features and clinical manifestations of sialolithiasis play an important role, assisting not only in diagnosis but also in determining appropriate treatment. Due to their location and smaller diameter, parotid stones in some cases can only be treated using a mini-invasive endoscopic technique. Submandibular stones more often require a combined approach.4
EVALuna2:19993

Neutrophil Extracellular Traps Promote the Development and Growth of Human Salivary Stones - Schapher, Mirco; Koch, Michael; Weidner, Daniela; Scholz, Michael; Wirtz, Stefan; Mahajan, Aparna; Herrmann, Irmgard; Singh, Jeeshan; Knopf, Jasmin; Leppkes, Moritz; Grüneboom, Anika; Alexiou, Christoph; et al. (Cells, 2020)
Salivary gland stones, or sialoliths, are the most common cause of the obstruction of salivary glands. The mechanism behind the formation of sialoliths has been elusive. Symptomatic sialolithiasis has a prevalence of 0.45% in the general population, is characterized by recurrent painful periprandial swelling of the affected gland, and often results in sialadenitis with the need for surgical intervention. Here, we show by the use of immunohistochemistry, immunofluorescence, computed tomography (CT) scans and reconstructions, special dye techniques, bacterial genotyping, and enzyme activity analyses that neutrophil extracellular traps (NETs) initiate the formation and growth of sialoliths in humans. The deposition of neutrophil granulocyte extracellular DNA around small crystals results in the dense aggregation of the latter, and the subsequent mineralization creates alternating layers of dense mineral, which are predominantly calcium salt deposits and DNA. The further agglomeration and appositional growth of these structures promotes the development of macroscopic sialoliths that finally occlude the efferent ducts of the salivary glands, causing clinical symptoms and salivary gland dysfunction. These findings provide an entirely novel insight into the mechanism of sialolithogenesis, in which an immune system-mediated response essentially participates in the physicochemical process of concrement formation and growth.
CRIS-Team Scopus Importer:2020-10-09
Keywords: lithogenesis; neutrophil extracellular traps; neutrophils; salivary glands; salivary stones; sialadenitis; sialolithiasis; stone development; stone growth

NiTiBOND an optimized self-crimping stapes prosthesis for treatment of otosclerosis - Huber, A. M.; Hornung, Joachim; Plontke, S.; Roeoesli, C.; Iro, Heinrich; Strutz, J.; Rahne, T.; Pezier, T. F.; Kwok, P. (Laryngo-Rhino-Otologie, 2014)
Compared to traditional stapes prostheses, self-crimping prostheses have been shown to result in similar, if not better, closure of the air bone gap in patients undergoing stapedotomy for otosclerosis. To achieve self-crimping, nitinol, a shape memory alloy, has been used for several years but concerns have been raised regarding possible damage to the incus and its muco-periosteum. We investigate these concerns with regard to the newer NiTiBOND stapes prosthesis in an observational multi-centre study.In a multicentre, prospective observational study, 76 patients undergoing stapedotomy with the NiTiBond prosthesis across 4 centres were compared to 75 -retrospectively selected control SMart patients. Complications, intra-operative user-friendliness and audiological results at 3 months were documented.Audiological improvement and the rate of complications were similar in both groups. Non inferiority was shown at all frequencies and in the pure-tone average. The NiTiBOND prosthesis was described as very user-friendly.By eliminating manual crimping, stapedotomy using the NiTiBOND prosthesis can be facilitated and standardized. Furthermore, intraoperative handling characteristics of the prosthesis are very good which may further reduce operative risk. Importantly, we show that these benefits are not to the detriment of audiological outcome. Larger and longer-term studies are required to further evaluate results.
EVALuna2:19925

Nuclear NR4A2 (Nurr1) Immunostaining is a Novel Marker for Acinic Cell Carcinoma of the Salivary Glands Lacking the Classic NR4A3 (NOR-1) Upregulation - Haller, Florian; Moskalev, Evgeny; Kuck, Sarina; Bieg, Matthias; Winkelmann, Christa; Müller, Susanna; Ihrler, Stephan; Märkl, Bruno; Eils, Roland; Wiemann, Stefan; Iro, Heinrich; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2020)
CRIS-Team Scopus Importer:2020-05-22

Nuclear NR4A3 Immunostaining Is a Specific and Sensitive Novel Marker for Acinic Cell Carcinoma of the Salivary Glands - Haller, Florian; Skálová, Alena; Ihrler, Stephan; Märkl, Bruno; Bieg, Matthias; Moskalev, Evgeny; Erber, Ramona; Blank, Susanne; Winkelmann, Christa; Hebele, Simone; Baněčková, Martina; Wiemann, Stefan; et al. (American Journal of Surgical Pathology, 2019)
Recently, we discovered the recurrent genomic rearrangement [t(4;9)(q13;q31)] enabling upregulation of the transcription factor Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) through enhancer hijacking as the oncogenic driver event in acinic cell carcinoma (AciCC) of the salivary glands. In the current study, we evaluated the usefulness of NR4A3 immunostaining and NR4A3 fluorescence in situ hybridization (FISH) in the differential diagnosis of AciCC, comparing a total of 64 AciCCs including 17% cases with high-grade transformation, 29 secretory (mammary analog) carcinomas (MASC), and 70 other salivary gland carcinomas. Nuclear NR4A3 immunostaining was a highly specific (100%) and sensitive (98%) marker for AciCC with only 1 negative case, whereas NR4A3 FISH was less sensitive (84%). None of the MASCs or other salivary gland carcinomas displayed any nuclear NR4A3 immunostaining. The recently described HTN3-MSANTD3 gene fusion was observed in 4 of 49 (8%) evaluable AciCCs, all with nuclear NR4A3 immunostaining. In summary, NR4A3 immunostaining is a highly specific and sensitive marker for AciCC, which may be especially valuable in cases with high-grade transformation and in "zymogen granule"-poor examples within the differential diagnostic spectrum of AciCC and MASC.
CRIS-Team Scopus Importer:2019-09-03
Keywords: acinic cell carcinoma; HTN3-MSANTD3; immunohistochemistry; NR4A3; salivary glands; translocation

Olfactory Neuroblastomas: What Actually Happens in the Long-Term? - Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Constantinidis, Jannis (Journal of Clinical Medicine, 2022)
Objective: The aim of this study was to investigate the long-term oncologic outcome and review the state of the art in the management of olfactory neuroblastomas. Material and Methods: The records of all patients treated for olfactory neuroblastomas in two academic departments between 1975 and 2012 were evaluated retrospectively. Data on epidemiological parameters were collected (age, gender), along with staging (Kadish, Morita), histologic grading (Hyams), time and form of treatment, locoregional control, and disease-specific and overall survival. Patients with other malignant diseases, distant metastases of olfactory neuroblastomas at the time of initial diagnosis, a follow-up time of less than 5 years, or insufficient clinical-pathological data were excluded from further analysis. Results: In total, 53 cases made up our final study sample (26 men, 27 women; male–female ratio 0.96:1). Their mean age was 48.6 years (range: 10–84 years). The mean follow-up time was 137.5 months (4–336 months, SD: 85.0). A total of 5 out of 53 study cases (9.4%) showed metastatic involvement of the neck at the time of initial presentation. Local recurrence was detected in 8/53 (15.1%) and regional recurrence in 7/53 of our study cases (13.2%). Three patients (42.8%) from the group of cases with surgery as the sole form of management (7/53, 13.2%) died due to the disease. The cumulative disease-specific survival and overall survivalfor the whole group of patients were 88.6% and 63.6%, respectively. The cumulative disease-specific survival stratified by Kadish A/B vs. Kadish C/D as well as Hyams I/II vs. Hyams III/IV showed superior results for limited tumors, albeit without significance, and low-grade tumors (highly significant difference). Conclusion: Craniofacial or sometimes solely endoscopically controlled resection can warrant resection of the olfactory neuroblastoma with wide margins. However, locoregional failures and distant metastases can occur after a long period of time. The non-negligible incidence of regional recurrences, partly in unusual localizations, leads us to consider the need to identify the “recurrence-friendly” cases and to perform individualized elective irradiation of the neck in cases with high-risk features.
CRIS-Team Scopus Importer:2022-05-20
Keywords: endoscopic surgery; esthesioneuroblastoma; Hyams; Kadish; olfactory neuroblastoma; recurrence; survival

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

Ossicular osteoma of the malleus—A rare diagnosis of middle ear mass - Sievert, Matti; Mantsopoulos, Konstantinos; Hornung, Joachim; Thimsen, Vivian; Heiß, Rafael; Kopp, Markus; Wetzl, Matthias; Iro, Heinrich; Uder, Michael; Wiesmüller, Marco (Radiology Case Reports, 2022)
Osteoma of the middle ear (MEO) is a rarity. Due to the benign nature and slow growth rate, MEO are often occasionally found by chance. Possible unspecific clinical symptoms may be conductive hearing loss, tinnitus, effusion, and a sense of fullness. If the osteoma is small and not visible in the otoscopic inspection, it may be confused with other conductive hearing loss etiologies, such as otosclerosis. Nevertheless, one should be aware of this rare but important differential diagnosis of middle ear lesions. This article presents an MEO case causing conductive hearing loss and outlines the diagnostic approach with computed tomography.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Computed tomography; Conductive hearing loss; Middle ear lesion; Middle ear osteoma; Temporal bone osteoma

Outcome and management of rare high-grade “salivary” adenocarcinoma: the important role of adjuvant (chemo)radiotherapy - Scherl, Claudia; Haderlein, Marlen; Agaimy, Abbas; Mantsopoulos, Konstantinos; Koch, Michael; Traxdorf, Maximilian; Fietkau, Rainer; Grundtner, Philipp; Iro, Heinrich (Strahlentherapie und Onkologie, 2019)
Purpose: To determine survival and management strategies for high-grade adenocarcinoma of salivary glands (ASG). Methods: A retrospective analysis of cases diagnosed between 1998 and 2015 from our single tertiary referral center was performed. Multivariable logistic regression was used to determine factors associated with survival. Results: Thirty-eight cases of high-grade ASG were identified. Most patients were men (68.4%) with a median age of 65.5 years (range 23–84 years). Most tumors were T3 and T4 (65.8%). Regional metastases were common (55.2%), and 42.1% developed distant metastases. The mean follow-up was 60.5 months. All patients received surgery as primary treatment, with 84.2% of patients receiving adjuvant radiation therapy or chemoradiotherapy ([C]RT). Cumulative overall survival was 89.1%, 50.9%, and 20.7% after 1, 5, and 10 years, respectively. Disease-specific survival was 94.4%, 69.8%, and 42.8%, and distant-metastases-free survival (DMFS) was 80.5%, 50.1%, and 40.1% after 1, 5, and 10 years. On multivariable analysis, advanced T status correlated with DMFS (hazard ratio 2.75, 95% CI 0.93–8.16). Postsurgical (C)RT reduced the locoregional recurrence rate by 23.9%, and it improved the locoregional-recurrence-free survival by 39% (p = 0.094). Conclusion: High-grade ASG is considered to have an unfavorable prognosis. Adjuvant (C)RT reduces the rate of locoregional recurrences. Distant metastases are common, and an advanced T stage has increased prognostic value for development of early distant lesions.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Head and neck cancer; Salivary gland cancer; Salivary gland malignancy; Survival salivary gland cancer; Treatment salivary gland cancer

Outcome and prognostic factors in T4a oropharyngeal carcinoma, including the role of HPV infection - Psychogios, Georgios; Mantsopoulos, Konstantinos; Agaimy, Abbas; Brunner, Kathrin; Mangold, Elisabeth; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The prognosis of patients with advanced oropharyngeal carcinoma (OPSCC) is generally poor. The aim of this study is to investigate the different therapeutic approaches and identify prognostic factors associated with a worse outcome for patients treated for T4a OPSCC, in order to improve treatment selection for the individual.A retrospective study was conducted on 426 patients with T4a OPC treated between 1980 and 2010. Eleven prognostic factors including treatment modality, lymph node staging, and p16 status as a surrogate marker for human papillomavirus (HPV) infection were analyzed.Univariate analysis showed a significant difference in DSS between N0 and N+ (57.1% versus 26.9%, P < 0.001), primary surgical and primary nonsurgical treatment (52.7% versus 31.4%, P < 0.001), and perinodal invasion (51.7% versus 19.9%, P = 0.011). P16-negative patients tended towards a worse DSS than p16-positive patients (40.2% versus 64.6%, P = 0.126) but responded better to primary surgery than to nonsurgical treatment (71.4% versus 34.0%, P = 0.113). Multivariate analysis identified the N category as an independent prognostic factor for survival.The survival of p16-negative patients was worse than p16-positive patients, although they seem to respond better to primary surgery. The strongest independent prognostic factor for T4a carcinomas proved to be the presence of lymph node metastases.
EVALuna2:6638

Outcomes of transoral laser microsurgery and transoral robotic surgery in oropharyngeal squamous cell carcinoma - Sievert, Matti; Goncalves, Miguel; Zbidat, Ali; Traxdorf, Maximilian; Müller, Sarina Katrin; Iro, Heinrich; Gostian, Antoniu Oreste (Auris Nasus Larynx, 2020)
Objective: Transoral robotic surgery (TORS) has evolved to a standard therapy modality for oropharyngeal carcinoma, especially in T1/ T2 tumors involving the base of the tongue due to its advantages compared with open surgery. However, knowledge about its benefits compared with transoral laser microsurgery (TLM) are scarce. This study compares oncological and functional results of TLM or TORS in the treatment of oropharyngeal squamous cell carcinoma (OPSCC). Methods: This retrospective analysis comprises all patients with OPSCC treated with TLM (n = 30) or TORS (n = 24) between April 2003 and May 2018 (follow-up 43 ± 38.3 months). Both treatment groups (TLM and TORS) were comparable in terms of the stage of the disease, prognosis-determining factors, and adjuvant therapy modalities. Results: There were no significant differences regarding to the resection status (p = 0.272), the rate of local- (p = 0.834) and distant- recurrence (p = 0.416), with a disease-free survival of 86.7 % and 87.5 %, respectively (p = 0.892). In addition, we could not confirm any differences regarding to operating time (p = 0.860), intraoperative blood loss (p = 0.660), inpatient stay (p = 0.585) and postoperative bleeding rate (p = 0.245). The frequency of tracheostomy and percutaneous endoscopic gastrostomy between both groups is comparable, with a longer duration of tube feeding in patients who have received TLM (p = 0.030). Conclusion: In conclusion, TORS allows for similar oncological outcomes compared with TLM at comparable perioperative risks. The postoperative swallowing function may benefit from TORS.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Head and neck cancer; Oropharyngeal cancer; Primary ablative surgery; Transoral laser microsurgery; Transoral robotic surgery

Pain management after tonsillectomy—by demand or by-the-clock—is there a difference? - Gostian, Magdalena; Stilkerich, Lisa; Pauly, Anne; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Gostian, Antoniu-Oreste; Waldfahrer, Frank (Ent-Ear Nose & Throat Journal, 2022)
Purpose: To improve pain management after tonsillectomy (TE) by comparing individual analgesic management by demand versus a fixed-scheduled analgesic treatment protocol in a prospective trial. Patients and Methods: Forty consecutive patients received individual pain treatment by demand (control group) followed by 40 patients who were treated by a fixed-scheduled four-staged escalating analgesic protocol (intervention group) after TE. Minimum and maximum pain as well as pain on ambulation (NRS 0-10) on the first postoperative day were defined as primary objectives. Secondary endpoints comprised the analgesic score, treatment-related side effects/pain-associated impairments, wish for more pain medication, and patient satisfaction. Patients were surveyed using the standardized and validated “Quality Improvement in Postoperative Pain Treatment” (QUIPS) questionnaire. Results: Patients of the control group reported comparable minimum (2.03 ± 1.42 vs 2.38 ± 1.79, P = 0.337, r = 0.110) and maximum pain (6.65 ± 2.10 vs 6.93 ± 1.86, P = 0.536, r = 0.07) and pain on ambulation (4.73 ± 2.26 vs 5.18 ± 2.19, P = 0.370, r = 0.10) compared to the intervention group. Patients in both groups were comparably well satisfied with the pain treatment (7.53 ± 2.40 vs 7.73 ± 2.30, P = 0.704, r = 0.04), experienced similar side effects and functional impairments (P > 0.050, Φ < 0.3), and did not ask for much more analgesic medication (P = 0.152, Φ = 0.160). Conclusion: Pain control following TE was not distinctly affected by applying a fixed-scheduled analgesic treatment protocol compared to individual analgesic therapy. In conclusion, analgesic treatment after TE remains unsatisfying. Consequently, further efforts are needed to achieve a standardized and effective approach to the underlying pathophysiological causes of pain following TE.
CRIS-Team Scopus Importer:2022-08-05
Keywords: patient reported outcome measure; postoperative pain; quality management; QUIPS

Papillary stenosis of the submandibular gland caused by dental prostheses - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objectives: The aim of this study was to assess diagnosis and treatment of submandibular duct stenosis caused by dental prostheses. Study Design: This retrospective study included 9 patients with papillary stenosis caused by physical irritation of the Wharton duct ostium by a mandibular dental prosthesis. Diagnostics included physical examination, as well as transcutaneous and transoral ultrasound examinations. Treatment consisted of duct incision, papillotomy, and subsequent sialendoscopy. After surgery, patients were advised to have the dental prosthesis altered by the dentist and to have regular gland massage. Follow-up data were obtained via telephone interviews. The most important outcome parameter was a symptom-free state. Results: In all 9 patients, the insertion of the sialendoscope was initially impossible because of the stenosis. After duct incision, sialendoscopy ruled out other obstructive causes and inflammatory states, leaving the dental prosthesis as the only underlying cause of the obstruction. Seven of the 9 treated patients were interviewed after a follow-up period of 28.1 (± 25.4) months. The procedures had resulted in all patients being symptom-free, without any reported complications. Conclusions: Mandibular prostheses can cause stenosis of the papillary region with subsequent submandibular duct obstruction. Surgical therapy is easy to perform and results in excellent long-term outcomes.
CRIS-Team Scopus Importer:2020-03-06

Paradigm shift in surgery for benign parotid tumors: 19 years of experience with almost 3000 cases - Bär, Bianca; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2019)
Objectives: The aim of this study was to explore the changes in philosophy in the surgical therapy of benign parotid tumors over a period of 19 years. Methods: The records of all patients treated for benign parotid tumors between 2000 and 2018 were evaluated. Data were analyzed with respect to the number of procedures carried out per year of the study according to each of the different surgical modalities and the incidence of postoperative complications. Statistical analysis was performed using the x2 test. A P value of <.05 was considered statistically significant. Results: A total of 2988 patients were included in this study. Our analysis showed that the increasing performance of extracapsular dissection was associated with a progressive reduction in the incidence of temporary facial nerve palsy and Frey's syndrome, while the rate of permanent facial nerve palsy remained consistently low. Conclusion: One of the most controversial issues in head and neck surgery is which therapeutic approach is best in patients with benign parotid tumors. Our analysis demonstrated that a change of strategy towards reducing invasiveness was possible, with exceptional functional results. Avoidance of facial nerve dissection is feasible in more than two-thirds of cases with benign tumors. Level of Evidence: 4b. Laryngoscope, 2019.
CRIS-Team Scopus Importer:2019-12-17
Keywords: complete parotidectomy; Extracapsular dissection; facial nerve; Frey's syndrome; superficial parotidectomy

Paragangliomas of the Head and Neck: Local Control and Functional Outcome Following Fractionated Stereotactic Radiotherapy - Weissmann, Thomas; Lettmaier, Sebastian; Roesch, Johannes; Mengling, Veit; Bert, Christoph; Iro, Heinrich; Hornung, Joachim; Janka, Rolf Matthias; Semrau, Sabine; Fietkau, Rainer; Putz, Florian (American Journal of Clinical Oncology-Cancer Clinical Trials, 2019)
Objectives: To investigate local control and functional outcome following state-of-the-art fractionated stereotactic radiotherapy (FSRT) for paragangliomas of the head and neck. Methods: In total, 40 consecutive patients with paragangliomas of the head and neck received conventionally FSRT from 2003 to 2016 at the Department of Radiation Oncology of the University Hospital Erlangen. Local control, toxicities, and functional outcome were examined during follow-up. In total, 148 magnetic resonance imaging studies were subjected to longitudinal volumetric analysis using whole tumor segmentation in a subset of 22 patients. Results: A total of 80.0% (32/40) of patients received radiotherapy as part of their primary treatment. In 20.0% (8/40) of patients, radiation was used as salvage treatment after tumor recurrence in patients initially treated with surgery alone. The median dose applied was 54.0 Gy (interdecile range, 50.4 to 56.0 Gy) in single doses of 1.8 or 2 Gy. Local control was 100% after a median imaging follow-up of 52.2 months (range, 0.8 to 152.9 mo). The volumetric analysis confirmed sustained tumor control in a subset of 22 patients and showed transient enlargement (range, 129.6% to 151.2%) in 13.6% of cases (3/22). After a median volumetric follow-up of 24.6 months mean tumor volume had diminished to 86.1% compared with initial volume. In total, 52.5% (21/40) of patients reported improved symptoms after radiotherapy, 40% (16/40) observed no subjective change with only 7.5% (3/40) reporting significant worsening. Conclusions: State-of-the-art FSRT provides excellent control and favorable functional outcome in patients with paragangliomas of the head and neck. The volumetric analysis provides improved evidence for sustained tumor control.
CRIS-Team Scopus Importer:2019-10-22
Keywords: fractionated stereotactic radiotherapy; functional outcomes; paraganglioma; tumor control; volumetric analysis

Parotid pleomorphic adenomas: Factors influencing surgical techniques, morbidity, and long-term outcome relative to the new ESGS classification in a retrospective study - Schapher, Mirco; Koch, Michael; Agaimy, Abbas; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Journal of Cranio-Maxillofacial Surgery, 2019)
Purpose: To assess long-term results after treatment of parotid pleomorphic adenomas (PPAs) with different surgical techniques, standardized according to the European Salivary Gland Society (ESGS) classification system. Methods: We analyzed ESGS categories, occurrence of facial nerve paresis (FNP), Frey's syndrome, histopathology, and recurrences. Surgical modalities were compared, differentiating techniques with and without facial nerve dissection. A strict protocol ensured a postoperative follow-up-period of more than 7 years. Results: 205 patients were included. A complete follow-up was possible in 138 patients, 77 of whom underwent extracapsular dissection (ED) and 61 of whom had other surgical modalities (OSMs). ESGS categories correlated with the extent of surgery, significantly with the risk for FNP and Frey's syndrome, but not with recurrences. Recurrences did not differ significantly between ED and OSMs, whereas the risks for FNP (p < 0.001 each) and Frey's syndrome (p = 0.000) were significantly higher after OSMs in comparison with ED. Young women with a stroma-rich (myxoid) tumor subtype appear to have the greatest risk for recurrences. Conclusion: ED is the treatment of choice for PPAs, if possible, resulting in similar recurrence rates but significantly fewer comorbidities in comparison with more extensive surgery. After the treatment of PPAs, a long-term follow-up is needed, including imaging.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Extracapsular dissection; Facial nerve paresis; Follow-up; Frey's syndrome; Pleomorphic adenoma; Recurrence

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Pediatric salivary gland tumors and tumor-like lesions - Agaimy, Abbas; Iro, Heinrich; Zenk, J. (Pathologe, 2017)
Salivary gland tumors and tumor-like lesions in the pediatric population are uncommon. They comprise a heterogeneous group of infectious/inflammatory and neoplastic conditions. Pediatric salivary neoplasms include benign tumors of mesenchymal or epithelial origin as well as malignancies of epithelial (carcinomas), mesenchymal (sarcoma) or hematolymphoid (lymphoma) derivation. Infectious/inflammatory conditions and hematolymphoid malignancies may represent either genuine parenchymal pathology or conditions involving intraglandular lymph nodes of the parotid glands (intraglandular lymphadenopathy and intraglandular nodal lymphomas). Pediatric sialadenitis may be of diverse etiologies including viral (mumps, CMV, HIV, etc.), bacterial, autoimmune (juvenile Sjögren syndrome) or idiopathic (chronic recurrent juvenile sialectatic sialadenitis). Angiomatous lesions (juvenile capillary hemangioma, lymphangioma and vascular malformation) and pleomorphic adenomas represent the most common pediatric benign mesenchymal and benign epithelial tumors, respectively. The vast majority of salivary gland carcinomas in children and adolescents represent low-grade mucoepidermoid carcinomas followed by acinic cell and adenoid cystic carcinomas (together >80% of carcinomas). Other malignant neoplasms include (rhabdomyo-) sarcomas, malignant lymphomas and very rarely sialoblastomas. This long differential diagnosis list of etiologically and biologically highly heterogeneous entities, their shared clinical presentation as "salivary gland enlargement" and the significant differences in their therapeutic strategies and prognosis underline the need for careful assessment to identify the correct diagnosis. Diagnosis is mainly based on a set of typical clinical and imaging features, serological/microbiological findings and, in selected cases, histomorphological characteristics in biopsy specimens.
EVALuna2:6863

Perioperative anticoagulation in free microvascular flaps – a comparison of different prophylactic regimes in oncologic reconstructive surgery - Tamse, Henriette; Koch, Michael; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Sievert, Matti (European Review for Medical and Pharmacological Sciences, 2024)
OBJECTIVE: Free tissue transfer has an established place in oncologic head and neck surgery. However, the necessity and specific regimen of perioperative thromboprophylaxis remain controversial. Here, the risk of postoperative hemorrhage contrasts with vascular pedicle thrombosis and graft loss. This work compares three different heparin protocols (AC) with regard to postoperative complications. PATIENTS AND METHODS: A retrospective analysis of our free flap transplants between 2004 and 2023 was conducted. Inclusion criteria were thromboprophylaxis with (A) 500 IU/h unfractionated heparin (UFH), (B) low-molecular-weight heparin (LMWH) once daily, and (C) LMWH once daily with additional immediate preoperative administration. Primary endpoints were the incidence of postoperative bleeding and hematoma and the appearance of flap thrombosis. RESULTS: We evaluated 355 cases, 87 in group A, 179 in group B, and in group C 89 patients. Overall, postoperative bleeding occurred in 8.7% of patients, and 83% underwent hemostasis under intubation anesthesia, with no significant difference between groups (p = 0.784). Hematoma formation requiring revision was found in 3.7% of patients (p = 0.660). We identified postoperative hematoma as a significant influencing factor for venous pedicle thrombosis (OR 3.602; p = 0.001). Venous and arterial flap thrombosis in the graft vessel showed no difference between the groups (p = 0.745 and p = 0.128). CONCLUSIONS: The three anticoagulation regimens appear to be equivalent therapy for the prevention of thrombosis without significant differences in postoperative bleeding. The use of LMWH with additional preoperative administration can, therefore, be administered in free flap reconstruction.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Anticoagulation; Bleeding; Flap thrombosis; Free flap; Hematoma; Heparin; Microvascular reconstruction

Pleomorphic adenoma - become more common in women - Iro, Heinrich (HNO, 2018)
EVALuna2:35390

Pleomorphic adenoma compared with cystadenolymphoma of the parotid gland: which is more common? - Mantsopoulos, K.; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2020)
The aim of this single-institution, observational study was to detect and explain any potential changes in the incidence of pleomorphic adenoma and cystadenolymphoma over a period of 19 years. The records of all patients who were treated for benign parotid tumours between 2000 and 2018 were evaluated and the data analysed to detect any potential changes in the incidence over time. A total of 2988 patients were studied, 1150 of whom had cystadenolymphomas (39%), and 1047 pleomorphic adenomas (35%). The dominance of cystadenolymphomas was first noted during the period 2004–2007 and remained stable throughout the following years (p = 0.05). The predominant incidence of cystadenolymphomas has increased over time and is not expected to change in the next decades.
CRIS-Team Scopus Importer:2020-02-07
Keywords: cystadenolymphoma; parotid gland; pleomorphic adenoma

Pleomorphic adenoma of the parotid gland and the parapharyngeal space: two diametrically opposing surgical philosophies for the same histopathologic entity? - Hornung, Benita; Constantinidis, Jannis; Thimsen, Vivian; Agaimy, Abbas; Koch, Michael; Gostian, Antoniu-Oreste; Sievert, Matti; Müller, Susanna; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Background: The aim of this study was to investigate the histopathologic findings in parotid and parapharyngeal pleomorphic adenomas and draw conclusions concerning the surgical strategy. Methods: Retrospective study of medical charts of patients with resected pleomorphic adenomas (PA) between 2005 and 2020 at two tertiary medical referral centers. Histologic specimens were reexamined by an experienced head and neck pathologist. Patients with insufficient/incomplete data were excluded from our study sample. Results: A total of 844 patients formed our study sample (291 men, 553 women, average age 48.9 years); 786 cases had a PA in the parotid gland (PG) (93.1%), and the remaining 58 cases had a PA in the parapharyngeal space (PS) (6.9%). Recurrences were detected in 8/844 cases (7/786 in the PG, 1/58 in the PS, 0.94% in total) with a mean follow-up time of 86.7 months (10–189 months) with no statistically significant differences between the study groups (p = 0.527). Our analysis showed that parapharyngeal pleomorphic adenomas are characterized by a lower incidence of an intact anatomical capsule (71.4% vs. 82.6%, p = 0.035) and a remarkably more frequent occurrence of satellite nodules (20.7% vs. 7.5%, p < 0.001). Conclusions: The more challenging histopathologic profile of parapharyngeal pleomorphic adenomas points towards the fact that parapharyngeal surgery should remain in the hands of experienced surgeons at high-volume centers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Capsule; Parapharyngeal space; Parotid gland; Pleomorphic adenoma; Pseudopodium; Satellite

Pneumoparotid: Practical impact of Surgeon performed Ultrasound in an effective Diagnostic Approach - Goncalves, Miguel; Sievert, Matti; Mantsopoulos, Konstantinos; Schapher, Mirco; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael (Oral Diseases, 2022)
Objectives: Pneumoparotid is characterized by air inclusions in the parotid duct system. Use of ultrasound has proved valuable for evaluating air inclusions in various parts of the body; the diagnostics of this condition has not been systematically analyzed, however. The aim of this study was to evaluate the value of ultrasound in the detection of air inclusions along the parotid duct system and its closer characterization. Methods: Retrospective analysis was carried out of patients diagnosed with pneumoparotid between 2005 and 2020 in a salivary gland center. Ultrasound was performed in all cases, and features of air inclusions were described. Reference standard was the clinical demonstration of foamy saliva after gland massage and/or sialendoscopic evidence of intraductal air inclusions. Results: Twenty-one patients were identified (48.8 ± 3.8 years). Two were associated with wind instruments; seven were iatrogenic, following treatment for duct stenosis; one after radiotherapy; four with known bruxism and seven were idiopathic and without associated conditions. On ultrasound examination, pneumoparotid was characterized by three phenomena: flattened, mobile hyperechoic reflexes, dirty shadows with reverberation or “sunbeam effect,” and shifting shadows during gland massage. Conclusions: Ultrasound was useful for characterizing pneumoparotid in a fast and practical way and could serve as imaging tool of first choice.
CRIS-Team Scopus Importer:2022-07-15
Keywords: diagnostics; parotid gland; pneumoparotid; ultrasound

Positive factors on survival of head and neck cancer of unknown primary: what the clinician can do - Khalil, Firas; Koch, Michael; Iro, Heinrich; Sievert, Matti; Haderlein, Marlen; Semrau, Sabine; Fietkau, Rainer; Agaimy, Abbas; Scherl, Claudia (Acta Oto-Laryngologica, 2023)
Background: Management of patients with head and neck cancer of unknown primary (HNCUP) is challenging. Aims/Objectives: To provide a long-term analysis focusing on protective survival factors for clinical decision-making. Furthermore, the prognostic value of the current N classification system was evaluated. Material and methods: We retrospectively analyzed patients with HNCUP between 2003 and 2016. Univariate and multivariate analyses were used to investigate predictors of overall survival (OS). Results: A primary tumor was found in 67 of 290 patients with suspected HNCUP, leaving after exclusion 141 HNCUP cases for analysis, who received multi-step therapy (MST) (n = 108) or single therapy (n = 28). Chemotherapy (CT) (n = 101), curative MST, ≤3 positive lymph nodes (LN) (n = 33), squamous cell carcinoma (SCC) (n = 123), HPV+ (n = 21), M0 (n = 70) increased OS by 21.8%, 24.4%, 12.7%, 6.8%, 18.7%, 29.6%, respectively. 5- and 10-year OS was 78.1%/66.6%. The number of metastatic LNs predicted OS is better than N classification. Conclusion and significance: Aspects for clinical decision-making: Curative MST and SCC histology were the most significant predictors for improved OS. Categorizing LN into 1, 2-3, and >3 LNs was more significant than the traditional N classification. The addition of CT to curative MST has a stronger impact on survival than HPV and N classifications.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cancer; cancer of unknown primary; CUP; head and neck; hNCUP; hNSCC; squamous cell carcinoma; survival

Postinflammatory Medial Meatal Fibrosis: Histopathologic Features and Outcomes of Surgical Management - Mantsopoulos, Konstantinos; Thimsen, Vivian; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Goncalves, Miguel; Iro, Heinrich; Agaimy, Abbas; Hornung, Joachim (Ent-Ear Nose & Throat Journal, 2021)
Objectives: The aims of our study were to investigate the clinical and audiometric outcome of the surgical treatment of postinflammatory medial meatal fibrosis (PIMMF) and to review the histopathologic changes in the specimens of the fibrotic plug, in order to try to shed light on the pathogenesis of the disease. Materials and Methods: The clinical records and the histopathologic specimens of all patients who underwent tympanomeatoplasty for PIMMF at the ENT Clinic of the University of Erlangen between 2006 and 2020 were evaluated retrospectively. Results: Thirty-four patients (41 primary surgical procedures) made up our study cohort. Of this, 28 cases were managed by means of meatoplasty and 13 cases with tympanomeatoplasty. The mean preoperative air–bone gap (ABG) was 27.8 dB (10-44 dB). Postoperative ABG was significantly improved compared to preoperative values at both short- and long-term follow-ups (P <.001 for both). No significant difference was noted between short-term and long-term ABG (P =.240). An ABG ≤20 dB was achieved in 65.8% of patients (short term) and 50% (long term). The overall rate of revision surgery for restenosis was 29.3% (12/41). Histopathologic reevaluation of the fibrotic plugs revealed a mosaic of patterns with frequent occurrence of secondary cholesteatoma-like lesions and keloid-like tissue changes. Lichenoid submucosal inflammation and increased ectopic ceruminous gland lobules were seen less frequently. Discussion: The moderate long-term outcome of surgical management and the identification of histologic changes with therapeutic implications might pave the way for alternative nonsurgical treatment options.
CRIS-Team Scopus Importer:2021-04-19
Keywords: air–bone gap; cholesteatoma; keloid; lichen; postinflammatory medial meatal fibrosis

Postlaryngectomy sinonasal squamous cell carcinoma: Case report and review of the literature - Mantsopoulos, Konstantinos; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (Clinical Case Reports, 2020)
Postlaryngectomy sinonasal squamous cell carcinoma, being theoretically associated with exposure to the same risk factors or development of precancerous lesions due to altered nasal physiology, should warrant a thorough head and neck examination.
CRIS-Team WoS Importer:2020-01-21

Postoperative legal disputes involving patients with cochlear implants - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: After the implantation of one or two cochlear implants additional problems often arise concerning the question which further costs have to be covered by statutory insurances or other insurance providers, e.g. within the framework of integration aid. OBJECTIVE: This article provides an overview of judgments rendered by the German social courts. It was investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIAL AND METHODS: A search was made for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear", "Cochlea", "Implant", and "Implantat". The reviewed judgments were issued between 2002 and 2017. RESULTS: A total of 13 judgments were found. The results varied according to the specifics of the individual case and 54% of the patients won their cases. The court procedures took between 2 months (starting from the filing of a complaint, date of application in this case unknown), and 6 years and 11 months. CONCLUSION: This study showed that it is uncertain whether costs that are not caused directly by the surgery or the postoperative treatment will be remunerated. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory insurances or other providers refuse to meet expenses incurred.
EVALuna2:35385

Postoperative management of antithrombotic medication in microvascular head and neck reconstruction: a comparative analysis of unfractionated and low-molecular-weight heparin - Sievert, Matti; Goncalves, Miguel; Tamse, Rosalie; Müller, Sarina Katrin; Koch, Michael; Gostian, Antoniu Oreste; Iro, Heinrich; Scherl, Claudia (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Free flap reconstruction is a valuable technique to preserve function in oncological head and neck surgery. Postoperative graft thrombosis is a dreaded risk. This study aims to compare low-dose unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) in perioperative thrombosis prophylaxis. Methods: This is a retrospective analysis of 266 free flaps performed at our academic center. A comparison was made between 2 patient groups, based on their respective postoperative prophylaxis protocols either with UFH (n = 87) or LMWH (n = 179). Primary endpoints were the frequency of transplant thrombosis and the number of flap failures. Secondary endpoints were the occurrence of peri- and postoperative complications. Results: The flap survival rate was 96.6% and 93.3% for the groups UFH and LMWH, respectively (P = 0.280). The rate of postoperative bleeding requiring revision was 4.6% and 6.7% for each group, respectively (P = 0.498). We found a hematoma formation in 4.6% and 3.9% (P = 0.792). Conclusion: The free-flap survival rate using low-dose UFH seems to be equivalent to LMWH regimens without compromising the postoperative outcome. Consequently, for risk-adapted thrombosis prophylaxis, either LMWH or UFH can be administrated.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Antithrombotic agent; Flap failure; Free-flap reconstruction; Head and neck; Thrombosis

Precautionary documents in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, M.; Balk, Matthias; Rupp, Robin; Hecht, Markus; Ostgathe, Christoph; Müller, Sarina Katrin; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery

Predictive value of FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas: a retrospective study - Fiedler, Mathias; Renner, Patty; Schubert, Juergen; Weber, Florian; Hartmann, Arndt; Iro, Heinrich; Vielsmeier, Veronika; Bohr, Christopher; Gerken, Michael; Reichert, Torsten E.; Ettl, Tobias (Clinical Oral Investigations, 2019)
Objectives: The aim of this study was to investigate the predictive value of the biomarkers FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas. Material and methods: Immunohistochemical staining of FHIT, p27, and pERK1/ERK2 of 265 patients with salivary gland carcinomas was conducted, and associations with clinico-histopathological data, overall survival, and disease-specific survival were examined. Results: Expression of FHIT (quick score 98.7 vs. 206.4) and p27 (QS 187.3 vs. 244.8) was significantly lower in carcinomas compared to non-tumor control tissue. Loss of FHIT frequently occurred in ACC (55.2%), SDC (68.2%), and SCC (100%). In the totality of tumors, loss of FHIT expression was found in 46.7% (106/227) and was significantly associated with advanced T stage and UICC stage, high-grade histology, loss of p27, PI3K, and survivin. FHIT positivity went along with significantly better overall and disease-specific survival. Negativity of p27 occurred in 28.7% (70/244) of tumors, particularly in SDC (54.4%) and SCC (50%). In the totality of tumors, p27 was associated with advanced patient age, high-grade histology, PI3K, survivin as well as better overall and disease-specific survival (p < 0.05). Positive pERK1/ERK2 expression correlated with positive survivin expression but did not affect overall survival in the totality of tumors. In mucoepidermoid carcinomas, pERK1/ERK2 expression was associated with low-grade malignancy, positive nuclear survivin, and better disease-specific survival. Conclusions: Loss of FHIT and p27 characterizes aggressive tumor growth and unfavorable prognosis in salivary gland cancer. Clinical relevance: The results may help to stratify patient-specific therapies according to individual tumor characteristics.
CRIS-Team Scopus Importer:2019-10-25
Keywords: FHIT; p27; pERK1/ERK2; Salivary gland carcinoma

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Predictors of cervical lymph node metastasis in salivary gland cancer - Ettl, Tobias; Gosau, Martin; Brockhoff, Gero; Schwarz-Furlan, Stephan; Agaimy, Abbas; Reichert, Torsten E.; Rohrmeier, Christian; Zenk, Johannes; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
This study compares clinicopathological parameters with novel molecular markers for predicting cervical lymph node metastasis in salivary gland cancer.Three hundred sixteen salivary gland carcinomas were included in this study. Genomic epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), phosphatase and tensin homolog (PTEN), and hepatocyte growth factor receptor (MET) was determined by fluorescence in situ hybridization (FISH). Chi-square tests, multivariate regression, and Kaplan-Meier survival analysis were used for statistics.Nodal staging determines long-term survival. Clinicopathological parameters associated with positive neck nodes are advanced age (p = .006), T3/T4 classification, histological high-grade malignancy, and diagnosis of salivary duct carcinoma (p < .001 each). Neck node metastases also correlate with copy number gain of EGFR (p = .004) and HER2, aberration of MET, and deletion of PTEN (p < .001 each). Multivariate analysis showed SDC (p = .002) to be the strongest predictor of lymph node metastasis, followed by MET aberration (p = .009), T3/T4 classification (p = .017), PTEN deletion (p = .042), and adenocarcinoma not otherwise specified (NOS; p = .047).The histological subtype is crucial for decisions regarding neck dissection. New molecular parameters may also indicate elective treatment of the neck.
EVALuna2:6596

Predictors of olfactory improvement after endoscopic sinus surgery in chronic rhinosinusitis with nasal polyps - Hernandez, A. K.; Wendler, Olaf; Mayr, Susanne; Iro, Heinrich; Hummel, T.; Müller, Sarina Katrin (Journal of Laryngology and Otology, 2022)
Objective. This study aimed to determine the predictors of olfactory improvement after endoscopic sinus surgery among patients with chronic rhinosinusitis with nasal polyps.
CRIS-Team WoS Importer:2023-04-21

Primary parotid gland lymphoma: pitfalls in the use of ultrasound imaging by a great pretender - Mantsopoulos, Konstantinos; Koch, M.; Fauck, Vanessa; Schinz, Katharina; Schapher, Mirco; Constantinidis, J.; Rösler, Wolf; Iro, Heinrich (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to highlight several misleading imaging and clinical aspects of parotid gland lymphoma, taking our personal experience and relevant literature reports into consideration. The records of all patients diagnosed with lymphoma in the parotid gland between 2005 and 2017 were examined retrospectively. Sixty-seven patients were included in this study. The mean age was 61.4 years. The most frequent histological entities were marginal zone B-cell lymphoma (31.3%) and follicular lymphoma (28.4%). The tumour was stage I in 35 cases (52.2%), stage II in 13 cases (19.4%), stage III in 11 cases (16.4%), and stage IV in eight cases (11.9%). B symptoms were seen in only three patients (4.5%). The diagnosis was made after parotidectomy in 51 cases (76.1%), by core needle biopsy in 14 cases (20.9%), and by means of open biopsy in the remaining two cases (3.0%). Parotid gland lymphoma represents a diagnostically challenging, multifaceted entity that can easily mimic both benign and malignant conditions. This entity should be included in the differential diagnosis of almost all types of parotid lesion, as it seems to play the role of a great pretender.
CRIS-Team Scopus Importer:2021-04-19
Keywords: diffuse large B-cell lymphoma; follicular lymphoma; lymphoma; MALT lymphoma; marginal zone B-cell lymphoma; parotid gland; parotidectomy; ultrasound

Primary results of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) with double checkpoint blockade and radiotherapy dependent on intratumoral CD8+T-cell infiltration. - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias G.; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Frey, Benjamin; et al. (ASCO 2021 Annual Meeting, 2021)
CRIS-Team WoS Importer:2021-11-26

Primary Results of the phase II CheckRad-CD8 Trial: First-Line Treatment of locally advanced Head and Neck Tumors with double Checkpoint Blockade and Radiotherapy dependent on intratumoral CD8+T-Cell Infiltration - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Klautke, G.; Laban, S.; Hautmann, M.; Brunner, T.; Tamaskovics, B.; Hinke, A.; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Primary surgical therapy for locally limited oral tongue cancer - Mantsopoulos, Konstantinos; Psychogios, Georgios; Kuenzel, Julian; Waldfahrer, Frank; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The aim of this study was to assess the efficacy of primary surgical treatment in the management of locally limited oral tongue carcinoma.A retrospective evaluation was carried out for all patients treated with primary surgery for pT1-pT2 oral tongue carcinomas at a tertiary referral center between 1980 and 2005. All cases were assessed for disease-specific survival and local control rates in relation to T classification, N classification, infiltration depth of the primary tumor, and decision making on neck management and adjuvant therapy. The cases were additionally evaluated for the incidence of major complications and tracheotomies.263 cases were assessed. The 5-year disease-specific survival rate was 75.2%. Positive neck disease was shown to be a significant negative prognostic factor. The occult metastasis rate was 20.2%.Primary surgical treatment is a very effective modality against T1-T2 oral tongue carcinoma, and a low rate of complications can be anticipated.
EVALuna2:19930

Probe-based confocal laser endomicroscopy in detecting malignant lesions of vocal folds. - Goncalves, Miguel; Aubreville, Marc; Müller, Sarina Katrin; Sievert, Matti; Maier, Andreas; Iro, Heinrich; Bohr, Christopher (Acta Otorhinolaryngologica Italica, 2019)
Probe-based confocal laser endomicroscopy (CLE) is an innovative technique for real-time, non-invasive analysis of the surface epithelium. While being successfully used for diagnosis by experts, this method has not yet been established in clinical routine, partly due to the lack of standards and criteria for classifying various lesions. Our aim was to determine the diagnostic value and inter-rater reliability of CLE in detecting malignant lesions of the vocal cords. 58 video sequences were extracted from the probe-based CLE (GastroFlex probe with a Cellvizio® laser system) examinations of 3 patients with squamous cell carcinomas and 4 patients with benign alterations of the vocal folds. Two ENT surgeons, who were blinded to the histological result, were asked to identify the sequences representing a carcinoma. We showed an accuracy, sensitivity, specificity, PPV and NPV of 91.38-96.55%, 100%, 87.8-95.2%, 77.27-89.47% and 100%, respectively, with an inter-rater reliability of k = 0.89 ("almost perfect agreement"). Probe-based CLE is a promising method for diagnosis and assessment of vocal fold lesions in vivo. Our results suggest that, with adequate training, the diagnostic value of this technique can be improved and potentially provide important information during oncological surgery.

Prognostic value of O-6-methylguanine-DNA methyltransferase loss in salivary gland carcinomas - Scesnaite, Asta; Jarmalaite, Sonata; Müller, Maximilian; Agaimy, Abbas; Zenk, Johannes; Hartmann, Arndt; Iro, Heinrich; Peters, Brigitte; Schwarz, Susanne; Schneider-Stock, Regine (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
The purpose of this study was to determine the prognostic value of O-6-methylguanine-DNA methyltransferase (MGMT) inactivation in a group of 286 patients with salivary gland carcinoma and matched histologically normal tissues.MGMT promoter methylation was studied in 36 patients with salivary gland carcinoma and 19 histologically matched normal tissues by pyrosequencing. MGMT protein expression was examined in 286 patients with salivary gland carcinomas and histologically matched normal tissues by immunohistochemistry on tissue microarrays. The results were correlated to demographic, clinicopathologic parameters, and disease follow-up data.MGMT hypermethylation was significantly (p = .021) associated with the protein loss. MGMT loss was found in 39.2% of salivary gland carcinomas and was predominant in aggressive tumors (poorly differentiated, grade III, regional lymph node involved). MGMT loss significantly (p = .004) predicted poor clinical outcome of salivary gland carcinomas and defined high-risk subgroups in clinically favorable tumor groups.We suggest that immunohistochemical evaluation of nuclear MGMT protein might serve as a tool for the prediction of overall survival in patients with salivary gland carcinoma.
EVALuna2:6616

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy

Radiotherapy for the elderly Patient with Head and Neck Squamous Cell Carcinoma - Experience of a Center for ENT-Tumors - Winkler, Leah-Sophie; Lettmaier, Sebastian; Semrau, Sabine; Müller, Sarina Katrin; Traxdorf, Maximilian; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radiotherapy with paclitaxel/cisplatin vs. fluorouracil/cisplatin for head and neck cancer - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Iro, Heinrich; Gefeller, Olaf; Roedel, C.; Hautmann, M.; Koelbl, O.; Salay, A.; Ruebe, C.; Breinl, P.; Krings, W.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Randomized phase-III-trial of concurrent chemoradiation for locally advanced head and neck cancer comparing dose reduced radiotherapy with paclitaxel/cisplatin to standard radiotherapy with fluorouracil/cisplatin: The PacCis-trial - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Lubgan, Dorota; Iro, Heinrich; Gefeller, Olaf; Rödel, Claus; Hautmann, Matthias G.; Kölbl, Oliver; Salay, Attila; Rübe, Christian; Melchior, Patrick; et al. (Radiotherapy and Oncology, 2020)
Background and purpose: This multicenter, phase 3 trial investigates whether the incorporation of concurrent paclitaxel and cisplatin together with a reduced total dose of radiotherapy is superior to standard fluorouracil–cisplatin based CRT. Materials and methods: Patients with SCCHN, stage III–IVB, were randomized to receive paclitaxel/cisplatin (PacCis)–CRT (arm A; paclitaxel 20 mg/m2 on days 2, 5, 8, 11 and 25, 30, 33, 36; cisplatin 20 mg/m2, days 1–4 and 29–32; RT to a total dose of 63.6 Gy) or fluorouracil/cisplatin (CisFU)–CRT (arm B; fluorouracil 600 mg/m2; cisplatin 20 mg/m2, days 1–5 and 29–33; RT: 70.6 Gy). Endpoint was 3-year-disease free survival (3y-DFS). Results: A total of 221 patients were enrolled between 2010 and 2015. With a median follow-up of 3.7 years, 3y-DFS in the CisFU arm and PacCis arm was 58.2% and 48.4%, respectively (HR 0.82, 95% CI 0.56–1.21, p = 0.52). The 3y-OS amounted to 64.6% in the CisFU arm, and to 59.2% in the PacCis arm (HR 0.82, 95% CI 0.54–1.24, p = 0.43). In the subgroup of p16-positive oropharyngeal carcinomas, 3y-DFS and 3y-OS was 84.6% vs 83.9% (p = 0.653), and 92.3% vs. 83.5% (p = 0.76) in arm A and B, respectively. Grade 3–4 hematological toxicities were significantly reduced in arm A (anemia, p = 0.01; leukocytopenia, p = 0.003), whereas grade 3 infections were reduced in arm B (p = 0.01). Conclusion: Paclitaxel/cisplatin–CRT with a reduced RT-dose is not superior to standard fluorouracil/cisplatin–CRT. Subgroup analyses indicate that a reduced radiation dose seems to be sufficient for p16+ oropharyngeal cancer or non-smokers. Clinical trial information: NCT01126216; EudraCT Number 2005-003484-23.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Chemoradiotherapy; Cisplatin; Fluorouracil; Head and neck cancer; Paclitaxel

Rare manifestation of non-Hodgkin lymphoma of the head & neck following cochlear implant surgery - Gehrking, Mika; Miksch, Malin; Agaimy, Abbas; Iro, Heinrich; Sievert, Matti (Otolaryngology Case Reports, 2024)
Background: Lymphomas are the second most common malignant neoplasm in the head & neck region (H&N). This report describes a rare cutaneous manifestation of non-Hodgkin lymphoma (NHL) after cochlear implant (CI) surgery. Case presentation: A 71-year-old female presented to the university hospital with an ulcerative retroauricular lesion. The lesion had developed over a week at the site of prior incision for CI surgery 5 years ago and revision surgery due to device failure 16 months ago. The patient's history is notable for NHL with cervical lymphadenopathy and tonsillar manifestation treated with Ibrutinib. A delayed infection after CI surgery is suspected. Histopathologic examination shows infiltration of NHL cells. Conclusion: Lymphomas display variable clinical presentation in the head & neck. A history of trauma may delay the diagnosis. A locus minoris resistentiae may be created at those sites and allow lymphoma cells to accumulate. Thorough analysis of the patient's medical history is therefore crucial. Suspicious findings in the head and neck should be biopsied timely and a histopathologic examination should be conducted.
CRIS-Team Scopus Importer:2024-11-08
Keywords: CLL; Cochlear implant; Head & neck; Non-hodgkin lymphoma

Reconstruction of the Oral Commissure With the Zisser Flap - Mantsopoulos, Konstantinos; Iro, Heinrich; Constantinidis, Jannis (Journal of Oral and Maxillofacial Surgery, 2019)
The aim of this study was to investigate the role of the Zisser flap in the reconstruction of defects of the oral commissure. We describe our personal experience with this method and present some interesting aspects from the relevant literature. We retrospectively evaluated the records, from the period between 2003 and 2017, of all patients with defects of the oral commissure after resection of malignant tumors, traumas, or burns and reconstruction by means of the Zisser flap. We looked for information on the origin of the commissural defect, method of vermillion reconstruction using the lingual or buccal mucosa, functional result, esthetic outcome, and postoperative complications. The functional result of the reconstruction of the oral commissure was assessed regarding postoperative subjective speech integrity, preservation of competence of the oral sphincter, and lip sensation. The esthetic outcome was evaluated regarding limitations in facial expression and scar formation. The study included 13 patients. The follow-up period in the oncologic cases was 63.2 months (range, 10 to 140 months). No tumor recurrences were detected. Vermillion reconstruction was achieved by means of a buccal mucosal flap in 11 cases and a lingual mucosal flap in 2. All patients achieved normal oral competence and mouth opening except for 1 case, in which secondary commissuroplasty with restoration of sphincter function was needed. No cases of blunting or microstomia were detected. Reconstruction of the oral commissure with the Zisser flap is associated with an outstanding functional outcome that is cosmetically very acceptable.
CRIS-Team Scopus Importer:2019-05-24

Recurrent Mutations within the Amino-Terminal Region of ?-Catenin Are Probable Key Molecular Driver Events in Sinonasal Hemangiopericytoma - Haller, Florian; Bieg, Matthias; Moskalev, Evgeny; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Diessl, Nicolle; Braumandl, Karin; Brors, Benedikt; Iro, Heinrich; Hartmann, Arndt; Wiemann, Stefan; et al. (American Journal of Pathology, 2015)
Sinonasal hemangiopericytoma (SN-HPC) is an uncommon, site-specific, low-grade mesenchymal neoplasm of probable perivascular myoid cell origin. In contrast to solitary fibrous tumors of soft tissue and sinonasal tract origin, SN-HPCs were recently shown to lack recurrent NAB2-STAT6 fusion variants. Other molecular alterations known to occur in some of soft tissue perivascular myoid cell neoplasms were also absent in SN-HPC; thus, the molecular pathogenesis of SN-HPCs remained unknown. Guided by whole-genome sequencing combined with RNA sequencing of an index case, we analyzed a total of six SN-HPCs for mutations within the amino-terminal region of the gene CTNNB1 (cadherin-associated protein), ? 1, 88 kDa, encoding ?-catenin. All six cases showed missense mutations, with amino acid substitutions clustering at positions 33 to 45, corresponding to the recognition site of the ?-catenin destruction complex. Similar CTNNB1 mutations have been described in a variety of epithelial and mesenchymal neoplasms. These mutations prevent ?-catenin phosphorylation and proteasomal degradation but promote its nuclear accumulation and subsequent increased transcription of Wingless-related integration site target genes. Consistent with these molecular findings, ?-catenin IHC showed consistent diffuse and strong nuclear staining of the tumor cells in all six SN-HPCs. Our results highlight, for the first time, CTNNB1 mutations as the likely initiating molecular events driving SN-HPC tumorigenesis, which places SN-HPC among the growing family of ?-catenin-driven mesenchymal neoplasms.
EVALuna2:6646

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Refinement of the surgical indication and increasing expertise are associated with a better quality of pathology specimen in pleomorphic adenomas - Mantsopoulos, Konstantinos; Iro, Ann Kristin; Sievert, Matti; Müller, Sarina Katrin; Agaimy, Abbas; Koch, Michael; Iro, Heinrich (Acta Oto-Laryngologica, 2021)
Background: Traditional surgical philosophy condemns extracapsular dissection for pleomorphic adenoma as a euphemism for the enucleation of this lesion. Objectives: The aims of the study were to trace the development of surgical treatment by pleomorphic adenomas of the parotid gland over the last 15 years and explore its effects on the histopathology specimen. Materials and Methods: The medical records of all cases with pleomorphic adenomas of the parotid gland between 2006 and 2020 were examined for information on age, gender, and type of surgery. An experienced head and neck pathologist re-evaluated the histology slides from all the cases. Results: The study included 844 patients. Our analysis showed an increase in the performance of extracapsular dissection from 52.8% (2006) to 63.3% (2020), and an increase in histopathology specimens with tumours completely covered by healthy tissue from 27.7% (2006) to 50% (2020). Conclusions: Our decision-making process reached its peak in the last study years, in terms of reduced surgical invasiveness and quality of the pathology specimen. Significance: Extracapsular dissection has gained a firm hold as an indispensable tool for the experienced parotid surgeon. Proper indication is based on careful selection of cases and the correct interpretation of preoperative features on palpation and imaging.
CRIS-Team Scopus Importer:2021-01-29
Keywords: capsule; extracapsular dissection; facial nerve; Parotid gland; pathology; pleomorphic adenoma; pleomorphic adenoma

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina Katrin Ursel; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (BMC Cancer, 2021)
Introduction In contrast to head and neck squamous cell carcinoma (HNSCC), the effect of treatment duration in HNSCC-CUP has not been thoroughly investigated. Thus, this study aimed to assess the impact of the time interval between surgery and adjuvant therapy on the oncologic outcome, in particular the 5-year overall survival rate (OS), in advanced stage, HPV-negative CUPs at a tertiary referral hospital. 5-year disease specific survival rate (DSS) and progression free survival rate (PFS) are defined as secondary objectives. Material and methods Between January 1st, 2007, and March 31st, 2020 a total of 131 patients with CUP were treated. Out of these, 59 patients with a confirmed negative p16 analysis were referred to a so-called CUP-panendoscopy with simultaneous unilateral neck dissection followed by adjuvant therapy. The cut-off between tumor removal and delivery of adjuvant therapy was set at the median, i.e. patients receiving adjuvant therapy below or above the median time interval. Results Depending on the median time interval of 55 days (d) (95% CI 51.42-84.52), 30 patients received adjuvant therapy within 55 d (mean 41.69 d, SD = 9.03) after surgery in contrast to 29 patients at least after 55 d (mean 73.21 d, SD = 19.16). All patients involved in the study were diagnosed in advanced tumor stages UICC III (n = 4; 6.8%), IVA (n = 27; 45.8%) and IVB (n = 28; 47.5%). Every patient was treated with curative neck dissection. Adjuvant chemo (immune) radiation was performed in 55 patients (93.2%), 4 patients (6.8%) underwent adjuvant radiation only. The mean follow-up time was 43.6 months (SD = 36.7 months). The 5-year OS rate for all patients involved was 71% (95% CI 0.55-0.86). For those patients receiving adjuvant therapy within 55 d (77, 95% CI 0.48-1.06) the OS rate was higher, yet not significantly different from those with delayed treatment (64, 95% CI 0.42-0.80; X-(1)(2) = 1.16, p = 0.281). Regarding all patients, the 5-year DSS rate was 86% (95% CI 0.75-0.96). Patients submitted to adjuvant treatment in less than 55 d the DSS rate was 95% (95% CI 0.89-1.01) compared to patients submitted to adjuvant treatment equal or later than 55 d (76% (95% CI 0.57-0.95; X-(1)(2) = 2.32, p = 0.128). The 5-year PFS rate of the entire cohort was 72% (95% CI 0.59-0.85). In the group < 55 d the PFS rate was 78% (95% CI 0.63-0.94) and thus not significantly different from 65% (95% CI 0.45-0.85) of the group >= 55 d; (X-(1)(2) = 0.29, p = 0.589). Conclusions The results presented suggest that the oncologic outcome of patients with advanced, HPV-negative CUP of the head and neck was not significantly affected by a prolonged period between surgery and adjuvant therapy. Nevertheless, oncologic outcome tends to be superior for early adjuvant therapy.
CRIS-Team WoS Importer:2021-12-03

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller, Sarina Katrin; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Response to Letter to the editor: Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis: Methodological Issues. Interrater Reliability of Ultrasound: Methodological Issues - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
CRIS-Team Scopus Importer:2019-10-18

Results of contralateral anastomosis of microvascular free flaps in head and neck reconstruction - Gschoßmann, Juliane; Balk, Matthias; Rupp, Robin; Müller-Hübner, Sarina Katrin Ursel; Allner, Moritz; Sievert, Matti; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2022)
Objectives: Despite various solutions to the issue of ipsilateral vessel-depleted neck in microvascular head and neck reconstruction, concrete data on its safety and implementation are scarce. This paper focuses on the feasibility and success rates of contralateral anastomosis in free flap reconstruction in the head and neck region. Methods: This single-center retrospective study at a tertiary referral center includes all patients who underwent free flap reconstruction of the head and neck with contralateral anastomosis between January 1st, 2007 and February 28th, 2021. Primary objectives were frequency, success, and flap-associated complication rates. Secondary objectives were recipient vessels and flap type. Results: Of 318 patients who underwent microvascular reconstruction, anastomosis was performed on the contralateral side of the neck in 32 patients (10.0%). Recipient vessels involved mainly the superior thyroid artery (74.2%; n = 23) and the facial vein (51.1%; n = 23). Thirty patients (93.8%) received a radial forearm free flap. Flap-associated complications occurred in 12.5% of included cases (n = 4): one partial flap necrosis (3.1%), one anastomotic insufficiency (3.1%), one venous thrombosis of the microvascular pedicle (3.1%), and one wound dehiscence (3.1%). All of these complications were resolved without complete flap loss. Conclusion: This study demonstrates that contralateral anastomosis is a successful and safe option in microvascular head and neck reconstruction, especially using a radial forearm free flap. Thus, anastomosing to the contralateral side of the neck can be advocated as a valuable option in the ipsilateral vessel-depleted neck.
CRIS-Team Scopus Importer:2022-07-15
Keywords: contralateral anastomosis; free flaps; head and neck cancer; microvascular reconstruction; recipient vessels; vessel-depleted neck

Rezidivierende retroaurikuläre Entzündungen - Rupp, Robin; Iro, Heinrich; Hornung, Joachim (Laryngo-Rhino-Otologie, 2020)
CRIS-Team Scopus Importer:2020-06-30

Risk of magnetic resonance imaging-induced magnet dislocation for different types of cochlear implants: a single-center retrospective study - Rupp, Robin; Balk, Matthias; Sievert, Matti; Leibl, Victoria; Schleder, Stephan; Allner, Moritz; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim; Gostian, Antoniu-Oreste (Journal of Otolaryngology-Head & Neck Surgery, 2023)
Background: When performing magnetic resonance imaging (MRI) in patients with a cochlear implant (CI), complication rates vary widely in the literature. The primary objective of this retrospective study was to determine the prevalence of complications, in particular magnet dislocation, in patients with CI undergoing 1.5 Tesla (T) MRI. As a secondary objective, the prevalence of magnet dislocation for specific cochlear implant device types was elaborated. Methods: In a single-center retrospective study, all patients with a cochlear implant presenting for an MRI examination at 1.5 T at our institution between January 1st, 2010 and December 31st, 2020 were included. Implants with axial and diametrical magnets were included in the study. MRI safety measures were applied before imaging. The prevalence of complications was evaluated. Magnet dislocation rates were calculated for device types with at least 20 MRI exposures. Results: During the study period, 196 MRI examinations were performed in a total of 128 patients, accounting for 149 different implants (21 implanted bilaterally) with a total of 231 implant exposures to MRI (average 1.69 ± 1.57; min. 1, max. 12). Complications were reported in 50 out of 231 cochlear implant exposures (21.6%). Magnet dislocation occurred in a total of 27 cases (11.7%). Dislocation rates were 29.6% for the Cochlear® CI500 series (24 dislocations from 81 exposures), 1.1% for the Cochlear® CI24RE series (1 from 87) and 0% for the MED-EL® Synchrony (0 from 36). The dislocation rate for the CI500 was significantly higher than for the CI24RE (χ2(1) = 26.86; p < 0.001; ϕ = 0.40) or the Synchrony (χ2(1) = 13.42; p < 0.001; ϕ = 0.34). Conclusions: For 1.5 T MRI, the risk of magnet dislocation ranges from 0 to 29.6% and depends on the CI device type. Implants with a diametrical magnet can be considered potentially MRI-safe, whereas in CIs with axial magnets, the CI500 is at high risk of magnet dislocation. Therefore, apart from a strict indication for an MRI and adherence to safety protocols, post-MRI follow-up examination to rule out magnet dislocation is recommended. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-05-05
Keywords: CI24RE; CI500; Cochlear implant; Complication; Magnet dislocation; Magnet repositioning; Magnetic resonance imaging; Synchrony

Risk stratification of thyroid nodules: Assessing the suitability of ChatGPT for text-based analysis - Sievert, Matti; Conrad, Olaf; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Richter, Daniel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (American Journal of Otolaryngology, 2024)
Purpose: Accurate risk stratification of thyroid nodules is essential for optimal patient management. This study aimed to assess the suitability of ChatGPT for risk stratification of thyroid nodules using a text-based evaluation. Methods: A dataset was compiled comprising 50 anonymized clinical reports and associated risk assessments for thyroid nodules. The Chat Generative Pre-trained Transformer (ChatGPT) was used to classify sonographic patterns in accordance with the Thyroid Imaging Reporting and Data System (TI-RADS). The model's performance was assessed using various criteria, including sensitivity, specificity, and accuracy. A comparative analysis was conducted, evaluating the model against investigator-based risk stratification as well as histology. Results: With an overall agreement rate of 42 % in comparison with examiner-based evaluation (TI-RADS 1–5), the results show that ChatGPT has moderate potential for predicting the risk of malignancy in thyroid nodules using text-based reports. The chatbot model achieved a sensitivity of 86.7 %, a specificity of 10.7 %, and an overall accuracy of 68 % when distinguishing between low-risk (TI-RADS 2 and 3) and high-risk (TI-RADS 4 and 5) categories. Interrater reliability was calculated with a Cohen's kappa of 0.686. Conclusion: This study highlights the potential of ChatGPT in assisting clinicians with risk stratification of thyroid nodules. The results suggest that ChatGPT can facilitate personalized treatment decisions, although the agreement rate is still low. Further research and validation studies are necessary to establish the clinical applicability and generalizability of ChatGPT in routine practice. The integration of ChatGPT into clinical workflows has the potential to enhance thyroid nodule risk assessment and improve patient care.
CRIS-Team Scopus Importer:2024-01-19
Keywords: AI; ChatGPT; Risk stratification; Thyroid nodules; Ultrasound

Role of extracapsular dissection in surgical management of benign parotid tumors - Iro, Heinrich; Zenk, Johannes (JAMA Otolaryngology - Head and Neck Surgery, 2014)
Hypothesis: Extracapsular dissection is a safe and effective surgical technique in the management of benign parotid neoplasms.
EVALuna2:19938

Role of ultrasonography in the detection of a subperiosteal abscess secondary to mastoiditis in pediatric patients - Mantsopoulos, Konstantinos; Wurm, Jochen; Iro, Heinrich; Zenk, Johannes (Ultrasound in Medicine and Biology, 2015)
The aim of the study described here was to evaluate experience in the diagnosis of a subperiosteal abscess secondary to mastoiditis by means of ultrasound. Ten consecutive cases in which an ultrasound examination of the retro-auricular region was performed for suspected mastoiditis were identified. In nine cases, we found a poorly demarcated, inhomogeneous, irregular, poorly perfused lesion abutting the outer table of the cranial vault, with elevation of the outer periosteum and a clearly delineated defect of the cortical layer. In one case, there was additional invasion of the insertion of the sternocleidomastoid muscle on the mastoid process of the temporal bone, raising the suspicion of Bezold mastoiditis. Ultrasound may help in selecting patients for further imaging and might spare computer tomography, especially in sensitive patient groups such as children and pregnant women, if a defect of the outer cortex of the temporal bone can be excluded with certainty.
EVALuna2:19981

Safety and efficacy of single cycle induction treatment with cisplatin/docetaxel/ durvalumab/tremelimumab in locally advanced HNSCC: first results of CheckRad-CD8 - Hecht, Markus; Gostian, Antoniu Oreste; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias Günther; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Hinke, Axel; Becker, Ina; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: To determine safety and efficacy of single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab in stage III-IVB head and neck cancer. METHODS: Patients received a single cycle of cisplatin 30 mg/m² on days 1-3 and docetaxel 75 mg/m² on day 1 combined with durvalumab 1500 mg fix dose on day 5 and tremelimumab 75 mg fix dose on day 5. Patients with pathologic complete response (pCR) in the rebiopsy after induction treatment or at least 20% increase of intratumoral CD8+ cell density in the rebiopsy compared with baseline entered radioimmunotherapy with concomitant durvalumab/tremelimumab. The objective of this interim analysis was to analyze safety and efficacy of the chemoimmunotherapy-induction treatment before radioimmunotherapy. RESULTS: A total of 57 patients were enrolled, 56 were treated. Median pretreatment intratumoral CD8+ cell density was 342 cells/mm². After induction treatment, 27 patients (48%) had a pCR in the rebiopsy and further 25 patients (45%) had a relevant increase of intratumoral CD8+ cells (median increase by a factor of 3.0). Adverse event (AE) grade 3-4 appeared in 38 patients (68%) and mainly consisted of leukopenia (43%) and infections (29%). Six patients (11%) developed grade 3-4 immune-related AE. Univariate analysis computed p16 positivity, programmed death ligand 1 immune cell area and intratumoral CD8+ cell density as predictors of pCR. On multivariable analysis, intratumoral CD8+ cell density predicted pCR independently (OR 1.0012 per cell/mm², 95% CI 1.0001 to 1.0022, p=0.016). In peripheral blood CD8+ cells, the coexpression of programmed death protein 1 significantly increased especially in patients with pCR. CONCLUSIONS: Single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab is feasible and achieves a high biopsy-proven pCR rate.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CD8-Positive T-lymphocytes; clinical trials; combined modality therapy; head and neck neoplasms; Phase II as topic; radioimmunotherapy

Salivary duct carcinoma of the sinonasal cavity: A case report and review of the literature - Müller, Sandra; Mantsopoulos, Konstantinos; Iro, Heinrich; Agaimy, Abbas (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
Salivary duct carcinoma is a rare, aggressive tumor entity first described by Kleinsasser et al in 1968, as a group of malignant salivary gland tumors characterized by duct formation and central necrosis. A case with an unusual localization in the nasal cavity and maxillary sinus is being described in our report.A 60-year-old patient presented with difficulty of nasal breathing and recurrent episodes of epistaxis from the left nasal cavity over the previous 3 months. On endoscopy, a vulnerable lesion in the left inferior nasal meatus could be seen. Biopsy showed salivary duct carcinoma. Treatment consisted of tumor resection by means of a combined endoscopic-osteoplastic surgical approach to the maxillary sinus, bilateral neck dissection, partial parotidectomy, and adjuvant radiochemotherapy.The patient is 6 months after completion of treatment and is free of disease.As salivary duct carcinoma of the sinonasal tract is extremely rare, no therapeutic standards have been developed and treatment essentially is based upon experience with ductal adenocarcinoma of the salivary glands. Surgery therapy should be radical, aiming at eradicating locoregional disease with the role of adjuvant radiotherapy lying in the management of cases with negative prognostic factors. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2464-E2466, 2016.
EVALuna2:6924

Salivary duct stenosis: diagnosis and treatment - Koch, Matthias; Iro, Heinrich (Acta Otorhinolaryngologica Italica, 2017)
The management of stenoses of the major salivary glands had undergone a significant change during the last 15-20 years. Accurate diagnosis forms the basis of adapted minimal invasive therapy. Conventional sialography and MR-sialography are useful examination tools, and ultrasound seems to be a first-line investigational tool if salivary duct stenosis is suspected as cause of gland obstruction. Sialendoscopy is the best choice to establish final diagnosis and characterise the stenosis in order to plan accurate treatment. In all major salivary glands, inflammatory stenosis can be distinguished from fibrotic stenosis. In the parotid duct system, an additional stenosis associated with various abnormalities of the duct system has been reported. Conservative therapy is not sufficient in the majority of cases. The development of a minimally invasive treatment regime, in which sialendoscopy plays a major role, has made the preservation of the gland and its function possible in over 90% of cases. Ductal incision procedures are the most important measure in submandibular duct stenoses, but sialendoscopy becomes more important in the more centrally located stenoses. Sialendoscopic controlled opening and dilation is the dominating method in parotid duct stenoses. In 10-15% of cases, success can be achieved after a combined treatment regime had been applied. This review article aims to give an overview on the epidemiology, diagnostics and current state of the art of the treatment of salivary duct stenoses.
EVALuna2:33183

Salivary gland carcinoma (SGC) with perineural spread and/or positive resection margin - High locoregional control rates after photon (chemo) radiotherapy - Experience from a monocentric analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Putz, Florian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Radiation Oncology, 2019)
Background: The aim was to evaluate the outcome, especially locoregional control of patients with locally advanced salivary gland carcinoma (SGC) with perineural spread (Pn1) and/or positive resection margins (R1/2) after postoperative photon (chemo) radiotherapy in a single centre. Methods: We retrospectively reviewed data of 65 patients with newly diagnosed locally advanced SGC without distant metastases who underwent radio (chemo) therapy in the department of radiation oncology of the university hospital of Erlangen from January 2000 until April 2017. Kaplan Meier method was used to calculate survival and recurrence rates. In univariate analysis the log-rank test was used to correlate patient-/tumor- and treatment-related parameters to survival and recurrence rates. Results: Median follow-up was 45 months (range: 6; 215). After 1, 3, 5 years cumulative incidence of local and locoregional failure was 3.1, 7.0, 7.0% and 3.1, 9.7, 12.9%, whereas cumulative incidence of distant metastases (DM) was 15.6, 36.0, 44.0%. After 1,3, 5 years cumulative Overall (OS) and Disease-free survival (DFS) was 90.5, 74.9, 63.9% and 83.0, 54.8, 49.4%. The only significant predictor for decreased local and locoregional control was a macroscopic resection margin(R2) (p = 0.002 and p = 0.04). High-grade histology (p = 0.006), lymph node metastases with extracapsular spread (p = 0.044) and an advanced T-stage (p = 0.031) were associated with an increased rate of DM. High-grade histology was the only factor predicting for a decreased DFS (p = 0.014). Conclusion: Photon radiotherapy leads to high local and locoregional control rates in a high-risk patient population with SGC with microscopically positive resection margins and/or perineural spread. The most common site of disease recurrence was distant metastases. Therefore the real challenge for the future should be to prevent distant metastases.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Locoregional control; Perineural spread; Photon radiotherapy; Positive resection margin; Salivary gland cancer

Salvage laryngectomy after primary radio- and radiochemotherapy : A retrospective study - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Müller, Sarina Katrin; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
BACKGROUND: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. OBJECTIVE: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors' academic cancer center. MATERIALS AND METHODS: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. RESULTS: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5) . One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. CONCLUSION: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Salvage-Laryngektomie nach primärer Radio- und Radiochemotherapie: Eine retrospektive Fallzusammenfassung - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Müller, Sarina Katrin; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
Background: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. Objective: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors’ academic cancer center. Materials and methods: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. Results: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5). One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. Conclusion: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Satellite nodules in pleomorphic adenomas of the parotid gland: A nightmare for less invasive parotid surgery? - Iro, Ann Kristin; Agaimy, Abbas; Müller, Sarina Katrin; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos (Oral Oncology, 2021)
Objectives: The aim of this study was to thoroughly investigate the incidence of satellite nodules (SN) and some of their characteristics (number, distance to main lesion) in a large series of pleomorphic adenomas (PA) and to compare several surgical modalities regarding their efficacy in addressing this critical morphological feature. Materials and methods: The records of all patients treated for primary PA of the parotid gland between 2006 and 2020 were studied retrospectively. All the histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. Results: 845 cases made up our initial study sample. SNs were detected in 68/845 cases (8%). No statistically significant difference could be detected in the incidence of SNs in the surgical specimens between the patient groups managed by extracapsular dissection (46/577, 7.9%) and facial nerve dissecting surgery (22/268, 8.2%, p = 0.502). In the group of cases with SNs, no recurrences were detected (mean follow-up time: 71.4 months). The mean distance from the main lesion to the most distant SN was 1.1 mm (0.08–6.3 mm). The mean size of the SN was 1.9 mm (0.1–9.7 mm). Altogether, the mean distance from the main lesion to the outer periphery of the most distant SN was 3.1 mm (0.4–10.5 mm). Conclusion: Our analysis could not award SNs the title of an “extracapsular dissection's nightmare”. In the majority of cases, their favourable histological patterns offer the ideal circumstances for their surgical inclusion in a tumour specimen.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Capsule; Extracapsular dissection; Parotidectomy; Pleomorphic adenoma; Satellite nodule

Schlafstadienbestimmung mit Hilfe bewegungsbasierter Sensortechnologie - Traxdorf, Maximilian; Gradl, Stefan; Kugler, Patrick; Leutheuser, Heike; Lauten, Juliane; Eskofier, Björn; Angerer, Florian; Iro, Heinrich (Proceedings of the 84th Annual Meeting of the German Society of Oto-Rhino-Laryngology, Head and Neck Surgery, 2013)

Secondary Tracheoesophageal Puncture After Laryngectomy Increases Complications With Shunt and Voice Prosthesis - Scherl, Claudia; Kauffels, Julia; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Dürr, Stephan; Fietkau, Rainer; Haderlein, Marlen; Koch, Michael; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller, Sarina Katrin; et al. (Laryngoscope, 2020)
Objectives/Hypothesis To evaluate the demographics, clinical features, management, and prognostic indicators of tracheoesophageal puncture complications in patients undergoing placement of voice prosthesis following cancer treatment.
CRIS-Team WoS Importer:2020-02-21

Shifting cancer care towards Multidisciplinarity: the cancer center certification program of the German cancer society - Kowalski, Christoph; Graeven, Ullrich; Von Kalle, Christof; Lang, Hauke; Beckmann, Matthias; Blohmer, Jens-Uwe; Burchardt, Martin; Ehrenfeld, Michael; Fichtner, Jan; Grabbe, Stephan; Hoffmann, Hans; Iro, Heinrich; et al. (BMC Cancer, 2017)
BACKGROUND: Over the last decades numerous initiatives have been set up that aim at translating the best available medical knowledge and treatment into clinical practice. The inherent complexity of the programs and discrepancies in the terminology used make it difficult to appreciate each of them distinctly and compare their specific strengths and weaknesses. To allow comparison and stimulate dialogue between different programs, we in this paper provide an overview of the German Cancer Society certification program for multidisciplinary cancer centers that was established in 2003. MAIN BODY: In the early 2000s the German Cancer Society assessed the available information on quality of cancer care in Germany and concluded that there was a definite need for a comprehensive, transparent and evidence-based system of quality assessment and control. This prompted the development and implementation of a voluntary cancer center certification program that was promoted by scientific societies, health-care providers, and patient advocacy groups and based on guidelines of the highest quality level (S3). The certification system structures the entire process of care from prevention to screening and multidisciplinary treatment of cancer and places multidisciplinary teams at the heart of this program. Within each network of providers, the quality of care is documented using tumor-specific quality indicators. The system started with breast cancer centers in 2003 and colorectal cancer centers in 2006. In 2017, certification systems are established for the majority of cancers. Here we describe the rationale behind the certification program, its history, the development of the certification requirements, the process of data collection, and the certification process as an example for the successful implementation of a voluntary but powerful system to ensure and improve quality of cancer care. CONCLUSION: Since 2003, over 1 million patients had their primary tumors treated in a certified center. There are now over 1200 sites for different tumor entities in four countries that have been certified in accordance with the program and transparently report their results from multidisciplinary treatment for a substantial proportion of cancers. This led to a fundamental change in the structure of cancer care in Germany and neighboring countries within one decade.
EVALuna2:33190

Sialendoscopy in Sialolithiasis - Iro, Heinrich (HNO, 2017)
EVALuna2:33176

Significant polyomic and functional upregulation of the PAPP-A/IGFBP-4/5/IGF-1 axis in chronic rhinosinusitis with nasal polyps - Müller, Sarina Katrin; Nocera, Angela L.; Workman, Alan; Ubermann, Towia; Dillon, Simon T.; Stegmann, Achim; Wurm, Jochen; Iro, Heinrich; Wendler, Olaf; Bleier, Benjamin S. (International Forum of Allergy and Rhinology, 2020)
BACKGROUND: Chronic rhinosinusitis with nasal polyps (CRSwNP) is associated with epithelial expansion and polyp survival. However, the molecular mechanism of this aberrant proliferation is unclear. The purpose of this study was to interrogate derangements of the pappalysin-A/insulin-like growth factor binding protein/insulin-like growth factor-1 (PAPP-A/IGFBP-4/5/IGF-1 axis) as a major contributing factor to polyp growth in CRSwNP. METHODS: Matched tissue and exosomal proteomic arrays including PAPP-A, IGFBP-4, IGFBP-5, and IGF-1 were quantified using aptamer-based methods/Western blots for proteomic analysis and whole-transcriptome sequencing/quantitative polymerase chain reaction (qPCR) for transcriptomic analysis in CRSwNP and control patients. Functional PAPP-A assays were then performed in both tissue and exosomes (set 1: n = 20 per group; validation set 2: n = 26 per group). RESULTS: Tissue and exosomal PAPP-A was significantly overexpressed in CRSwNP compared to controls on both a transcriptomic and proteomic level (p < 0.0001). Known inhibitors of PAPP-A (stanniocalcin-1/-2) were significantly downregulated (p < 0.0001) as were PAPP-A cleavage products (IGFBP-5 p < 0.0001). PAPP-A function was shown to be increased 5-fold to 6-fold in tissue and exosomes. CONCLUSION: Upregulated tissue and exosomal PAPP-A signaling is significantly associated with CRSwNP and may be an important factor in the promotion of epithelial proliferation and polyp growth. These data lend further support to the emerging concept of exosomal functional and polyomic analyses as a method to study sinonasal pathology.
EVALuna2:209860

Silent sinus syndrome: Reduction of surgical invasiveness in an underdiagnosed clinical entity - Mantsopoulos, Konstantinos; Thimsen, Vivian; Karkos, Petros; Sievert, Matti; Iro, Heinrich; Constantinidis, Jannis (American Journal of Otolaryngology, 2022)
Objective: The aim of this study was to investigate our experience in the management of silent sinus syndrome. Material and methods: The records of all patients treated for silent sinus syndrome between 2011 and 2021 were evaluated retrospectively. Data were collected on epidemiological parameters (age, gender), referral specialty, imaging findings, surgical approach, and management. Results: In total, nine cases made up our final study sample (5 men, 4 women; male-female ratio 1:0.8). Their mean age was 39 years (range: 19–71 years). Besides the typical imaging findings (orbital floor depression, maxillary sinus atelectasis with ostium occlusion), lateralization of the uncinate process could be seen in seven cases (77.8 %) and ipsilateral septal deviation in six cases (66.6 %). Four cases were managed by means of middle meatal antrostomy and five with additional reconstruction of the orbital floor (transconjuctival approach in two cases, endonasal endoscopic approach in three cases). Enopthalmus recovered in all cases; diplopia (3 cases) recovered completely in two cases and partly in one case. Conclusion: Reduced surgical invasiveness in silent sinus syndrome, with management of the cause (maxillary sinus hypoventilation) and the sequel (orbital floor depression) using the same endoscopic approach, is associated with an acceptable clinical outcome.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Diplopia; Maxillary sinus atelectasis; Orbital floor; Reconstruction; Silent sinus

Simultaneous Application of Ultrasound and Sialendoscopy and its Value in the Management of Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Ultraschall in der Medizin, 2020)
Objective Ultrasound (US) and sialendoscopy (SE) are routinely used in patients presenting with sialolithiasis in the submandibular (SMG) and parotid gland (PG). The objective was to assess the value of the simultaneous application of US and SE in the management of sialolithiasis. Study Design Retrospective study. Setting: Tertiary referral center for salivary gland diseases. Participants: Patients in whom US and SE as single investigation tools were neither conclusive nor useful in the management of sialolithiasis were investigated using both methods simultaneously (simUS + SE). Main outcome measures: Establishment of the final diagnosis and/or contribution to the planning/performing of treatment in sialolithiasis. Results 74 patients were examined by simUS + SE (58.1 % SMG and 41.9 % PG). In all patients (unclear) hyperechoic reflexes were assessed and/or localized by SE-controlled US na-vigation. 68.9 % of the patients were investigated for diagnostic or differential-diagnostic reasons including distinguishing extraductal from intraductal calcifications and/or to exclude residual stones after therapy. In 52.7 % simUS + SE was used to plan and/or perform further treatment, in 20.3 % to enable performing a combined approach (all PG) and in 29.7 % to evaluate and plan the most adequate therapy (mainly intraductal vs. extracorporeal shock wave lithotripsy, 68.2 % of these SMG). In two cases SE-controlled and US-guided stone extraction was performed. Conclusion SimUS + SE is an innovative approach which proved to be very useful in managing sialolithiasis. It added valuable information regarding the establishment of a diagnosis or differential diagnosis, planning and performing the most adequate treatment, intraoperative control of therapy and postoperative follow-up.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Diagnosis; Salivary gland; Sialendoscopy; Therapy; Ultrasound

Simultaneous application of ultrasound and sialendoscopy: experience in the management of stenosis and other non-sialolithiasis-related salivary gland disorders - Koch, M.; Schapher, Mirco; Goncalves, Miguel; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: To assess the value of the simultaneous application of ultrasound and sialendoscopy (US+SE) in several salivary gland diseases not caused either by sialolithiasis or by tumours. PATIENTS AND METHODS: US+SE are routinely used in patients with inflammatory, obstructive, and other non-tumorous major salivary gland diseases. In patients in whom US and SE as single investigation tools were not conclusive or not useful in the management of several non-sialolithiasis-related conditions (stenoses, ductal anomalies, ductal trauma, space-occupying paraductal lesions), both methods were used simultaneously for diagnosis and treatment. RESULTS: US+SE were used simultaneously in 44 patients for 56 indications. Stenosis was managed in 36 cases (81.8%) and in thirty-eight of the indications (67.9%) with simultaneous US+SE. The successful opening was achieved in 23 (63.9%), conservative and/or ablative treatment was indicated in 13 (36.1%), and further imaging was indicated in two (5.5%) of these cases. Post-traumatic or postinfectious complications were managed in 12 (27.3%) of all cases, and isolated ductal anomalies and paraductal space-occupying lesions were assessed in three cases (8.3%) each. In all instances, simultaneous US+SE clearly improved the management in diagnosis and/or therapy. CONCLUSIONS: Simultaneous application of US+SE provided additional information that proved to be valuable for diagnosis, planning, and treatment in several non-sialolithiasis-related conditions such as stenoses, ductal anomalies, ductal trauma, and space-occupying paraductal lesions.
CRIS-Team Scopus Importer:2020-03-31

Single-cycle induction chemotherapy before chemoradiotherapy or surgery in functionally inoperable head and neck squamous cell carcinoma: 10-year results - Breheret, Marius; Lubgan, Dorota; Haderlein, Marlen; Hecht, Markus; Traxdorf, Maximilian; Schmidt, Daniela; Müller, Sarina Katrin; Kitzsteiner, Christian; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer; Semrau, Sabine (European Archives of Oto-Rhino-Laryngology, 2019)
Introduction The response to induction chemotherapy (IC) predicts local control after conservative treatment of laryngeal, meso- and hypopharyngeal head and neck squamous cell carcinoma (HNSCC) and can thus help to avoid surgery. Single-cycle induction chemotherapy may help to maintain a low local recurrence rate while keeping the overall toxicity manageable. However, long-term data on single-cycle IC response by tumor location is lacking. Methods N = 102 patients with functionally inoperable primary HNSCC of the larynx (n = 43), hypopharynx (n = 42) or mesopharynx/tongue (n = 17) received one cycle of docetaxel (75 mg/m(2), d1) plus cisplatin (30 mg/m(2), d1-3) or carboplatin (AUC 1.5, d1-3) and a response evaluation 3 weeks later. Responders (>= 30% tumor size reduction and >= 20% SUVmax decrease in F-18-FDG PET/CT) were recommended chemoradiotherapy (CRT), and non-responders surgery. Results The overall response rate was 72.5%. All 74 responders and 10 non-responders received primary CRT, and 18 patients received primary surgery after single-cycle IC. Overall 10-year local recurrence-free survival (LRFS) was 73.7%. Three-year LRFS was 88.2% (mesopharynx/tongue), 88.2% (larynx), and 73.3% (hypopharynx); p = 0.17. 3-year distant metastasis-free survival (DMFS) was 94.1% (mesopharynx/tongue), 88.0% (larynx) and 76.4% (hypopharynx); p > 0.05. This influenced the 3-year cancer-specific survival (CSS) for larynx (91.2%) vs. hypopharynx tumors (60.8%); p = 0.003, but CSS was not different to tumors in the mesopharynx/tongue (81.4%); p > 0.05. Conclusions A single-cycle induction chemotherapy for HNSCC enables surgery plus adjuvant therapy as well as chemoradiotherapy. The long-term local and distant disease control was good but varied between tumors in the larynx and mesopharynx/tongue vs. hypopharynx.
CRIS-Team WoS Importer:2019-10-18

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

Single cycle induction treatment with cisplatin/docetaxel plus durvalumab/tremelimumab in stage III-IVB head and neck squamous cell cancer (CheckRad-CD8 trial) - Hecht, Markus; Gostian, A-O.; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Brunner, T.; Laban, S.; Klautke, G.; Tamaskovics, B.; Frey, Benjamin; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Sinonasal papillomas: A single centre experience on 137 cases with emphasis on malignant transformation and EGFR/KRAS status in “carcinoma ex papilloma” - Maisch, Saskia; Müller, Sarina Katrin; Traxdorf, Maximilian; Weyerer, Veronika; Stoehr, Robert; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
Among the three major histological subtypes of sinonasal papillomas, inverted (ISP) and oncocytic (OSP) sinonasal papillomas tend to undergo malignant transformation to carcinoma. However, criteria determining risk of recurrence and malignant progression have not been established. Recently, EGFR and KRAS mutations were detected to be characteristic for ISP and OSP, respectively. In this study, we analyzed 137 sinonasal papilloma cases (132 ISP and 5 OSP) for clinicopathological characteristics, frequency of recurrences/malignant transformation, and histological types and genetic features of carcinoma ex Schneiderian papilloma. OSP presented at a higher age than ISP (median, 75 vs. 57 years) and affected predominantly females. Overall frequency of recurrences and malignant transformation was 23.1% and 9.5%, respectively. Rates of recurrence (33.3% vs. 22.0%) and malignant transformation (33.3% vs. 8.8%) were higher in OSP compared to ISP, respectively. Carcinomas (n = 10) occurred mostly synchronously, more frequently in females and mainly associated with ISP (n = 9). Squamous cell carcinoma (SCC) was the most frequently associated malignancy. Concordant EGFR (in ISP/associated carcinoma) and KRAS (in the OSP/associated carcinoma) mutations were detected in all successfully analyzed matching papilloma/carcinoma pairs, confirming their shared clonal origin. Results of this large study are in line with recent studies showing frequent EGFR and KRAS mutations in sinonasal carcinoma ex Schneiderian papilloma. As the papilloma component might on occasion be missed on biopsy of synchronous carcinoma ex papilloma, EGFR and KRAS mutation testing represents a promising molecular surrogate for sinonasal “carcinoma ex papilloma”, at the same time offering an opportunity for targeting mutant EGFR in this rare cancer type.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Carcinoma ex papilloma; EGFR; Inverted papilloma; KRAS; Oncocytic papilloma; Schneiderian papilloma; Sinonasal papilloma; Squamous cell carcinoma

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

SMARCB1 (INI-1)-deficient Sinonasal Carcinoma: A Series of 39 Cases Expanding the Morphologic and Clinicopathologic Spectrum of a Recently Described Entity - Agaimy, Abbas; Hartmann, Arndt; Antonescu, Cristina R.; Chiosea, Simion I.; El-Mofty, Samir K.; Geddert, Helene; Iro, Heinrich; Lewis, James S.; Markl, Bruno; Mills, Stacey E.; Riener, Marc-Oliver; Robertson, Thomas; et al. (American Journal of Surgical Pathology, 2017)
To more fully characterize the clinical and pathologic spectrum of a recently described tumor entity of the sinonasal tract characterized by loss of nuclear expression of SMARCB1 (INI1), we analyzed 39 SMARCB1-deficient sinonasal carcinomas collected from multiple medical centers. The tumors affected 23 males and 16 females with an age range of 19 to 89 years (median, 52). All patients presented with locally advanced disease (T3, n=5; T4, n=27) involving the sinuses (mainly ethmoid) with variable involvement of the nasal cavity. Thirty patients received surgery and/or radiochemotherapy with curative intent. At last follow-up, 56% of patients died of disease 0 to 102 months after diagnosis (median, 15), 2 were alive with disease, and 1 died of an unrelated cause. Only 9 patients (30%) were alive without disease at last follow-up (range, 11 to 115 mo; median, 26). The original diagnosis of retrospectively identified cases was most often sinonasal undifferentiated carcinoma (n=14) and nonkeratinizing/basaloid squamous cell carcinoma (n=5). Histologically, most tumors displayed either a predominantly basaloid (61%) or plasmacytoid/rhabdoid morphology (36%). The plasmacytoid/rhabdoid form consisted of sheets of tumor cells with abundant, eccentrically placed eosinophilic cytoplasm, whereas similar cells were typically rare and singly distributed in the basaloid variant. Glandular differentiation was seen in a few tumors. None of the cases showed squamous differentiation or surface dysplasia. By immunohistochemistry, the tumors were positive for pancytokeratin (97%), CK5 (64%), p63 (55%), and CK7 (48%); and they were negative for NUT (0%). Epstein-Barr virus and high-risk human papillomavirus was not detected by in situ hybridization. Immunohistochemical loss of SMARCB1 (INI1) expression was confirmed for all 39 tumors. Investigation of other proteins in the SWI/SNF complex revealed co-loss of SMARCA2 in 4 cases, but none were SMARCA4 deficient or ARID1A deficient. Of 27 tumors with SMARCB1 fluorescence in situ hybridization analysis, 14 showed homozygous (biallelic) deletions and 7 showed heterozygous (monoallelic) deletions. SMARCB1-deficient sinonasal carcinoma represents an emerging poorly differentiated/undifferentiated sinonasal carcinoma that (1) cannot be better classified as another specific tumor type, (2) has consistent histopathologic findings (albeit with some variability) with varying proportions of plasmacytoid/rhabdoid cells, and (3) demonstrates an aggressive clinical course. This entity should be considered in any difficult-to-classify sinonasal carcinoma, as correct diagnosis will be mandatory for optimizing therapy and for further delineation of this likely underdiagnosed disease.
EVALuna2:6856

Sonographic diagnosis of tonsillar abscesses: Our experience and a systematic review - Miksch, Malin; Koch, Michael; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Rupp, Robin; Iro, Heinrich; Sievert, Matti (Laryngo-Rhino-Otologie, 2022)
Background Transcutaneous sonography has been an integral part of imaging diagnostics in the head and neck region for several decades. Especially in the imaging of abscesses of the tonsillar fossa, sonography is a fast, safe, and cost-effective diagnostic method. This paper aims to provide an overview of the currently published studies in terms of diagnostic value. Material and methods systematic literature search in the following online databases: PubMed und MEDLINE according to the search terms: transcutaneous ultrasound, tonsillar abscess, peritonsillar abscess, intratonsillar abscess, peritonsillar cellulitis, parapharyngeal abscess. Evaluation of the scientific relevance of the papers according to established criteria. Results The publications were analyzed in terms of clinical application, clinical diagnosis, and diagnostic accuracy. Sensitivity and specificity are reported between 67 % - 100 %, and 50 % - 93 %, respectively, depending on the study and patient cohort. Conclusions In the synopsis of the currently published results, transcutaneous sonography promises a high potential to improve the diagnosis of peritonsillar abscess and allows a reliable differentiation to peritonsillar cellulitis. This fact seems crucial for the clinical management of patients with suspected abscesses.
CRIS-Team WoS Importer:2022-02-11

Sonographie des Halses – differenzialdiagnostische Aspekte - Sievert, Matti; Koch, Michael; Iro, Heinrich; Thimsen, Vivian (HNO, 2023)
Sonography is the preferred method for primary diagnosis and acute treatment of pathologies involving the neck’s soft tissues. Technological advances, particularly high image resolution and multiparametric ultrasound, have improved diagnostic performance. Clinical interest focuses on examining the cervical lymph nodes, salivary glands, and the thyroid gland, as well as space-occupying and inflammatory processes of the neck. In addition, sonography enables targeted minimally invasive histology acquisition using ultrasound-guided biopsies. In this context, the examiner’s comprehensive anatomical knowledge and clinical experience are of utmost importance for the quality of findings. This article provides an overview of the most important findings related to sonography of the neck and highlights the relevance of this imaging modality in the hands of the otorhinolaryngologist.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Head and neck neoplasms; Lymph nodes; Otorhinolaryngologic diseases; Salivary glands; Thyroid gland

Stellenwert der Vakzine gegen humane Papillomaviren in der Prävention von Krebserkrankungen - Schulmeyer, Carla; Knöll, Antje; Iro, Heinrich; Müller, Susanna; Beckmann, Matthias (Onkologe, 2021)
Background: Human papillomaviruses (HPV) are the most common causes of genital viral infections. HPV infections usually heal, but can also persist and thus cause lesions of different grades. Infections with high-risk HPV types (hrHPV) 16, 18, 31, 33, 45, 52, and 58 are responsible for causing 90% of cervical cancer cases in Europe. Head and neck cancer, vaginal and vulvar cancer and their precursors, as well as penile or anal cancer may also be associated with hrHPV. Objectives: The aim of this work is to demonstrate the importance of HPV vaccines in the prevention of genital as well as head and neck cancers. Materials and methods: This work is based on a selective literature search in the PubMed database on the correlation between HPV vaccines and HPV-associated cancer. Results: HPV vaccination ensures a high level of protection against precancerous lesions and cancer of the cervix, vagina, vulva, anus, and genital warts. Conclusions: Results of HPV vaccination and its positive effects on head and neck tumors is expected within the next few decades.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Condylomata acuminata; HPV; Oropharyngeal neoplasms; Sexually transmitted diseases; Uterine cervical neoplasms

Stenosis and stenosis-like lesions in the submandibular duct: detailed clinical and sialendoscopy-based analysis and proposal for a classification - Koch, Michael; Zenk, Johannes; Iro, Heinrich (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objective: The aim of this study was to perform a detailed analysis of submandibular duct stenoses and propose a classification for them. Study Design: This retrospective study covering the period 2001–2019 included 314 patients with 370 submandibular duct stenoses, assessed sialendoscopically for number, grade of narrowing, length, tissue type, and underlying main cause/associated diseases. Results: In the included patients, 58.9% of the stenoses were at the papilla, 89.2% were short, and 61.6% were of high grade. Predominantly inflammatory stenoses (type 1) differed from fibrotic stenoses (type 2). Detailed analysis identified stenosis-like lesions caused by anatomic duct narrowing and/or duct variations (type 3), differing significantly from type 2 stenoses in location, length, and bilaterality (each P = .0001) and from type 1 stenoses in location (P = .0001). Compared with type 2, type 1 stenoses were bilateral significantly more often and shorter (each P = .0001). Frequencies of the main causes of stenosis—anatomic narrowness/duct variation and chronic sialadenitis—differed significantly in the different locations (P = .0001). There were no significant differences in frequencies of associated diseases/conditions for the different stenosis types. Conclusions: Three types of stenosis/stenosis-like lesions were distinguished. In view of these results and the findings from a review of the literature, the location and type of stenoses were found to be more important parameters, whereas number, grade, and length were less important. The underlying cause may be useful for assessing the prognosis.
CRIS-Team Scopus Importer:2020-08-21

Stereotactic radiotherapy of vestibular schwannoma : Hearing preservation, vestibular function, and local control following primary and salvage radiotherapy - Putz, Florian; Müller, Jan; Wimmer, Cornelia; Goerig, Nicole; Knippen, Stefan; Iro, Heinrich; Grundtner, Philipp; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian (Strahlentherapie und Onkologie, 2017)
OBJECTIVE: The aim of this publication is to present long-term data on functional outcomes and tumor control in a cohort of 107 patients treated with stereotactic radiotherapy (RT) for vestibular schwannoma. PATIENTS AND METHODS: Included were 107 patients with vestibular schwannoma (primary or recurrent following resection) treated with stereotactic RT (either fractioned or single-dose radiosurgery) between October 2002 and December 2013. Local control and functional outcomes were determined. Analysis of hearing preservation was limited to a subgroup of patients with complete audiometric data collected before treatment and during follow-up. Vestibular function test (FVT) results could be analyzed in a subset of patients and were compared to patient-reported dizziness. RESULTS: After a mean follow-up of 46.3 months, actuarial local control for the whole cohort was 100% after 2, 97.6% after 5, and 94.1% after 10 years. In patients with primary RT, serviceable hearing was preserved in 72%. Predictors for preservation of serviceable hearing in multivariate analysis were time of follow-up (odds ratio, OR = 0.93 per month; p = 0.021) and pre-RT tumor size (Koos stage I-IIa vs. IIb-IV; OR = 0.15; p = 0.031). Worsening of FVT results was recorded in 17.6% (N = 3). Profound discrepancy of patient-reported dizziness and FVT results was observed after RT. In patients with primary RT, worsening of facial nerve function occurred in 1.7% (N = 1). CONCLUSION: Stereotactic RT of vestibular schwannoma provides good functional outcomes and high control rates. Dependence of hearing preservation on time of follow-up and initial tumor stage has to be considered.
EVALuna2:32910

Submandibular gland pleomorphic adenoma: Histopathological capsular characteristics and correlation with the surgical outcome - Mantsopoulos, Konstantinos; Goncalvesa, Miguel; Koch, Michael; Iro, Heinrich; Agaimy, Abbas (Annals of Diagnostic Pathology, 2018)
Pleomorphic adenoma (PA) of the submandibular gland is known to have a very low recurrence rate. The aim of this study was to investigate the histopathological and capsular characteristics of submandibular gland PA, looking for any differences between submandibular PA and the reported data for PA of the parotid gland as possible explanation for its low recurrence rate. We reviewed 72 submandibular gland PM resected at our center between 2000 and 2016. Patient age ranged from 14 to 77 years (mean, 47.2). At least follow (range, 12 to 170 months; mean, 82), none of the 72 patients developed a local recurrence. Histologically, all of the tumors were encased by a complete and intact anatomical capsule (100%). Pseudopodia were detected in 11 (15.3%) and satellite nodules in 3 (4.2%) cases. The histological subtype (according to Seifert et al.) was classic (mixed) in 39 (54.2%), stroma-rich/myxoid in 18/72 (25%) and cellular in 15 (20.8%) cases. A complete rim of healthy pericapsular tissue encasing the tumor and its capsule was observed in only 23/72 (31.9%) cases. In conclusion, submandibular PAs are characterized by consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia, a remarkably infrequent occurrence lower frequency of secondary satellite tumor nodules and a comparatively lower proportion of the fragile risky myxoid subtype. Despite the fact that surgery of the submandibular gland can frequently lead to focal capsular exposure, the aforementioned capsular characteristics of submandibular gland PA are probably responsible for the excellent oncologic results.
EVALuna2:34875

Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358

Surgery for Benign Salivary Neoplasms - Gillespie, M. Boyd; Iro, Heinrich (Advances in Oto-Rhino-Laryngology, 2016)
Salivary neoplasms are relatively infrequent entities that account for only 4% of tumors of the head and neck. Although slow-growing lesions of the preauricular area and submandibular space are often confused with sebaceous cysts, lymph nodes, or lipomas by the non-otolaryngologist, otolaryngologists-head and neck surgeons recognize that all preauricular and submandibular masses should be considered a salivary neoplasm until proven otherwise. Surgery remains the treatment of choice for benign salivary gland neoplasms; however, techniques continue to evolve in order to preserve salivary function and reduce surgical morbidity. The goals of management of benign salivary neoplasms include accurate diagnosis of the lesion, complete surgical extirpation, and functional preservation of adjacent cranial nerves. Accurate diagnosis is aided by appropriate preoperative physical examination, imaging, and fine needle aspiration biopsy. Benign neoplasms typically present as slow-growing, painless, mobile masses without adverse features, such as tissue fixation, ulceration, a cranial nerve deficit, or regional lymphadenopathy. Preoperative imaging with ultrasonography, computed tomography, or magnetic resonance imaging reveals well-circumscribed lesions without an infiltrative growth pattern or associated adenopathy. Fine needle aspiration biopsy may favor a benign neoplasm, supporting the clinical presentation. Surgery for a benign or malignant salivary neoplasm is in essence a false dichotomy since the surgeon can never be completely confident of the diagnosis until the specimen is removed. The surgeon must recognize the significant overlap between benign and malignant salivary masses in terms of clinical presentation, imaging, and cytology, which requires the surgeon to remain vigilant and flexible at the time of surgery should tissue characteristics or frozen section analysis suggest a malignant process.
EVALuna2:33359

Surgery for parotid gland cancer-controversial and proven aspects - Mantsopoulos, Konstantinos; Iro, Heinrich (HNO, 2022)
Background Due to the rarity of primary parotid malignancies, there are currently only limited clinical study data on the optimal surgical therapy. Parotid malignancies encompass a broad spectrum of more than 20 different histological subtypes with varying biology, which thus represents a challenge for even experienced pathologists and head and neck surgeons with proven expertise in salivary gland surgery. Objective The aim of this review article is to provide an overview of the current literature on surgical therapy of the primary tumor and the cN0 neck as well as treatment of the facial nerve, and to shed light on the various controversial aspects of this topic. Results In salivary gland oncology there is a trend towards safe (R0) but more conservative surgery. Currently, less-invasive surgical approaches could potentially be applied in a small subgroup with carefully selected caudally located and R0-resected "low-grade tumors" in stages T1-T2 and cN0 in relatively young patients with high compliance and more in the context of structured clinical studies. Elective neck dissection in the case of cN0 status should be carried out if risk factors for occult cervical lymph node metastasis (T3-T4a, "high-grade subtypes," advanced age, lymphangitic carcinomatosis) are present. In cases of small "low-grade parotid carcinomas," narrow resection margins or even microscopic tumor residues on the facial nerve can potentially be adequately compensated with adjuvant radiation therapy. However, due to the lack of solid data, the significance of the actual effect of the radiation in this situation should be viewed with great caution.
CRIS-Team WoS Importer:2022-05-27

Surgical Versus Noninvasive Manual Repositioning After Cochlear Implant Partial Magnet Dislocation - Rupp, Robin; Balk, Matthias; Allner, Moritz; Sievert, Matti; Müller, Sarina Katrin; Hoppe, Ulrich; Hornung, Joachim; Iro, Heinrich; Gostian, Antoniu Oreste (Ent-Ear Nose & Throat Journal, 2023)
Objectives: To compare surgical magnet repositioning (SMR) and noninvasive manual magnet repositioning (MMR) as treatments for partial magnet dislocation (PMD) of the internal magnet in a cochlear implant (CI) caused by magnetic resonance imaging (MRI). The primary objective was the success rate, while the secondary objectives were total postinterventional CI downtime and complications. Methods: This single-center retrospective study was conducted at a tertiary referral medical center. Patients with CI treated for PMD between January 1, 2007 and September 30, 2022 were included. SMR served as primary treatment until June 2019 and as secondary treatment after the introduction of MMR. Results: A total of 51 cases of PMD were observed in 42 patients and 43 devices (18 ♀; 24 ♂; 12 with bilateral CI). MMR was performed successfully in 19 out of 20 cases (95%), while 32 cases were managed successfully by SMR. The median age at first magnet repositioning was 53.8 years (minimum 19 years, maximum 93 years). When MMR was performed, the mean time from diagnosis to treatment (0.5 ± 1.5 days vs 9.8 ± 7.6 days; P <.01), the mean time from repositioning to CI reactivation (1.4 ± 4.3 days vs 13.1 ± 6.7 days; P <.01), and the mean total CI downtime (1.9 ± 4.8 days vs 22.9 ± 11.9 days; P <.01) were significantly shorter compared to SMR. Significantly fewer complications were experienced with MMR [n = 0 (0%) vs n = 8 (25%); P =.04]. Conclusion: In case of PMD caused by MRI, noninvasive MMR shows a high success rate with a shorter total CI downtime as well as a lower complication rate compared to SMR. Therefore, MMR should be considered as first line treatment with SMR as a second option in case of failure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: CI500; cochlear implant; complication; magnet dislocation; magnet repositioning; magnetic resonance imaging; manual maneuver

Survival benefit for patients treated in a certified head and neck tumor center. - von Wilmowsky, Cornelius; Traxdorf, Maximilian; Adler, Werner; Neukam, Friedrich Wilhelm; Iro, Heinrich; Nkenke, Emeka; Kesting, Marco Rainer; Wurm, Matthias (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: Increasing effort has been put in the implementation and certification of head and neck tumor centers in order to establish standardized, quality assured health care for head and neck tumor patients. This study evaluated survival rates after treatment in a certified head and neck tumor center (CHNTC) vs. a non-certified head and neck tumor center (non-CHNTC) in Middle Franconia, Germany. PATIENTS AND METHODS: Age, sex, possible obituary, and typical relevant prognostic variables were analyzed. Diagnosis was recorded according to ICD10. Clinical and pathological TNM staging, tumor grading, localization, R-stage, and morphology were assessed (ICD-0). Patients diagnosed with oral cancer (N=1047) were divided into groups based on where they received their primary treatment; CHNTCs or non-CHNTCs. RESULTS: Patients treated at CHNTCs had significantly higher survival rates vs. those treated at non-CHNTC (p=0.023) in univariate analysis. In a Cox regression model, survival rates for patients with pN0 and pN+ stage were similar at both types of centers. Men with pN0 had significantly lower survival rates (HR=0.497, p<0.001). Age had a statistically significant influence on survival rates independently from pN stage (HR=1.031 per year, p<0.001 in both groups). CONCLUSIONS: Patients treated at CHNTC had better survival rates than those treated at non-CHNTC.
EVALuna2:184478

Survival benefit for patients treated in a certified head and neck tumor center - von Wilmowsky, Cornelius; Traxdorf, Maximilian; Adler, Werner; Neukam, Friedrich Wilhelm; Iro, Heinrich; Nkenke, Emeka; Kesting, Marco Rainer; Wurm, Matthias (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: Increasing effort has been put in the implementation and certification of head and neck tumor centers in order to establish standardized, quality assured health care for head and neck tumor patients. This study evaluated survival rates after treatment in a certified head and neck tumor center (CHNTC) vs. a non-certified head and neck tumor center (non-CHNTC) in Middle Franconia, Germany. PATIENTS AND METHODS: Age, sex, possible obituary, and typical relevant prognostic variables were analyzed. Diagnosis was recorded according to ICD10. Clinical and pathological TNM staging, tumor grading, localization, R-stage, and morphology were assessed (ICD-0). Patients diagnosed with oral cancer (N=1047) were divided into groups based on where they received their primary treatment; CHNTCs or non-CHNTCs. RESULTS: Patients treated at CHNTCs had sig - nificantly higher survival rates vs. those treated at non-CHNTC (p=0.023) in univariate analysis. In a Cox regression model, survival rates for patients with pN0 and pN+ stage were similar at both types of centers. Men with pN0 had significantly lower survival rates (HR=0.497, p<0.001). Age had a statistically significant influence on survival rates independently from pN stage (HR=1.031 per year, p<0.001 in both groups). CONCLUSIONS: Patients treated at CHNTC had better survival rates than those treated at non-CHNTC.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Certification; Head; Neck Tumor Center; Prognosis; Survival

Symptom Burden and Quality of Life in Long-Term Survivors with Head and Neck Cancer - Gostian, Magdalena; Allner, Moritz; Rak, Atina; Balk, Matthias; Rupp, Robin; Ostgathe, Christoph; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Objectives: In this study, long-term survivors of head and neck cancer (HNC) were evaluated regarding their symptom burden and quality of life (QoL). Methods: This prospective study was performed during the regular follow-up consultations at one of Germany’s largest tertiary referral centers for HNC. The assessment included demographic, clinical, and oncological data, as well as the MIDOS(2) and the University of Washington Quality of Life Questionnaire (UW QoL) questionnaires. Patients were subdivided based on their disease stage, that is, early cancer stages (UICC I/II) and advanced cancer stages UICC (III/IV). Results: Between January 1, 2019 and December 31, 2019, 212 HNC patients with a mean follow-up of 46.36 ± 43.64 months were included (120 patients UICC stage I/II (22.5% female, mean age 61.93 ± 12.38 years) versus 92 patients UICC stage III/IV (25.0% female, mean age 63.73 ± 11.74 years)). For all patients evaluated (UICC I/II versus III/IV), the three most common symptoms were tiredness (47.5 vs 60.9%, P =.073, r =.123), anxiety (35.8 vs 32.6%, P =.624, phi =.034) and drowsiness (35.0 vs 44.6%, P =.157, phi =.097). Patients diagnosed with UICC III/IV stages reported loss of appetite significantly more frequently and with a high level of severity (15.0 vs 32.6%, P =.002, phi =.157; 0.23 ± 0.60 vs 0.47 ± 0.78, P =.003, r =.203). The overall symptom burden was low with a severity sum score (min 0-max 30) of 3.04 ± 3.29 versus 3.58 ± 3.38 (P =.143, r =.100). All patients rated their QoL as good (65.67 ± 20.93 vs 59.56 ± 22.00, P =.043, r =.139). Conclusion: The overall symptom burden of long-term survivors of HNC is encouragingly low. Trial registration: The study was registered in the German Registry for Clinical Studies (application No.: 00017122). Date of registration: 15.08.2019. https://drks.de/search/de/trial/DRKS00017122.
CRIS-Team Scopus Importer:2025-02-04
Keywords: head and neck cancer; MIDOS(2); patient-reported outcome; quality of life; symptom burden; UW QoL

Systematic classification of confocal laser endomicroscopy for the diagnosis of oral cavity carcinoma - Sievert, Matti; Oetter, Nicolai; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Koch, Michael; Balk, Matthias; Thimsen, Vivian; Stelzle, Florian; Eckstein, Markus; Iro, Heinrich; Goncalves, Miguel (Oral Oncology, 2022)
Introduction: Confocal laser endomicroscopy (CLE) is an optical imaging technique that allows in vivo microscope-like images of the upper aerodigestive tract's mucosa in 1000-fold magnification. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignoma suspected mucosa requires strict evaluation criteria. This study aims to validate a score for oral cavity squamous cell carcinoma (OCSCC) diagnostic. Methods: We performed CLE and examined a total of twelve patients. All 95 sequences (778 s, 6224 images) originate from the area of the primary tumor 260 s, 2080 images) and unsuspicious mucosa of the oral cavity (518 s, 4144 images). Specimen were taken at corresponding locations and analyzed histologically in H&E staining as a reference standard. A total of eight examiners (four experienced and four inexperienced) evaluated the sequences based on a scoring system. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are inter-rater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 88.7 %, 90.1 %, 87.4 %, 87.5 %, and 90.0 %, respectively, with inter-rater reliability and κ-value of 0.775, and an area under the curve of 0.935. Conclusions: The results confirm that this scoring system is applicable in the oral cavity mucosa to classify benign and malignant tissue.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Carcinoma; Squamous cell/diagnosis; Confocal laser endomicroscopy; Early detection of cancer*; Endoscopy; Fluorescence; Fluorescent dyes; Head and neck cancer; Head and neck neoplasms/diagnosis; Head and neck neoplasms/pathology*; Humans; Lasers; Margins of excision; Microscopy; Confocal/methods*; Mouth neoplasms*/diagnosis; Optical biopsy; Oral cavity squamous cell carcinoma; Safe surgical margins

Systematic interpretation of confocal laser endomicroscopy: larynx and pharynx confocal imaging score Interpretazione sistematica dell’endomicroscopia confocale laser: punteggio endomicroscopico confocale laringeo e faringeo - Sievert, Matti; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Rupp, Robin; Aubreville, Marc; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (Acta Otorhinolaryngologica Italica, 2022)
Objective. Development and validation of a confocal laser endomicroscopy (CLE) classification score for the larynx and pharynx. Methods. Thirteen patients (154 video sequences, 9240 images) with laryngeal or phar-yngeal SCC were included in this prospective study between October 2020 and February 2021. Each CLE sequence was correlated with the gold standard of histopathological ex-amination. Based on a dataset of 94 video sequences (5640 images), a scoring system was developed. In the remaining 60 sequences (3600 images), the score was validated by four CLE experts and four head and neck surgeons who were not familiar with CLE. Results. Tissue homogeneity, cell size, borders and clusters, capillary loops and the nu-cleus/cytoplasm ratio were defined as the scoring criteria. Using this score, the CLE experts obtained an accuracy, sensitivity, and specificity of 90.8%, 95.1%, and 86.4%, respectively, and the CLE non-experts of 86.2%, 86.4%, and 86.1%. Interobserver agreement Fleiss’ kappa was 0.8 and 0.6, respectively. Conclusions. CLE can be reliably evaluated based on defined and reproducible imaging features, which demonstrate a high diagnostic value. CLE can be easily integrated into the intraoperative setting and generate real-time, in-vivo microscopic images to demarcate malignant changes.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Targeted Therapy, Chemotherapy, Immunotherapy and Novel Treatment Options for Different Subtypes of Salivary Gland Cancer - Müller, Sarina Katrin; Haderlein, Marlen; Lettmaier, Sebastian; Agaimy, Abbas; Haller, Florian; Hecht, Markus; Fietkau, Rainer; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Surgical resection remains the first line treatment for salivary gland cancer (SGC). In the case of locally advanced disease, surgery is followed by adjuvant radiotherapy. Surgical resection should be favored in resectable locoregional recurrent disease as well, and even the complete resection of all distant oligometastases has clinical benefit for the patients. For inoperable and disseminated metastatic disease, a multitude of systemic therapies including chemotherapy, targeted therapy, and immunotherapy are available. In this review, the current therapeutic options for inoperable recurrent or metastatic SGCs are summarized. Systemic treatment can achieve prolonged progression-free and overall survival, while the overall prognosis remains poor. Current clinical trials include only a limited number of patients and mostly combine different histologic subtypes. Additionally, no randomized controlled trial comparing different therapeutic options has been performed. In the future, further studies with a larger patient cohort and ideally only one histologic subtype are needed in order to improve the outcome for SGC patients. However, this may be difficult to accomplish due to the rarity and diversity of the disease. Additionally, molecular analyses need to be performed routinely in order to individualize treatment and to go one step further towards precision medicine.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acinic cell carcinoma; Adenoid cystic carcinoma; Chemotherapy; Immunotherapy; Mucoepidermoid carcinoma; Salivary duct carcinoma; Salivary gland cancer; Targeted therapy

The COVID-19 pandemic and its consequences for the diagnosis and therapy of head and neck malignancies - Rupp, Robin; de Vasconcelos Craveiro, Antonio; Allner, Moritz; Grundtner, P.; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste; Balk, Matthias (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: The COVID-19 pandemic and the measures accompanying it have been accused of having a negative influence on the frequency and methods of treatment of various diseases including head and neck cancer (HNSCC). To go further into this assumption, the diagnoses made, and treatments performed at one of Germany's largest head and neck cancer centres were evaluated.
CRIS-Team WoS Importer:2022-02-04

The current value of quantitative shear wave sonoelastography in parotid gland tumors - Thimsen, Vivian; Goncalves, Miguel; Koch, Michael; Mantsopoulos, Konstantinos; Hornung, Joachim; Iro, Heinrich; Schapher, Mirco (Gland Surgery, 2021)
Background: The preoperative differentiation between salivary gland tumor entities using computed tomography, magnetic resonance imaging (MRI) and ultrasound ( US) is still limited. Biopsies are often regarded as indispensable for properly characterizing these various lesions. The aim of this study was to analyze the value of acoustic radiation force impulse (ARFI) sonoelastography as an US differentiation tool when examining parotid gland (PG) lesions.
CRIS-Team WoS Importer:2021-05-28

The Effects of a “New Generation” of Heat and Moisture Exchangers in Laryngectomized Patients with Previous Heat and Moisture Changer Experience - Almajali, Omar; Balk, Matthias; Rupp, Robin; Allner, Moritz; Sievert, Matti; Iro, Heinrich; Schützenberger, Anne; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2023)
Objectives: To evaluate the effects of a new generation of heat and moisture exchangers (NG-HMEs) on pulmonary rehabilitation, quality of life, patient satisfaction, and usage patterns. Methods: A prospective observational study on 23 laryngectomized patients with prior HME experience from June 1, 2021 to November 30, 2021. Patients were interviewed at inclusion, after 6 weeks and after 12 weeks after the introduction of NG-HMEs. Two validated questionnaires were used to report pulmonary complaints and quality of life: the Cough and Sputum Assessment Questionnaire (CASA-Q), the European Quality of Life 5 Dimensions Index Score (EQ-5D Index Score), and the European Quality of Life 5 Dimensions Visual Analog Scale (EQ-5D-VAS). Usage patterns and patient satisfaction were reported using study-specific questionnaires. Results: The patients had an average age of 65.7 ± 6.8 years, with 87% being male, on average 33.7 ± 35.3 months after total laryngectomy (TLE). NG-HMEs were used for a mean of 21.87 ± 4.63 hours/day (P =.034). After 12 weeks of use, patients reported the following changes in the CASA-Q domains: cough symptoms (+5; P =.663), cough impact (0; P =.958), sputum symptoms (+8; P =.13), and sputum impact (+3; P =.489). The EQ-5D index score increased (+0.024; P =.917) as well as the EQ-5D VAS (+0.8; P =.27). All patients rated their experience with NG-HMEs with ≥3 out of 5. The patients who used NG-HMEs as instructed (n = 13) reported more profound changes in the CASA-Q domains: cough symptom (+11; P =.129), cough impact (+7; P =.209), sputum symptom (+11; P =.123), and sputum impact (+10; P =.102). Conclusions: Our results show that NG-HMEs could have a positive clinical impact on pulmonary rehabilitation after TLE, even in HME-experienced patients. The use of NG-HMEs does not affect the quality of life. The possible effects of NG-HMEs require further evaluation in long-term studies to fully assess their efficacy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: devices; pulmonary rehabilitation; quality of life; total laryngectomy

The Erlangen Questionnaire: a new 5-item screening tool for obstructive sleep apnea in a sleep clinic population - A prospective, double blinded study - Traxdorf, Maximilian; Tziridis, Konstantin; Scherl, C.; Iro, Heinrich; Haferkamp, Jens (European Review for Medical and Pharmacological Sciences, 2017)
OBJECTIVE: The aim of this study was to develop and validate a simplified screening tool for identifying obstructive sleep apnea (OSA) in a sleep clinic population. PATIENTS AND METHODS: A total of 160 patients from a sleep clinic population was enrolled in the prospective, double-blinded study. OSA was defined by using diagnostic criteria of the ICSD-3 after overnight polysomnography (n=96) or polygraphy (n=64). The first 60 patients filled out a multi-item questionnaire and formed the development group. Subsequently, the five most predictive factors were selected to create the Erlangen Questionnaire (EQ). For validation of the EQ, the next 100 patients formed the validation group. RESULTS: The following factors were incorporated into the 5-item EQ: (1) ESS > 10, (2) age > 60, (3) gasping and (4) cardiovascular risk factors, (5) witnessed apneas. The EQ had sensitivities of 94.3%, 92.7% and 92.3%, specificities of 50.0%, 33.3% and 22.9%, positive predictive values of 81.5%, 62.9% and 29.6%, and negative predictive values of 78.9%, 78.9% and 89.5% with respect to mild, moderate and severe OSA. CONCLUSIONS: EQ is a compact 5-item-based, concise and easy-to-use screening tool to identify both male and female patients with OSA in a sleep clinic-population and exhibits all essential factors of internal and external validity. The results of the EQ are comparable to the best-validated and most commonly used STOP-Bang questionnaire regarding sensitivity and specificity in a sleep clinic population.
EVALuna2:33218

The influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome - Lenk, Christian; Meßbacher, Maria-Elena; Abel, Judith; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Sievert, Matti; Wirtz, Stefan; Marxreiter, Franz; Winkler, Jürgen; Iro, Heinrich; Traxdorf, Maximilian (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: The aim of this study was to investigate the influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome. PATIENTS AND METHODS: Endonasal swabs from the olfactory groove of 22 patients with moderate and severe obstructive sleep apnea (OSA) and a control group of 17 healthy controls were obtained at the Department of Otorhinolaryngology of the Friedrich-Alexander-Universität Erlangen-Nürnberg. 16S rRNA gene sequencing was performed to further evaluate the endonasal microbiome. In a second step, the longitudinal influence of continuous positive airway pressure (CPAP) therapy on the nasal microbiome was investigated (3-6 and 6-9 months). RESULTS: Analysis of the bacterial load and β-diversity showed no significant differences between the groups, although patients with severe OSA showed increased α-diversity compared to the control group, while those with moderate OSA showed decreased α-diversity. The evaluation of longitudinal changes in the nasal microbiota during CPAP treatment showed no significant difference in α- or β-diversity. However, the number of bacteria for which a significant difference between moderate and severe OSA was found in the linear discriminant analysis decreased during CPAP treatment. CONCLUSIONS: Long-term CPAP treatment showed an alignment of the composition of the nasal microbiome in patients with moderate and severe OSA as well as an alignment of biodiversity with that of the healthy control group. This change in the composition of the microbiome could be both part of the therapeutic effect in CPAP therapy and a promoting factor of the adverse side effects of the therapy. Further studies are needed to investigate whether the endonasal microbiome is related to CPAP compliance and whether CPAP compliance can be positively influenced in the future by therapeutic modification of the microbiome.
CRIS-Team WoS Importer:2023-05-26

The modified Polsby–Popper score, a novel quantitative histomorphological biomarker and its potential to predict lymph node positivity and cancer-specific survival in oral tongue squamous cell carcinoma - Csűry, Tamás Dániel; Csűry, Anna Zsófia; Balk, Matthias; Kist, Andreas; Rupp, Robin; Müller, Sarina Katrin; Sievert, Matti; Iro, Heinrich; Eckstein, Markus; Gostian, Antoniu-Oreste (Cancer Medicine, 2023)
Background: The significance of different histological spreading patterns of tumor tissue in oral tongue squamous cell carcinoma (TSCC) is well known. Our aim was to construct a numeric parameter on a continuous scale, that is, the modified Polsby–Popper (MPP) score, to describe the aggressiveness of tumor growth and infiltration, with the potential to analyze hematoxylin and eosin-stained whole slide images (WSIs) in an automated manner. We investigated the application of the MPP score in predicting survival and cervical lymph node metastases as well as in determining patients at risk in the context of different surgical margin scenarios. Methods: We developed a semiautomated image analysis pipeline to detect areas belonging to the tumor tissue compartment. Perimeter and area measurements of all detected tissue regions were derived, and a specific mathematical formula was applied to reflect the perimeter/area ratio in a comparable, observer-independent manner across digitized WSIs. We demonstrated the plausibility of the MPP score by correlating it with well-established clinicopathologic parameters. We then performed survival analysis to assess the relevance of the MPP score, with an emphasis on different surgical margin scenarios. Machine learning models were developed to assess the relevance of the MPP score in predicting survival and occult cervical nodal metastases. Results: The MPP score was associated with unfavorable tumor growth and infiltration patterns, the presence of lymph node metastases, the extracapsular spread of tumor cells, and higher tumor thickness. Higher MPP scores were associated with worse overall survival (OS) and tongue carcinoma-specific survival (TCSS), both when assessing all pT-categories and pT1-pT2 categories only; moreover, higher MPP scores were associated with a significantly worse TCSS in cases where a cancer-free surgical margin of <5 mm could be achieved on the main surgical specimen. This discriminatory capacity remained constant when examining pT1-pT2 categories only. Importantly, the MPP score could successfully define cases at risk in terms of metastatic disease in pT1-pT2 cancer where tumor thickness failed to exhibit a significant predictive value. Machine learning (ML) models incorporating the MPP score could predict the 5-year TCSS efficiently. Furthermore, we demonstrated that machine learning models that predict occult cervical lymph node involvement can benefit from including the MPP score. Conclusions: We introduced an objective, quantifiable, and observer-independent parameter, the MPP score, representing the aggressiveness of tumor growth and infiltration in TSCC. We showed its prognostic relevance especially in pT1-pT2 category TSCC, and its possible use in ML models predicting TCSS and occult lymph node metastases.
CRIS-Team Scopus Importer:2023-12-29
Keywords: computer-assisted image analysis; squamous cell carcinoma of head and neck; survival analysis; tongue cancer

The Offprint of an Abnormal Pre-Parotidectomy Electrodiagnostic Finding in a Normally Functioning Facial Nerve: Correlation with Intraoperative Findings, Histology and Postoperative Facial Nerve Function† - Katheder, Verena; Sievert, Matti; Müller, Sarina Katrin; Thimsen, Vivian; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
The aim of this study was to search for associations between an electrodiagnostically abnormal but clinically normal facial nerve before parotidectomy and the intraoperative findings, as well as the postoperative facial nerve function. The records of all patients treated for parotid tumors between 2002 and 2021 with a preoperative House–Brackmann score of grade I but an abnormal electrophysiologic finding were studied retrospectively. A total of 285 patients were included in this study, and 222 patients had a benign lesion (77.9%), whereas 63 cases had a malignant tumor (22.1%). Electroneurographic facial nerve involvement was associated with nerve displacement in 185 cases (64.9%) and infiltration in 17 cases (6%). In 83 cases (29.1%), no tumor–nerve interface could be detected intraoperatively. An electroneurographic signal was absent despite supramaximal stimulation in 6/17 cases with nerve infiltration and in 17/268 cases without nerve infiltration (p < 0.001). The electrophysiologic involvement of a normal facial nerve is not pathognomonic for a malignancy (22%), but it presents a rather rare ( 6%) sign of a “true” nerve infiltration and could also appear in tumors without any contact with the facial nerve ( 29%). Of our cases, two thirds of those with an anatomic nerve preservation and facial palsy had already directly and postoperatively recovered to a major extent in the midterm.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Electromyography; Electroneurography; Facial nerve; Facial paralysis; Infiltration; Parotidectomy; Tumor

Therapies for synchronous malignomas - the importance of interdisciplinary oncology - Müller, Sarina Katrin; Haderlein, Marlen; Traxdorf, Maximilian; Semrau, Sabine; Agaimy, Abbas; Lettmaier, Sebastian; Gostian, Antoniu-Oreste; Schubart, Christoph; Mantsopoulos, Konstantinos; Schmidt, Daniela; Wiesmüller, Marco; Sievert, Matti; et al. (Laryngo-Rhino-Otologie, 2021)
CRIS-Team WoS Importer:2021-08-06

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14

The use of automatic speech recognition showing the influence of nasality on speech intelligibility - Mayr, Susanne; Burkhardt, Katja; Schuster, Maria; Rogler, Katrin; Maier, Andreas; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2010)

The value of transcutaneous ultrasound in the diagnosis of tonsillar abscess: A retrospective analysis - Sievert, Matti; Miksch, Malin; Mantsopoulos, Konstantinos; Goncalves, Miguel; Rupp, Robin; Müller, Sarina Katrin; Traxdorf, Maximilian; Iro, Heinrich; Koch, Michael (Auris Nasus Larynx, 2021)
Objective: To identify the appropriate treatment in the tonsillar region's infections, a distinction between tonsillitis with or without abscess formation is essential. Ultrasound proved to be a valuable method in identifying abscess formation in the head and neck region. However, no report described the assessment of the tonsil region. This study aims to determine the feasibility of transcervical ultrasound for abscess visualization in the palatal tonsillar region. Methods: Retrospective analysis of 354 patients presenting with clinical suspicion of tonsillar abscess to a tertiary referral center and university hospital. All patients received a transcervical ultrasound to establish a primary diagnosis. The existence of an abscess was confirmed by puncture and incision, or final tonsillectomy. If no abscess could be delineated, non-abscessing tonsillitis was supposed, and conservative primary therapy and closed follow-up examinations were performed. Results: After the first diagnostic ultrasound examination, in 257 cases (72.59%), the diagnosis of an abscess could be established, but in 97 cases (27.40%), due to missing abscess formation criteria, non-abscessing tonsillitis was documented. Overall, ultrasonography demonstrated an overall accuracy of 78.8% in this selected cohort. The sensitivity, specificity, PPV, and NPV after the first ultrasound examination were calculated with 75.1%, 88.6%, 94.6%, and 57.3%, respectively. Conclusion: The presented data confirm that an abscess formation due to tonsillitis can be detected by transcervical ultrasound, enabling prompt, adequate management. As transcervical ultrasound can be conducted fast and is not associated with radiation, it can be regarded as a first-line diagnostic tool in this condition.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Diagnostic; Intratonsillar abscess; Parapharyngeal abscess; Peritonsillar abscess; Tonsillar abscess; Transcutaneous ultrasound

Thrombose genähter vs. gekoppelter Anastomosen bei mikrovaskulären Kopf- und Halsrekonstruktionen - Sievert, Matti; Koch, Michael; Goncalves, Miguel; Richter, Daniel; Tamse, Rosalie; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Harreus, Uli; Iro, Heinrich (Laryngo-Rhino-Otologie, 2020)
Objective The Anastomotic Coupling Device for microvascular anastomoses has become widely used in free tissue transplantation. This study compares the thrombosis rate and flap failure as a function of the anastomosis technique at a large head and neck cancer center. Material and Methods Retrospective analysis of all patients receiving free flap reconstructions in the period 2001-2019. Reconstruction type, recipient vessels, number of venous anastomoses, coupler size, and operation time were investigated. We compared the rates of venous thrombosis between hand sewn and coupled anastomoses, as well as the rate of flap failure. Results A total of 403 free flap reconstructions were performed for over 17 years. The venous anastomosis was sewn in 113 flaps in single suture technique, and in 290 cases, coupler device was used. The rate of venous thrombosis requiring immediate surgical revision was 6.2 % (7/113) in the sewn group compared to 7.6 % in the coupled group (22/290; p = 0.627). With an overall success rate of 95.0 % (383/403), the rate of flap failure was 3.6 % (4/113) and 5.5 % (16/290; p = 0.421), respectively. Surgical time is comparable with 680 ± 144 minutes in the hand-sewn group and 688 ± 167 minutes in the coupled group (p = 0.678). Conclusions With similar success rates, the coupler device is an effective alternative to venous anastomosis in single suture technique. Due to the generally low rate of pedicle thrombosis in both groups, we cannot separate the influence of the anastomosis technique from possible interfering variables.
CRIS-Team Scopus Importer:2020-10-02
Keywords: anastomotic coupling device; flap failure; free flap reconstruction; pedicle thrombosis; venous anastomosis

Thyroglossal duct cysts: 20 years' experience (1992-2011) - De Tristan, Julie; Zenk, Johannes; Kuenzel, Julian; Psychogios, Georgios; Iro, Heinrich (European Archives of Oto-Rhino-Laryngology, 2015)
The objective of the present study is to report on the clinical course and management of thyroglossal duct cysts. Retrospective review of all patients who underwent surgery for thyroglossal duct cysts between 2000 and 2013 at a tertiary referral center was carried out. The operations were performed using a modification of the Sistrunk operation: transcervical cystectomy, partial dissection of the hyoid bone, and dissection of all tracts identified during surgery. A total of 352 patients (176 men, 176 women) underwent surgery for a cyst (n = 282) or discharging sinus (n = 70). The mean age for the incidence of cysts was 26 years. Four of the patients (1.4 %) had a papillary thyroid carcinoma in the epithelium of the cyst. The follow-up period ranged from 7 months to 10 years. The overall recurrence rate was 4.5 %. Resection is often regarded as an elective surgical procedure in patients with thyroglossal duct cysts, but surgery should always be considered. Papillary thyroid carcinoma in the epithelium of the cyst is a rare but possible differential diagnosis. Dissection of all tracts found is recommended and partial dissection of the hyoid bone is mandatory. Dissection of the foramen cecum is not imperative. The recurrence rates with this approach are comparable to more extensive methods such as those described by Sistrunk.
EVALuna2:19988

Time dependency of adjuvant therapy in advanced head-and-necksquamous-cell-carcinoma of unknown primary (CUP)-patients - Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Müller, Sarina Katrin; Allner, Moritz; Traxdorf, Maximilian; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16

Transdermal scopolamine for the prevention of a salivary fistula after parotidectomy - Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2018)
Our aim was to investigate whether perioperative transdermal application of scopolamine could help to prevent fistulas after parotidectomy, and to this end we retrospectively studied the records of all patients (n=645) who had benign parotid tumours treated by partial parotidectomy between 2011 and 2016. We found that scopolamine led to a significant decrease in the incidence of salivary fistulas from 54/371(15%) in the group not given it to 10/274 (4%) in the group given it (p<0.0001). The "number needed to treat" was 9.17. There was a relatively low incidence of all adverse effects after scopolamine. Our results are encouraging. Thorough consideration of the contraindications and a knowledge of the potential adverse effects are crucial for its successful implementation.
EVALuna2:35391

Transoral submandibulotomy for deep hilar submandibular gland sialolithiasis - Schapher, Mirco; Mantsopoulos, Konstantinos; Meßbacher, Maria-Elena; Iro, Heinrich; Koch, Michael (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To assess the long-term results after transoral submandibulotomy for stones located in the deep hilar and intraparenchymal submandibular region. STUDY DESIGN: Retrospective cohort analysis. METHODS: Retrospective evaluation including all patients treated with transoral submandibulotomy for sialolithiasis at a tertiary referral center. RESULTS: Complete stone removal at the first transoral surgical treatment was achieved in 185 of 234 patients (79.1%). One hundred seventy-five of the 234 patients were followed up for a mean of 31.2 ( ± 20.5) months. During the follow-up period, 140 of the 175 patients (80.0%) became symptom free after one operation. In patients with residual symptoms, no further treatment was needed in 12 patients (6.9%) due to the mildness of the symptoms; 23 patients (13.1%) received further therapy, which was successful in 15 cases. Submandibulectomy only had to be performed in 3.4% of the patients with follow-up (6/175). In a questionnaire survey, 91.4% of the patients stated that they would be prepared to have the same operation again. CONCLUSIONS: These findings show that transoral removal of submandibular sialoliths located in the deep hilum or adjacent intraglandular parenchyma is an effective treatment that can be assisted by additional measures. The techniques described show high success rates, good long-term results, low complication rates, and they avoided the need for submandibulectomy in >95% of cases. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:2038-2044, 2017.
EVALuna2:33207

Transoral ultrasound: a helpful and easy diagnostic method in obstructive salivary gland diseases - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (European Radiology, 2019)
• Transoral ultrasound is a simple technique, very helpful for the evaluation of obstructive diseases of the salivary glands. • It overcomes most of the limitations of transcutaneous ultrasound.
CRIS-Team Scopus Importer:2019-05-02

Transoral Ultrasound in the Diagnosis of Obstructive Salivary Gland Pathologies - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Ultrasound in Medicine and Biology, 2019)
Transcutaneous ultrasound (TCUS) is an accepted diagnostic method in salivary gland diseases. However, sparse data are available on the use of transoral ultrasound (TOUS) in sialadenopathies. One hundred five patients presenting with various obstructive sialadenopathies were examined using TOUS and TCUS. Ultrasound findings were validated by direct visualization in subsequent sialendoscopy examinations. By TOUS, but not by TCUS, all patients with sialolithiasis (70/105) could be identified and virtually all concrements, even very small ones, were detected and distinguished from artifacts. Ductal stenoses (16/105) could be correctly differentiated from sialoliths, and exceptional insights into the delicate anatomy of parotid duct stenoses were gained. TOUS provided detailed information on other space-occupying lesions (14/105) and circumvented the method-related diagnostic weaknesses of TCUS. As a valuable tool in the diagnosis of obstructive sialadenopathies, TOUS seems superior to TCUS in pathologies involving the distal parotid duct, the submandibular duct system and the floor of the mouth.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Obstructive sialadenopathy; Salivary duct stenosis; Salivary glands; Sialolithiasis; Transoral ultrasound

Treatment of cervical paragangliomas: is surgery the only way? - Künzel, Julian; Koch, Michael; Brase, Christoph; Fietkau, Rainer; Iro, Heinrich; Zenk, Johannes (American Journal of Otolaryngology, 2014)
To analyze the results after surgery or stereotactic radiotherapy (SRT) in the treatment of cervical paragangliomas. Against this background, the decision-making algorithm used in the treatment of carotid body tumors (CBTs) and vagal paragangliomas (VPs) was reevaluated relative to the existing literature on the topic.Retrospective study between 2000 and 2012. A total of 27 CBTs and nine VPs in 32 patients were treated. Shamblin class I: 59.3% (n=16); class II: 29.6% (n=8); class III: 11.1% (n=3). Treatment modalities were surgery, radiotherapy, or observation. The end points for analysis were long-term tumor control and integrity of the cranial nerves.21 CBTs and seven VPs underwent surgery; SRT was performed in three CBTs and two VPs. Three CBTs were clinically observed. Permanent nerve paresis followed after surgery for CBTs in five patients (20%) and in all patients with VPs. No impaired cranial nerve function resulted after SRT. The median follow-up period was 4.7 years. The tumor control rate after therapy for CBTs and VPs was 100%. One CBT that received clinical observation showed slow tumor progression.A surgical procedure should be regarded as the treatment of choice in patients with small CBTs. In larger CBTs, particularly in elderly patients with unimpaired cranial nerves, radical surgery should be regarded critically. As surgery for VPs caused regularly impairment of cranial nerves with functional disturbances of various degrees a comprehensive consultation with the patient is mandatory and nonsurgical strategies should be discussed.
EVALuna2:18181

Treatment of sialolithiasis: What has changed? an update of the treatment algorithms and a review of the literature - Koch, Michael; Mantsopoulos, Konstantinos; Müller, Susanna; Sievert, Matti; Iro, Heinrich (Journal of Clinical Medicine, 2022)
Treatment for sialolithiasis has undergone significant changes since the 1990s. Following the development of new minimally invasive and gland-preserving treatment modalities, a 40–50% rate of gland resection was reduced to less than 5%. Extracorporeal shock-wave lithotripsy (ESWL), refinement and extension of methods of transoral duct surgery (TDS), and in particular diagnostic and interventional sialendoscopy (intSE) are substantial parts of the new treatment regimen. It has also become evident that combining the different treatment modalities further increases the effectiveness of therapy, as has been especially evident with the combined endoscopic–transcutaneous approach. In the wake of these remarkable developments, a treatment algorithm was published in 2009 including all the known relevant therapeutic tools. However, new developments have also taken place during the last 10 years. Intraductal shock-wave lithotripsy (ISWL) has led to remarkable improvements thanks to the introduction of new devices, instruments, materials, and techniques, after earlier applications had not been sufficiently effective. Techniques involving combined approaches have been refined and modified. TDS methods have been modified through the introduction of sialendoscopy-assisted TDS in submandibular stones and a retropapillary approach for distal parotid sialolithiasis. Recent trends have revealed a potential for significant changes in therapeutic strategies for both major salivary glands. For the submandibular gland, ISWL has replaced ESWL and TDS to some extent. For parotid stones, ISWL and modifications of TDS have led to reduced use of ESWL and the combined transcutaneous–sialendoscopic approach. To illustrate these changes, we are here providing an updated treatment algorithm, including tried and tested techniques as well as promising new treatment modalities. Prognostic factors (e.g., the size or location of the stones), which are well recognized as having a strong impact on the prognosis, are taken into account and supplemented by additional factors associated with the new applications (e.g., the visibility or accessibility of the stones relative to the anatomy of the duct system).
CRIS-Team Scopus Importer:2022-01-07
Keywords: Combined treatment; Extracorporeal lithotripsy; Intraductal lithotripsy; Salivary gland; Sialendoscopy; Sialolithiasis; Transoral duct surgery; Treatment

Treatment of the donor site of free radial flaps: vacuum sealing versus conventional wound care - Koch, Michael; Jalyzada, Kavan; Grundtner, Philipp; Iro, Heinrich; Scherl, Claudia; Harreus, Ulrich; Kuenzel, Julian (Acta Oto-Laryngologica, 2017)
INTRODUCTION: Radial forearm flap donor side defects can be treated by vacuum therapy and conventional wound dressing. The aim of this study was to compare different wound management considering wound healing, including risk factors and cost effectiveness. MATERIALS AND METHODS: Retrospective study including patients treated with radial flaps in the Department of Head and Neck Surgery in Erlangen from January 2005 to August 2013. Wound healing was assessed regarding complications considering several risk factors and comorbidities. Data were analyzed comparing conventional dressing and vacuum therapy, including a calculation of costs. RESULTS: The study included 138 patients (n = 55 conventional dressing; n = 83 vacuum dressing). The incidence of wound complications in the vacuum group was 50.6 and 32.7% in the conventional dressing group (p = .058). The presence of risk factors and comorbidities did not have significant impact on the occurrence of complications. Costs for vacuum therapy turned out to be at least five times higher. CONCLUSION: In view of the current state of research, these results show that using vacuum dressings has no significant benefit in the wound management of forearm donor side defect covered with full-thickness skin grafts. If the costs and economical aspects are also considered, conventional wound dressing may be preferred.
EVALuna2:33185

Treatment strategy by radioiodine refractory differentiated thyroid cancer - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Pavel, Marianne Ellen; Kuwert, Torsten; Meidenbauer, Norbert; Fietkau, Rainer; Sievert, Matti; Iro, Heinrich (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung Traditionell besteht das multimodale Therapiekonzept bei den differenzierten Schilddrusenkarzinomen in der Thyreoidektomie mit Neck-Dissection (bei cN+-Halsstatus) und adjuvanten Radiojodablation mit abschlie ss ender risikoadaptierter TSH-Suppression. Das Ausma ss der Radiojodaufnahme beim metastasierten Schilddrusenkarzinom spielt eine signifikante Rolle bei der Einschatzung der Prognose. Das fehlende Jodspeicherungsvermogen einer Lasion in Zusammenschau mit dem fehlenden Abfall des Tumormarkers Thyreoglobulin sowie radiologische Zeichen einer Tumorprogression charakterisieren den Radiojod-refraktaren Patienten. Aufgrund des meistens uber einen langen Zeitraum indolenten Verlaufs erscheint in den meisten Fallen ein abwartendes Verhalten in Kombination mit lokaler Metastasenbehandlung sowie Symptomlinderung primar sinnvoll zu sein. Der Nachweis einer Veranderung der Tumordynamik ist der Zeitpunkt, um eine Systemtherapie zu evaluieren. Diese beruht auf Multi-Tyrosinkinase-Inhibitoren (Sorafenib, Lenvatinib). Diese Substanzen sind gro ss tenteils mit einem ungunstigen Nebenwirkungsprofil assoziiert (Diarrho, Hautauschlage, arterielle Hypertonie mit hypertensiver Entgleisung, lokale Wundheilungsstorungen), welches zu einer nicht vernachlassigbaren Rate einer therapieassoziierten Morbiditat sowie einer hohen Anzahl an Therapieunterbrechungen fuhrt. Daher sind im Jahr 2020 2 selektive RET-Inhibitoren (Selpercatinib, Pralsetinib) fur die differenzierten Schilddrusenkarzinome von der FDA zugelassen worden. Eine neue Perspektive fur die Zukunft waren die unterschiedlichen Redifferenzierungsstrategien, welche auf die Steigerung der Sensitivitat der Tumorzellen auf Radiojod abzielen.
CRIS-Team WoS Importer:2021-10-08

Treatment with (chemo)-radiation in old patients (≥76 years of age) with newly diagnosed non-metastatic squamous cell cancer of the head and neck region: real-world data from a tertiary referral center - Winkler, Leah-Sophie; Haderlein, Marlen; Semrau, Sabine; Putz, Florian; Höfler, Daniel; Müller, Sarina Katrin; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Schubert, Philipp (Frontiers in Oncology, 2024)
Purpose: Treatment of patients with cancer of the head and neck region is in focus in a multitude of studies. Of these patients, one patient group, those aged 76 and more, is mostly underrepresented despite requiring thorough and well-reasoned treatment decisions to offer curative treatment. This study investigates real-world data on curative treatment of old (≥76 years) patients with newly diagnosed squamous cell carcinoma of the head and neck region (HNSCC). Patients and methods: Between January 2010 and December 2021, we identified 71 patients older than 76 years with newly diagnosed HNSCC and cM0 at the Department of Radiation Oncology of the University Hospital of Erlangen-Nuremberg. Using electronic medical records, we analyzed treatment patterns and outcomes in terms of overall survival (OS), progression-free survival (PFS), and locoregional control (LRC) rate. Additionally, we performed univariate risk analysis and Cox regression in order to identify predictive factors associated with the abovementioned treatment outcomes. Results: The median follow-up was 18 months. OS was 83%, 79%, and 72% after 1 year, 2 years, and 3 years, respectively. PFS was 69%, 54%, and 46% after 1 year, 2 years, and 3 years, respectively. A total of 34 (48%) patients were treated with standard therapy according to current guidelines. The reasons for deviation from standard therapy before or during treatment were as follows: unfitness for cisplatin-based chemotherapy (n = 37), reduction of chemotherapy (n = 3), and dose reduction/interruption of radiotherapy (n = 8). Carboplatin-based systemic therapy showed improved PFS compared to cisplatin or cetuximab (60 vs. 28 vs. 15 months, p = 0.037) but without impact on OS (83 vs. 52 vs. 38 months, p = 0.807). Oropharyngeal tumor localization (p = 0.026) and combined treatment (surgery and postoperative treatment) (p = 0.008) were significant predictors for a better OS. In multivariate analysis, oropharyngeal tumor localization (p = 0.011) and combined treatment (p = 0.041) showed significantly increased PFS. After 1 year, 2 years, and 3 years, the cumulative incidence of locoregional recurrences (LRRs) was 13%, 24%, and 27%, respectively, and was significantly decreased in patients with oropharyngeal tumor localization (p = 0.037). Conclusions: Adherence to treatment protocols for radiotherapy alone in old patients with HNSCC is good, whereas the application of concurrent chemotherapy often deviates from guidelines in terms of de-escalation. An important risk factor for decreased OS, PFS, and a higher rate of LRR appears to be non-oropharyngeal tumor location in old patients.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemoradiation; head and neck cancer; old patients; squamous cell carcinoma; tumor localization

Tumour‐infiltrating lymphocytes (Tils) and pd‐l1 expression correlate with lymph node metastasis, high‐grade transformation and shorter metastasis‐free survival in patients with acinic cell carcinoma (acicc) of the salivary glands - Hiß, Selina; Eckstein, Markus; Segschneider, Paul; Mantsopoulos, Konstantinos; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian; Müller, Sarina Katrin (Cancers, 2021)
Objectives: The aim of this study was to assess the number of tumour‐infiltrating lympho-cytes (TILs) and the expression of Programmed Cell Death 1 Ligand 1 (PD‐L1) in Acinic Cell Carcinoma (AciCC) of the salivary glands, to enable a correlation with clinico‐pathological features and to analyse their prognostic impact. Methods: This single centre retrospective study represents a cohort of 36 primary AciCCs with long‐term clinical follow‐up. Immunohistochemically defined immune cell subtypes, i.e., those expressing T‐cell markers (CD3, CD4 and CD8) or a B‐cell marker (CD20) were characterized on tumour tissue sections. The number of TILs was quantitatively evaluated using software for digital bioimage analysis (QuPath). PD‐L1 expression on the tumour cells and on immune cells was assessed immunohistochemically employing established scoring criteria: tu-mour proportion score (TPS), Ventana immune cell score (IC‐Score) and combined positive score (CPS). Results: Higher numbers of tumour‐infiltrating T‐ and B‐ lymphocytes were significantly associated with high‐grade transformation. Furthermore, higher counts of T‐lymphocytes correlated with node‐positive disease. There was a significant correlation between higher levels of PD‐ L1 expression and lymph node metastases as well as the occurrence of high‐grade transformation. Moreover, PD‐L1 CPS was associated with poor prognosis regarding metastasis‐free survival (p = 0.049). Conclusions: The current study is the first to demonstrate an association between PD‐L1 expression and lymph node metastases as well as grading in AciCCs. In conclusion, increased immune cell infiltration of T and B cells as well as higher levels of PD‐L1 expression in AciCC in association with high‐grade transformation, lymph node metastasis and unfavourable prognosis suggests a rel-evant interaction between tumour cells and immune cell infiltrates in a subset of AciCCs, and might represent a rationale for immune checkpoint inhibition.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Acinic cell carcinoma; Checkpoint inhibition; Immuno‐oncology; PD‐L1; Tumour‐infiltrating lymphocytes

Tumour spillage of the pleomorphic adenoma of the parotid gland: A proposal for intraoperative measures - Mantsopoulos, Konstantinos; Iro, Heinrich (Oral Oncology, 2021)
Intraoperative rupture of a pleomorphic adenoma capsule with potential tumor spillage into the surgical field is thought to occur in approximately 5% of cases and has traditionally been recognized as one of the major causes of recurrence. It seems that recurrence of a pleomorphic adenoma is a multifactorial event, being related to surgery (capsular exposure, tumor spillage) and tumor-related factors (histologic subtype, incomplete capsule, pseudopodia, satellites). The exact quantities of these ingredients in the recipe of recurrence, as well as possible interactions between them (e.g. the potentially increased fragility of myxoid pleomorphic adenomas; satellites or pseudopodia being cut off the tumor specimen during an extremely narrow extracapsular dissection) remain unclear. A thorough literature search did not reveal any proposed algorithms for the intraoperative management of a capsular tear. The aim of this short communication is to present our department's experience-based proposal for intraoperative measures in the case of macroscopic rupture and tumor spillage of a parotid gland pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-01-08

Types of Sialendoscopes and Accessories - Marchal, Francis; Faure, Frederic; Koch, Michael; Iro, Heinrich; McGurk, Mark; Walvekar, Rohan R. (Elsevier, 2021)
CRIS-Team Scopus Importer:2024-12-16
Keywords: Accessories; Diagnostic Sialendoscope; Dilator; Interventional Sialendoscope; Modular Sialendoscope; Sialendoscope; Sialo-Balloon

Ultrasound and Sialendoscopy Findings in Radioactive Iodine–Induced Sialadenitis: Comparative Analysis and Possible Impact on Management - Koch, Michael; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Iro, Heinrich; Sievert, Matti (Journal of Clinical Medicine, 2024)
Background: To assess the correlation/association between ultrasound and sialendoscopy findings in radioactive iodine therapy–induced sialadenitis (RAIS). Methods: Patients presenting with RAIS were investigated with ultrasound and sialendoscopy. Four pathologic ultrasound parameters and seven pathologic sialendoscopy parameters were retrospectively assessed. Correlations/associations between ultrasound and sialendoscopy findings and associations between the changes between the first and last ultrasound and sialendoscopy findings were assessed separately for the parotid (PG) and submandibular glands (SMG). Results: Sixty-seven patients were included. In the first examination, 107 glands were investigated (PGs 88.8%, SMGs 11.21%), and in the last examination, 64 glands were investigated (90.6% PGs, 9.4% SMGs). Highly significant positive associations were observed between the severity or category of ultrasound and sialendoscopy findings for first and last examinations for PGs (both p = 0.0001) and SMGs (p = 0.002; p = 0.037). Duct dilation had a significant negative association with the sialendoscopy findings for PGs in the first and last examinations (both p = 0.0001), but not for SMGs. Comparison of changes in the ultrasound and sialendoscopy findings between the first and last examinations showed a significant positive association for PGs (p = 0.0001) but not for SMGs. Conclusions: Ultrasound and sialendoscopy findings for the parenchyma and duct system in RAIS showed significant associations/correlations and can be useful for effective management in RAIS.
CRIS-Team Scopus Importer:2024-06-14
Keywords: radioactive iodine; salivary gland; treatment; ultrasound: sialendoscopy

Ultrasound Changes in Salivary Glands after Radioactive Iodine Treatment in Benign Diseases and Differentiated Cancer of Thyroid Glands in Consideration of Dose and Time Dependency. - Koch, Michael; Fauck, Vanessa; Sievert, Matti; Mantsopoulos, Konstantinos; Iro, Heinrich; Müller-Hübner, Sarina Katrin Ursel (Ultraschall in der Medizin, 2024)
PURPOSE: To assess ultrasound (US) features observed in salivary glands after radioactive iodine treatment (RAIT) in relation to the dose and time interval after RAIT. MATERIALS AND METHODS: A retrospective analysis of US findings regarding the salivary glands of patients presenting after RAIT due to thyroid cancer (Group 1, n=99) or benign thyroid diseases (Group 2, n=25). The control group consisted of randomly selected patients (no RAIT, Group 3, n=100). Groups were compared regarding RAIT dose, symptoms, and US findings (duct dilation, hypoechoic/heterogeneous parenchyma, parenchymal loss). The association of the presence of US parameters after RAIT with various dose levels (2000-15000MBq) and time intervals (24, 60, 120 months) and the differences between the groups was evaluated. RESULTS: Significant differences between US parameters were noted when comparing Group 1 with Group 2 or 3. Nothing of relevant significance was noted when Groups 2 and 3 were compared. US features indicating a slight or moderate sialadenitis showed the most significant associations with doses <4000MBq and time intervals <24 months after RAIT. US changes indicating a serious sialadenitis or even gland atrophy showed the most significant association at doses between >7000-9000MBq and when US was performed >60 months after RAIT. CONCLUSION: Our results point to a dose and time dependency of pathologic US findings in RAIT-induced effects on the major salivary glands. Based on the US findings, a better estimation of the current impact of RAIT on the salivary glands and the further prognosis appears possible.
EVALuna2:567741

Ultrasound in Diagnosis of Magnet Dislocation of Cochlear Implants: A Retrospective Study in Patients With Surgical Magnet Repositioning and Preinterventional Ultrasound Examination - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Otology & Neurotology, 2020)
OBJECTIVE: To investigate whether ultrasound is a reliable diagnostic tool to identify magnet dislocation in patients with cochlear implant. DESIGN: Retrospective analysis. SETTING: A tertiary referral medical center. PATIENTS: Patients with cochlear implant who presented with the suspicion of magnet dislocation between January 1, 2009 and July 31, 2019. INTERVENTIONS: Preinterventional ultrasound with subsequent surgical magnet repositioning. MAIN OUTCOME MEASURES: Accuracy of ultrasound in detecting magnet dislocation; intraoperative extent of magnet dislocation. RESULTS: Out of the 28 included patients (n = 28 magnets, 36% ♀; 51.6 years [±19.0 yr]) the diagnosis by the preoperative ultrasound was confirmed intraoperatively in 25 patients (89%). In two cases (7%), tissue swelling impeded the determination of the magnet by the preoperative ultrasound. In one case, ultrasound misdiagnosed the magnet as not dislocated. During revision surgery, all 28 magnets were repositioned successfully revealing a predominant partial dislocation (86%) compared with complete magnet dislocation (14%). CONCLUSION: In CI-patients undergoing 1.5 Tesla MRI, partial magnet dislocation occurs much more frequently than complete magnet dislocation. The clinical suspicion of a dislocated cochlear implant magnet can be accurately confirmed by preoperative ultrasound. Thus, preoperative diagnostic ultrasound can be advocated as the diagnostic tool of first choice.
CRIS-Team Scopus Importer:2020-09-25

Ultrasound in inflammatory and obstructive salivary gland diseases: Own experiences and a review of the literature - Koch, Michael; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos; Schapher, Mirco (Journal of Clinical Medicine, 2021)
Background: Ultrasound is established as a diagnostic tool in salivary glands for obstructive diseases such as sialolithiasis and tumors. Concerning inflammatory diseases and in non-sialolithiasis-caused obstruction, much fewer data are available. In recent years, technical devel-opment has allowed a better assessment of the gland parenchyma, and knowledge about intraductal pathologies has increased considerably, which has provided new insights and a new interpretation of ultrasound findings. Objectives: To provide a comprehensive review of the literature that in-cludes our own experiences and to point out the state of the art in ultrasound in the diagnostics of inflammatory and obstructive salivary gland diseases, taking adequate techniques and recent technical developments into consideration. Data sources and study eligibility criteria: A systematic literature search was performed in Pubmed using various specific key words. Results: According to the literature results, including our own experiences, ultrasound is of value in up to >90% of cases presenting with inflammatory and/or obstructive diseases. Technical developments (e.g., elastography) and the application of modified ultrasound techniques (e.g., transoral ultrasound) have contributed to these results. Today, ultrasound is considered a first-line diagnostic tool in these diseases. However, in some inflammatory diseases, the final diagnosis can be made only after inclusion of the anamnesis, clinical symptoms, serologic blood tests, or histopathologic investiga-tion. Conclusions: Ultrasound can be considered as a first-line diagnostic tool in obstructive and inflammatory salivary gland diseases. In obstructive diseases, it may be sufficient for diagnostics in >90% of cases. In inflammatory diseases, ultrasound is at least an excellent screening method and can be used to establish the diagnosis in cases of an early suspicion. In all diseases ultrasound can contribute to better management and can be used for monitoring during follow-up.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Inflammatory; Obstructive; Salivary calculi; Salivary gland; Salivary gland diagnosis; Salivary gland disorders; Salivary ultrasonography; Sialadenitis

Ultrasound in the Assessment of Parotid Duct Stenosis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Journal of Ultrasound in Medicine, 2019)
Objectives Parotid duct stenosis may occur with or without accompanying ductal anomalies, with associated differences in their pathogenesis and management. By identifying the characteristics of a stenosis, ultrasound (US) can assist in tailored management of parotid duct stenosis. The objective of this study was therefore to describe the US characteristics of parotid duct stenoses and to evaluate criteria for whether and in what ways these can be distinguished from each other by using US. Methods A total of 108 patients who presented with parotid duct stenoses (130 parotid glands) were examined with high-resolution US between 2014 and 2017. The stenoses were assessed for duct dilatation, location, signs of ductal anomalies (circular encroachments/webs, duct bending/kinking, and presence of a megaduct) and the echogenicity of the gland parenchyma. Results Ultrasound was able to distinguish between stenoses associated with ductal anomalies and those without anomalies. Webs (82.5% versus 7.8%; P < .001), kinking (75.0% versus 3.3%; P < .001), and a megaduct (87.50% versus 15.63%; P < .001) and a tendency toward normal echogenicity in the gland parenchyma (77.5% versus 25.6%; P < .001) were significantly associated with ductal anomalies. Stenoses associated with ductal anomalies also had significantly larger duct diameters in comparison with those without anomalies (mean +/- SD, 9.19 +/- 3.65 versus 3.27 +/- 2.17 mm; P < .001). Conclusions This study describes US parameters that allow more detailed characterization of parotid stenoses with or without accompanying ductal anomalies. Differentiating between these at an early stage may be helpful for decision making on the further management in these patients.
CRIS-Team WoS Importer:2019-11-01

Ultrasound in the diagnosis and differential diagnosis of enoral and plunging ranula: a detailed and comparative analysis - Koch, Michael; Mantsopoulos, Konstantinos; Leibl, Victoria; Müller, Sarina Katrin; Iro, Heinrich; Sievert, Matti (Journal of Ultrasound, 2022)
Purpose To develop sonographic criteria for ranula that to allow rapid and precise diagnosis, differentiation between enoral (ER) and plunging ranula (PR), and differential diagnosis from other competing pathologies in this region.Methods Patients who presented with or were referred with ranula between 2002 and 2022 were assessed in a retrospective study. After clinical investigation, ultrasound examinations were performed in all cases. Several sonographic parameters describing the echotexture, shape and size of ranulas, their relationship to important surrounding anatomical landmarks and the characteristic spreading pattern of ERs and PRs were elaborated and evaluated.Results 207 ranulas were included (82.12% ERs and 17.87% PRs). The ranulas were all in close anatomical relationship to the sublingual gland (SLG) and mylohyoid muscle (MM). The echo texture was hypoechoic to anechoic in 97.6% of the lesions. In comparison with ERs, PRs were larger and irregular in shape significantly more often (P = 0.0001). There were significant differences between ERs and PRs in their exact location relative to the SLG (superficial, deep, anterior, each P = 0.0001; posterior, P = 0.03) and level of the MM (above, below, above and below, P = 0.0001 each). The exact extent and plunging pattern were depicted in all PRs, but naturally in none of the ERs.Conclusions The ultrasound criteria developed in this study, confirming previously published results, indicate that ultrasound is an excellent diagnostic tool for diagnosing ranula and differentiating between ERs and PRs.
CRIS-Team WoS Importer:2023-01-20

Ultrasound in the diagnosis of parotid duct obstruction not caused by sialolithiasis: diagnostic value in reference to direct visualization with sialendoscopy - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Dentomaxillofacial Radiology, 2021)
Objectives: The aim of this study was to evaluate the diagnostic value of ultrasound in the obstructive pathology of the parotic gland not caused by sialolithiasis using sialendoscopy as reference standard.
CRIS-Team WoS Importer:2021-03-26

Ultrasound Supplemented by Sialendoscopy: Diagnostic Value in Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Otolaryngology-Head and Neck Surgery, 2018)
Objective To assess the value of ultrasound, if indicated, supplemented by sialendoscopy, in the diagnosis of sialolithiasis. Study Design Retrospective study. Setting Referring center for salivary gland diseases. Subjects and Methods All patients who presented with a suspected diagnosis of obstructive sialopathy between January 2011 and April 2017 and had not undergone any treatment were retrospectively evaluated. A total of 2052 patients and 2277 glands were included in the study. Ultrasound examinations were carried out initially and followed by sialendoscopy in all cases. Direct demonstration of sialothiasis by sialendoscopy, transoral ductal surgery, and discharge of concrements/observation of fragments during sialendoscopy after extracorporeal shock-wave lithotripsy were regarded as definitive evidence of sialolithiasis. Results Ultrasound had an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 94.77%, 94.91%, 94.57%, 96.14%, and 92.89%, respectively, for the diagnosis of sialolithiasis. All false-positive findings were correctly diagnosed, and in all false-negative findings, stones/fragments were visualized by sialendoscopy. Over 95% of the false-negative findings in major salivary glands (64/67) had visible ductal dilation in sonography, and in 73.1%, the stones not detected on ultrasound were located in the distal part of the duct, which is easily accessible with the sialendoscope. Conclusion This study shows that sialolithiasis can be diagnosed using ultrasonography with a high degree of certainty. If supplemented by sialendoscopy, the correct diagnosis could be established in virtually all cases of sialolithiasis. Ultrasound supplemented by sialendoscopy has the potential to serve as an alternative diagnostic standard in the future.
EVALuna2:35387

Unexpected Detection of Parotid Gland Malignancy during Primary Extracapsular Dissection - Mantsopoulos, Konstantinos; Velegrakis, Stylianos; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2015)
To evaluate the oncologic and functional outcome in cases in which a false preoperative working hypothesis "benign parotid tumor" led to a primary extracapsular dissection being performed rather than a traditional, more radical surgical modality.Case series with chart review.Academic tertiary referral center.The records of all patients treated for malignant tumors of the parotid gland between 2006 and 2012 were retrospectively studied. Patients were excluded from our study sample for insufficient data or if their histories indicated manifestation of malignant tumors without primary parotid origin (squamous cell carcinomas, lymphomas, melanomas), revision surgery, as well as concomitant or past malignant tumors. Consequently, a total of 29 patients with 30 primary malignant tumors of the parotid gland formed our study sample (14 men, 15 women; male:female ratio, 0.93:1; mean age, 55.4 years; range, 14-85 years).Of 30 cases, 22 had low-grade tumors. Further tumor cells were detected in only the histology specimens of the parotid in 3 of the 25 cases treated subsequently with completion parotidectomy. Five patients received adjuvant radiation. Five-year disease-specific survival was 100%; local disease control was 96.6%. Of 30 cases, 28 had House-Brackmann I after tumor treatment; the other 2 cases had a slight paralysis (House-Brackmann II).Beginning with the "false" working hypothesis and performing an extracapsular dissection in unsuspected cases seems to have no adverse impact on patients' survival and postoperative quality of life in cases in which definitive histology reveals malignancy.
EVALuna2:19991

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16

Updated S2k AWMF guideline on obstructive sialadenitis Aktualisierte AWMF-S2k-Leitlinie zur obstruktiven Sialadenitis - Geisthoff, Urban; Al-Nawas, Bilal; Beutner, Dirk; Günzel, Thomas; Iro, Heinrich; Koch, Michael; Lell, Michael; Luers, Jan Christoffer; Schröder, Ursula; Sproll, Christoph; Teymoortash, Afshin; Uβmüller, Jürgen; et al. (Laryngo-Rhino-Otologie, 2021)
The update of this guideline was an important step to define standards for the use of sialendoscopy and other emerging minimally invasive techniques for the therapy of sialolithiasis and other obstructive salivary gland diseases. The current actualization was necessary to adapt the diagnostic and therapeutic algorithms to the current scientific knowledge. In this article they are presented in a shortened version with a focus on conservative therapeutic measures which are especially relevant for daily practice.
CRIS-Team Scopus Importer:2021-10-22
Keywords: guideline; meta-analysis; salivary duct stenosis; sialadenitis; sialolithiasis; therapy

Validation of a classification and scoring system for the diagnosis of laryngeal and pharyngeal squamous cell carcinomas by confocal laser endomicroscopy - Sievert, Matti; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Rupp, Robin; Eckstein, Markus; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Aubreville, Marc; Iro, Heinrich; Goncalves, Miguel (Brazilian Journal of Otorhinolaryngology, 2021)
Introduction: Confocal laser endomicroscopy is an optical imaging technique that allows in vivo, real-time, microscope-like images of the upper aerodigestive tract's mucosa. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignant suspected mucosa requires strict evaluation criteria. Objective: This study aims to validate an eight-point score for the correct assessment of malignancy. Methods: We performed confocal laser endomicroscopy between March and October 2020 in 13 patients. 197 sequences (11.820 images) originated from the marginal area of pharyngeal and laryngeal carcinomas. Specimens were taken at corresponding locations and analyzed in H&E staining as a standard of reference. A total of six examiners evaluated the sequences based on a scoring system; they were blinded to the histopathological examination. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are interrater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. Confocal laser endomicroscopy of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 83.2%, 81.3%, 85.5%, 86.7%, and 79.7%, respectively, with a κ-value of 0.64, and an area under the curve of 0.86. Conclusion: The results confirm that this scoring system is applicable in the laryngeal and pharyngeal mucosa to classify benign and malignant tissue. A scoring system based on defined and reproducible characteristics can help translate this experimental method to broad clinical practice in head and neck diagnosis.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Confocal laser endomicroscopy; Diagnosis; Head and neck cancer; Squamous cell carcinoma

Validity of tissue homogeneity in confocal laser endomicroscopy on the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma - Sievert, Matti; Aubreville, Marc; Gostian, Antoniu-Oreste; Mantsopoulos, Konstantinos; Koch, Michael; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Rupp, Robin; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; et al. (European Archives of Oto-Rhino-Laryngology, 2022)
Purpose: Confocal laser endomicroscopy (CLE) allows imaging of the laryngeal mucosa in a thousand-fold magnification. This study analyzes differences in tissue homogeneity between healthy mucosa and squamous cell carcinoma (SCC) via CLE. Materials and methods: We included five SCC patients with planned total laryngectomy in this study between October 2020 and February 2021. We captured CLE scans of the tumor and healthy mucosa. Analysis of image homogeneity to diagnose SCC was performed by measuring the signal intensity in four regions of interest (ROI) in each frame in a total of 60 sequences. Each sequence was assigned to the corresponding histological pattern, derived from hematoxylin and eosin staining. In addition, we recorded the subjective evaluation of seven investigators regarding tissue homogeneity. Results: Out of 3600 images, 1620 (45%) correlated with benign mucosa and 1980 (55%) with SCC. ROIs of benign mucosa and SCC had a mean and standard deviation (SD) of signal intensity of, respectively, 232.1 ± 3.34 and 467.3 ± 9.72 (P < 0.001). The mean SD between the four different ROIs was 39.1 ± 1.03 for benign and 101.5 ± 2.6 for SCC frames (P < 0.001). In addition, homogeneity yielded a sensitivity and specificity of 81.8% and 86.2%, respectively, regarding the investigator-dependent analysis. Conclusions: SCC shows a significant tissue inhomogeneity in comparison to the healthy epithelium. The results support this feature’s importance in identifying malignant mucosa areas during CLE examination. However, the examiner-dependent evaluation emphasizes that homogeneity is a sub-criterion that must be considered in a broad context.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

Value of confocal laser endomicroscopy in the diagnosis of vocal cord lesions - Goncalves, M.; Iro, Heinrich; Dittberner, A.; Agaimy, Abbas; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2017)
The aim of this study was to assess the reliability and limitations of confocal laser endomicroscopy (CLE) for diagnosing lesions of the vocal cords and differentiating malignant from non-malignant lesions.During microlaryngoscopy, the vocal cords were scanned by probe-based CLE (pCLE: a GastroFlex probe with the Cellvizio® laser system, Mauna Technologies, Paris, France). The video recordings were analyzed and compared with the histological results. Thirty-one representative images were extracted and presented to four medical professionals (blinded examiners) for assessment.The accuracy for the category malignant/nonmalignant ranged between 58.1% and 87.1%. Overall interrater reliability was 0.29. Sensitivity ranged between 45.5 and 100%, specificity between 60.0 and 100%, PPV between 38.5% and 100% and NPV between 66.7 and 100%.CLE is a promising method for the non-invasive diagnosis of vocal cord lesions in vivo, but factors such as small penetration depth, not available contrast media for the nuclei and subjective analyses of the images limit, at the moment, its diagnostic value.
EVALuna2:6891

Value of Sonography in the Diagnosis of Sialolithiasis: Comparison With the Reference Standard of Direct Stone Identification - Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich; Wüst, Wolfgang; Mantsopoulos, Konstantinos; Koch, Michael (Journal of Ultrasound in Medicine, 2017)
The aim of this study was to assess the effectiveness of sonography for diagnosing sialolithiasis in comparison with the existing reference standard of direct identification of a stone.A total of 659 glands with signs of obstructive sialadenopathy were evaluated retrospectively. Sonographic examinations of the large head salivary glands had been performed initially in all cases. Direct depiction of a stone during sialoendoscopy or transoral ductal surgery or observation of stone fragmentation with discharge of concrements after extracorporeal shock wave lithotripsy, was regarded as definitive evidence and as the reference standard for the presence of sialolithiasis. The sonographic results were compared with those for direct identification of stones.The sensitivity of sonography was 94.7%, with specificity of 97.4%, a positive predictive value of 99.4%, and a negative predictive value of 79.6%. Stones that were not diagnosed correctly on sonography were most often located in the distal area of the duct.These results show that sialolithiasis can be diagnosed by sonography with a high degree of certainty. Sonography thus appears to be highly appropriate as the examination method of choice.
EVALuna2:14673

Voice Handicap and Health-Related Quality of Life after Treatment for Small Laryngeal Carcinoma - Killguß, Helen; Gottwald, Frank; Haderlein, Tino; Maier, Andreas; Rosanowski, Frank; Iro, Heinrich; Psychogios, Georgios; Schuster, Maria (Folia Phoniatrica Et Logopaedica, 2011)

Watchful waiting in carefully selected metachronous cystadenolymphomas of the parotid gland: a reliable option? - Mantsopoulos, K.; Goncalves, Miguel; Koch, M.; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2019)
The aim of this study was to evaluate the potential of watchful waiting in the treatment of metachronous cystadenolymphomas, taking the experience of our department into consideration. All patients suspected of having a metachronous cystadenolymphoma, and who had a minimum follow-up time of 12 months, were studied (n = 26). Data about the growth rate, number of lesions, and symptoms of inflammation were recorded. Mean (range) follow-up was 36 (13–94) months. Metachronous tumours developed in three cases on the ipsilateral side, in 22 cases on the contralateral side, and on both sides in one case. The mean rate of growth /lesion was 15% /year (range: 22%–158%). There were no signs of local inflammation. The extreme variability in the behaviour of metachronous cystadenolymphomas points to the need for an individualised approach, accurate investigation of the sonographic characteristics, and continuous watchful waiting in affected patients.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Benign tumours; Cystadenolymphoma; Parotid gland; Warthin tumour; Watchful waiting

Zufallsbefund Schilddrüsenknoten: Stellenwert der Sonographie und Szintigraphie in der Primärdiagnostik - Richter, Daniel; Beck, Michael; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael; Sievert, Matti (HNO, 2024)
Due to the widespread use of high-resolution sonography, numerous thyroid nodules are diagnosed, often as incidental findings. The challenge lies in evaluating various criteria such as size, shape, and echogenicity to assess the nodules’ malignancy risk. Risk stratification systems have been developed to enable systematic assessment as well as to avoid unnecessary medical interventions and malignant findings being overlooked. This article provides an overview of the current diagnostic standards in primary assessment of thyroid nodules.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Calcitonin; Cytology; Diagnostic imaging; Fine needle aspiration; Thyroid neoplasms